SND1 regulates the androgen signaling axis by stabilizing EIF3B mRNA to facilitate the deterioration of prostate cancer - Ying Li; Chengru Yang; Guoli Cui; Shiliang Gui; Linlin Jia; Yu Chen; Honglin Niu; Hua Xin (Molecular Genetics and Genomics, 2026)

Intrauterine exposure to HBsAg attenuates the immune response to hepatitis B vaccine via the miR-155-5p/MyD88 axis of DCs in mouse pups - Xufeng Cui; Jia Lian; Yangle Sun; Xiaosheng Zhang; Bihong Ke; Xinyuan Mo; Ying Zhang; Tian Yao; Yandi Li; Linying gao; Keke wang; Suping Wang; et al. (Medical Microbiology and Immunology, 2026)

Human YTHDC2 mutations disturb RNA homeostasis of oocytes and early embryos - Wei Su; Yang Wang; Jiaqi Sun; Changlong Zhang; Changjian Yin; Ying Cui; Xiaolei Chen; Bohan Yang; Shigang Zhao; Keliang Wu; Ge Lin; Zi-Jiang Chen; et al. (Human Genetics, 2026)

PbrFEN-1 positively regulates pear pollen tube growth and is involved in the self-incompatibility response - Zhi-Heng Sui; Yi-Peng Ye; Ju-Yang Yao; Ya-Ru Wang; Ying Xu; Ce-Xian Cui; Shao-Ling Zhang; Chao Gu (Plant Reproduction, 2026)

Sepiolite-driven facet reconstruction of MOFs: Multi-pathway enhancement for ultrafast antibiotic degradation - Haishuai Cui; Sheng Jiang; Hailin Wang; Ying Lan; Yang Ma; Weijie Zhang; Huiyue Xin; Fuhua Huang; Huajie Liu; Hai Yang (Applied Clay Science, 2026)

Restoration of membrane potential rescues organelle function via NS309-mediated KCa activation in aged porcine oocytes - Ying-Yan Jin; Cheng-Lin Zhan; Song-Hee Lee; Ji-Yeon Lee; Xiang-Shun Cui (Theriogenology, 2026)

Particle-associated distribution, sedimentary accumulation, and SSD-based ecological risk assessment of organochlorine pesticides in the East China Sea - Jie Fu; Longkun Sun; Yan Zhang; Wenqing Wang; Zhongyu Cui; Zhen He; Chun-Ying Liu; Dong-Liang Lu; Gui-Peng Yang (Marine Environmental Research, 2026)

From molecular assembly to functionality: structural characterization of chestnut 11S globulin and its implications for thermal gelation and bioactive peptide release - Haoxin Cui; Ying Zhang; Dongze Qin; Fan Wei; Zhenting Yu; Sihao Wu; Yazhou Ji; Wenhui Fu; Yan Zhang; Ruican Wang; Shuo Wang (Food Hydrocolloids, 2026)

Dual roles of static magnetic field on enhancing sulfamethoxazole biodegradation and preventing antibiotic resistance genes transfer in halotolerant fungal-bacterial sludge treating saline aquaculture wastewater - Zhen-Ying Li; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Yuan Sui (Bioresource Technology, 2026)

Rainfall modulates the divergent responses of bacterial and fungal communities to naphthalene contamination in soil - Yuntao Zhao; Duo Zhang; Xin Wang; Yong Cui; Ying Guo; Wei Su; Chen Hong; Wenxin Li; Mengwan Lin; Yixiang Chen; Haobo Ya; Jiayu Chen; et al. (Applied Soil Ecology, 2026)

Progressive fluorescence amplification of molecular rotors via G-run-length engineering of G-rich DNA scaffolds - Ruo-Yao Cui; Yu-Chao Cao; Yi-Xuan Gu; Ling-Li Zhao; Xu-Yang Shen; Ying Liu; Ying-Lin Zhou; Xin-Xiang Zhang (Analytica Chimica Acta, 2026)

Long-term nitrogen deposition weakens the CH4 sink capacity, but enhances the CO2 and N2O source potential of the alpine grassland soil - Hang Shi; Xiaoqing Cui; Shikui Dong; Zilong Liu; Ran Zhang; Ke Zhang; Xueqi Li; Yuhao Zhang; Hui Zuo; Fengcai He; Xianqi Zhou; Mingjie Ran; et al. (Agriculture, Ecosystems & Environment, 2026)

Dual-site magnetic microporous organic networks enabling high-performance capture and quantification of per- and polyfluoroalkyl substances - Chun-Ying Xu; Qing-Zhi Hou; Xiang-Sheng Xue; Zhan-Hui Qiu; Yuan-Yuan Cui; Cheng-Xiong Yang (Water Research, 2026)

Patterns and mechanisms of cross-media antimicrobial resistance development in a typical reclaimed water-receiving urban river - Bang-Ze Li; Shu-Hao Du; Han-Lin Cui; Xin-Xin Gao; Jia-Hao Wu; Bei-Ying Li; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2026)

Development and protective efficacy of a live attenuated vaccine candidate against goose astrovirus - Yifeng Qin; Xiaofang Wei; Chang Cui; Kang Ouyang; Ying Chen; Zuzhang Wei; Weijian Huang (Veterinary Microbiology, 2026)

Effect of net submergence depth on the dynamic response of a bottom-supported aquaculture cage - Guo-Hai Dong; Qi-Ying Sun; Sen-Qi Cui; Chun-Wei Bi (Ocean Engineering, 2026)

Whole genome sequencing reveals the phylogenetic relationships and reticulate evolution of Phrynocephalus lizards in Eurasia - Lin Cui; Roman A. Nazarov; Ying Chen; Yin Qi; Xianguang Guo; Yun Xia; Weizhao Yang (Molecular Phylogenetics and Evolution, 2026)

In-situ growth of modified Fe/Co bimetallic MOFs on carbon felt for highly efficient electro-Fenton catalysis - Ying Li; Mengmeng Cui; Xinlu Ma; Jinwei Liu; Hua Li (Journal of Water Process Engineering, 2026)

Development of a NIR fluorescent probe HDI based on Zinc-mediated competitive coordination for multidimensional detection of glyphosate in complex systems - Ya-Tong Liu; Xi-Yue Luo; Bu-Xiao Wu; Yi-Wen Cui; Jun-Wen Wang; Ying-Kai Yuan; Yue-Li Zou; Li-Xia Zhao (Journal of Environmental Chemical Engineering, 2026)

Mechanism of surface-functionalized materials for efficient iodide removal: Performance and theoretical insights - Meng Ren; Xuedan Cui; Sai Yuan; Ying Yang; Xiaotian Xu; Pengjie Zhao; Tianda Pu; Guilan Duan; Yinjie Zhang; Aijun Lin (Journal of Environmental Chemical Engineering, 2026)

Chemical recycling technologies for end-of-life photovoltaic modules: A comprehensive review - Jianming Zhu; Yongbo Deng; Xuwen Cai; Renyin Cui; Junnan Wang; Yujie Cao; Ying Lu; Xiaoyan Wang; Qing Huang; Wenyi Yuan (Journal of Environmental Chemical Engineering, 2026)

High-performance and stable MgFe-layered double hydroxide catalysts for green synthesis of dimethyl carbonate - Cui Qiao; Yunong Li; Qian Su; Yong Li; Ying Liu; Xiaoling Gao; Zifeng Yang; Yifan Liu (Fuel, 2026)

Alcohol and high-fat diet aggravate colitis-induced liver injury via glucocorticoid/IL-6-SAA1 axis in mice - Mingrui Zhao; Han Li; Xinghua Gao; Huijuan Da; Xun Cui; Dongquan Jing; Qixiang Zhao; Ying Wang; Yanling Guo; Zhenhua Gao; Shentian Zhuang; Qiuhua Cao (Food and Chemical Toxicology, 2026)

Perchlorate exposure in Chinese primary children: Levels, potential health risks, and association with sexual development - Yang Xiang; Cui-Lan Bai; Ting-Ting Xu; Yu-Ling Luan; Liang-Ying Liu; Li-Ning Zhao; Ying Guo (Environmental Pollution, 2026)

Zeolitic imidazolate framework enabled heat-resistant enzymatic biosensor for real-time and non-invasive detection of glucose - Qingwen Zhang; Meiling Yuan; Jingwen Chen; Ying Yang; Meng Lu; Chaoyue Cui; Xiaohu Liu; Hu Chen; Yi Wang (Chemical Engineering Journal, 2026)

Climate and limited soil development constrain the distribution of the highest alpine grassline: Insights from a transplanting and warming experiment - Pengfei Ma; Haoze Zhang; Haijuan Wei; Guangshuai Cui; Zhaoheng Deng; Wanglin Zhao; Xinru Zhang; Ying Guo; Liu Yang; Lin Zhang (CATENA, 2026)

Disintegrated halophilic aerobic granular sludge restoration using zinc oxide nanoparticles: synergistic effects of fungal toxicity inhibition and extracellular polymeric substances production - Ya-Nan Mi; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Zhen-Ying Li; Xu-Zhen Liu; Tong Ren (Bioresource Technology, 2026)

Hydrochar-derived organic fertilizers: Application potential in soil, soil-crop responses, and life cycle assessment - Ying Gao; Bo Yang; Qiang Wang; Haojie Cui; Haixin Guo (Biomass and Bioenergy, 2026)

Vertical redistribution of iron-bound organic carbon and microbial functional shifts across a mangrove restoration chronosequence: redox-mediated constraints on blue carbon stabilization - Hongcheng Li; Jiantong Liu; Qiuxia Chen; Ying Cui; Xiuzhen Li; Zhongzheng Yan (Marine Pollution Bulletin, 2026)

A Bibliometric Review of Blue Carbon Ecosystem Restoration Technologies - Yanbo Ai; Ying Cui (Regional Studies in Marine Science, 2026)

Novel RHOXF1 mutation causes male infertility by inducing severe oligoasthenozoospermia - Yinshan Jin; Ying Shi; Yuanqing Cui; Jie Chen; Xuebao Zhang; Xiong Wang (Reproductive Biology, 2026)

A combined hazard to mariculture: Quality and safety impairment associated with intestinal barrier disruption in fish co-exposed to environmentally relevant microplastics and antibiotics - Lin Zhu; Changlong Cui; Ying Bai; Xuemei Sun; Qi Sui; Nurzafirah Mazlan; Bin Xia (Journal of Hazardous Materials, 2026)

Geometry and topology of the fault network in the Yingmai 2 Area, Tarim Basin,China: implications for reservoir connectivity and hydrocarbon accumulation - Lijie Cui; Yuxi Niu; Yawen Huang; Ye Tao; Yongrui Chen; Ying Hu (Journal of Asian Earth Sciences, 2026)

Recruitment is the key process that improves trait-based predictions of tree range shifts - Yujun Feng; Yi Zheng; Jin Yin; Yue Bin; Pengcheng He; Dongxu Zhang; Honglin Cao; Ying Lei; Boao Zhang; Jinggang Zhou; Bo Cui; Wanhui Ye; et al. (Forest Ecology and Management, 2026)

TBK1 associates with TRIF and TRAF3 related IRF3, IRF7, and type I IFN signaling in large yellow croaker Larimichthys crocea - Ying Li; Wen Qi Zha; Wen Feng Cui; Meng Jia Li; Yan Mi Na Chen; Qiu Ye Huang; Qiao Yun Yang; Ying Jia Shen; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Carbon source-driven anaerobic assimilation of dye-derived dissolved organic nitrogen: A low-carbon strategy with performance and mechanism insights - Xumeng Lin; Huahan Huang; Ying Wu; Ling Xiong; Yang Meng; Faheem Ahmed Ghori; He Cui; Yinchuan Yang; Hong Chen; Gang Xue (Environmental Research, 2026)

Engineering acyclovir-mediated immune and stromal reprogramming to overcome multidrug resistance in tumors - Dan Zhu; Shujie Tian; Ying Cui; Zhixuan Wang; Ziting Zhang; Biqing Bao; Nadezhda Cherdyntseva; Yewei Zhang; Miaomiao Xu; Lixing Weng (Chemical Engineering Journal, 2026)

Bioinspired core-shell structured electrospun fibers guide neural stem/progenitor cell lineage development for spinal cord injury repair - Jiaxin Chen; Zilong Rao; Rui Cui; Rongli Deng; Jing Zhou; Daping Quan; Xipeng Guan; Houqing Long; Ying Bai (Chemical Engineering Journal, 2026)

Chirality-dependent catalytic activity of nanozymes for accelerated healing of infected wounds - Ying Lu; Shuaishuai Cui; Yang Zhang; Li Wu; Yujian He (Chemical Engineering Journal, 2026)

Wearable multifunctional conductive fabrics for integrated smart monitoring and protection of the human body - Miao Miao; Wendi Liu; Wuwei Bao; Rui Ma; Hao Yao; Zhenzhe Huang; Zixuan Lin; Ying Han; Wentao Shen; Yao Wang; Yifan Cui; Xinyang He (Chemical Engineering Journal, 2026)

Structure characterization and multi-target inhibitory activities of fucosylated chondroitin sulfate from sea cucumber Thelenota anax - Ying Hong; Ying Pan; Guangyu Zhu; Jing Wen; Rou Chen; Lige Cui; Huilin Chen; Tong Wu; Ronghua Yin; Jinhua Zhao (Carbohydrate Polymers, 2026)

RNAi-mediated immune suppression enhances Serratia marcescens pathogenicity against the oriental fruit fly, Bactrocera dorsalis - Bingbing Wei; Xun Cui; Qiongyu Jiao; Haocun Yang; Gregory Oluwole Ijiti; Yi Liu; Guijian Zhang; Ying Yan; Changying Niu (Journal of Pest Science, 2026)

Climatic, soil, and rhizosphere fungal drivers of flavonoid composition in Scutellaria baicalensis - Ying Liao; Xiaojian Chen; Xuan Du; Jintao Jia; Yahao Xu; Yi Qiang; Bixin Bai; Langjun Cui; Yulong Li (Applied Soil Ecology, 2026)

Influence of cold-tolerant Lactiplantibacillus plantarum L75 inoculation on fermentation quality, aerobic stability and microbial composition of wrapped oat silage in the alpine region - Ying Liang; Hao Guan; Rina Su; Xinyuan Cui; Guanghao Xia; Zohreh Akhavan Kharazian; Mengya Jia; Qiang Li; Xusheng Guo (Animal Feed Science and Technology, 2026)

Context-dependent responses of soil greenhouse gases to grassland restoration: A global meta-analysis - Yu Zhang; Xiaoqing Cui; Hang Shi; Zilong Liu; Ying Li; Zuyan Ma; Shikui Dong (Plant and Soil, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

A “dual thiol-yne click” post-synthesis strategy for bifunctional magnetic microporous organic networks enabling synergistic extraction of trace benzoylurea insecticides - Chun-Xiao Liu; Chun-Ying Xu; Yuan-Yuan Cui; Cheng-Xiong Yang (Journal of Hazardous Materials, 2026)

Molecular succession and transformation of soil dissolved organic matter under long-term polybutylene adipate-co-terephthalate and polyethylene microplastic disturbance - Runhao Bai; Xiaowei Liu; Wei Wang; Weiran Wang; Ying Zhang; Jixiao Cui; Yue Wang; Qin Liu; Qi Liu; Wenqing He (Journal of Environmental Chemical Engineering, 2026)

Icaridin-loaded copper(II) chloride-cyclodextrin metal-organic framework for jellyfish repellency - Muzi Yang; Yuxiao He; Qiuming Zhou; Shiyu Zheng; Feng Li; Siying Yang; Ying Cui; Li Wu; Yue Wang; Liang Fang; Jiwen Zhang; Liang Xiao (Journal of Environmental Chemical Engineering, 2026)

Microenvironmental reshaping and photosynthetic recovery: Artificial microbial consortium mediated mechanism for tolerance to combined low-temperature and atrazine stress in soybean seedlings - Siyue Han; Yonghui Huang; Binyu Zhao; Yunhe Cui; Yue Tao; Wentao Dang; Yan Zhang; Jianhua Qu; Ying Zhang (Journal of Environmental Sciences, 2026)

Sedimentation rate changes revealing the evolution of circum–Arctic ice sheets since the Last Interglacial - Song Zhao; Dong Wu; Yu-Ying Zhang; Chao Cui; Sen Shan; Peng Ren; Lin-Sen Dong; Wei-Bin Zhang; Shu-Wei Sun; Yan-Guang Liu (Global and Planetary Change, 2026)

Corrigendum to “The differential effects of sodium chloride on the formation of amyloid-like fibrils derived from glutenin and gliadin” [Food Chem. 520 (2026) 149793] - Ying Liang; Huiqun Wang; Weiwei Xing; Jikai Zhao; Keshu Wang; Hao Liu; Baoshan He; Liuqing Cui; Jinshui Wang (Food Chemistry, 2026)

The differential effects of sodium chloride on the formation of amyloid-like fibrils derived from glutenin and gliadin - Ying Liang; Huiqun Wang; Weiwei Xing; Jikai Zhao; Keshu Wang; Hao Liu; Baoshan He; Liuqing Cui; Jinshui Wang (Food Chemistry, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Layer-by-layer assembly of polycationic electrolytes onto cation exchange membranes for enhanced Li+/Mg2+ selectivity: A comparative study of polyethyleneimine and chitosan - Jiadi Ying; Zhen Cui; Xiaoxiang Xi; Junwei Zhu; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Yaochun Chen; Minfeng Zeng; et al. (Desalination, 2026)

Regulating spin states via building asymmetric CoTe dual-atom pairs for efficient bifunctional oxygen electrocatalysis in zinc-air batteries - Sichen Huo; Yanjie Chen; Xinyu Wang; Hang Yue; Wenjing Cui; Shuang Shi; Huanyu Guan; Zhuang Cai; Li Li; Ying Dai; Jinlong Zou (Chemical Engineering Journal, 2026)

Starch coating on low-sodium salt via fluidized bed granulation: Sensory improvement and health benefits - Xinyu Song; Xing Li; Xiangyu Liu; Zhaoxiang Ma; Zhi Fan; Zhiqiang Cui; Hui Xiong; Zhixin Li; Ying Zhou; Mingchun Lv; Yuan Li (Carbohydrate Polymers, 2026)

RNA-binding protein TARDBP enhances NPTX1 stability to induce neuronal injury and diabetic cognitive impairment - GuiTing Liu; XiaoXuan Qi; SiOu Li; XinPing Wang; TingYuan Han; LingJia Cui; HuiYing Yue; Feng Liu; Ying Lin (Molecular & Cellular Toxicology, 2026)

Linking cadmium source uncertainty to crop accumulation and health risk in mining-impacted agricultural soils using Cd isotopes and receptor modelling - Kai Hu; Yumiao Cui; Ying Liu; Yuanmin Zhang; Lu Miao; Minmin Zhang; Lishu Wang (Environmental Geochemistry and Health, 2026)

An improved Hoerl-Kennard-based ridge estimation method for SBAS-InSAR deformation model resolution - Zhiwei Wang; Xiang Wang; Wenzhuang Ding; Fangfang Li; Ying Cui; Tengfei Gao; Wanqiu Li; Min Zhai (International Journal of Remote Sensing, 2026)

Decalin derivatives from an endophytic fungus Trichoderma harzianum GLQ03 and their anti-inflammatory activities - Pei-Shan Li; Qi-Yu Chen; Jian-Ying He; Xin-Huan Qiu; Feng Wang; Qi Luo; Hong-Hua Cui (Natural Product Research, 2026)

Plant-derived CTLA-4-targeting miR152 via lipid nanoparticles potentiates doxorubicin efficacy in breast cancer immunochemotherapy - Hanyi Ye; Wei Jin; Yifan Feng; Ze Wu; Shuhui Sun; Mengyao Cui; Shun Lv; Bing Jin; Chang Liu; Siming Wang; Ying Li; Zhengqi Dong (Science China Life Sciences, 2026)

A comprehensive PTM atlas of Dermatophagoides farinae reveals an acylation-dominated landscape of allergens - Dan Zeng; Xinhui Gong; Ying Zhou; Lingli Han; Panpan Han; Cunyin Yuan; Dongmei Zhou; Ximeng Ma; Yubao Cui (Science China Life Sciences, 2026)

Compatibility of three adjuvants with Cordyceps fumosorosea and their synergistic effects on controlling the diamondback moth, Plutella xylostella - Mei-Qiong Xie; Long-Jiang Wang; Yong-Qiang Han; Jin-Cui Chen; Li-Ying Cao; Shi-Chuan Luo; Fan-Fan Jiao; Shu-Jun Wei (Crop Protection, 2026)

Spatially explicit supply-demand matching of cultural ecosystem services in the coastal city: A case study of Qingdao city - Fuyu Hu; Yueyue Zhang; Qiang Ren; Wanyu Liu; Ying Cui (Ocean & Coastal Management, 2026)

Scale effects on motion responses and flow characteristics in moonpool of a semi-submersible platform based on CFD - Ying Li; Tenghui Cui; Dongxu Xie; Hui Yang; Huailiang Li (Ocean Engineering, 2026)

Deconstructing thermal processing of cooperage oak: How oak species, toasting levels and charring levels collectively modulate phenolic profiles - Yongce Huang; Jiamin Gou; Dongsheng Cui; Min Luo; Mengyao Qi; Jin Li; Jisheng Fang; Kunqi Gao; Keji Yu; Changqing Duan; Ying Shi; Yibin Lan (Food Research International, 2026)

Co-exposure to polystyrene microplastics and Di-(2-ethylhexyl) phthalate exacerbates food allergy in mice associated with gut barrier dysfunction - Xuanpei Wang; Wenfeng Liang; Shiyun Chen; Ying Liu; Jiaxin Yu; Jianing Cui; Lin Xu; Min Fang; Zhiyong Gong; Xin Liu; Qing Yang (Food Bioscience, 2026)

Long-term reduced soil salinity stress and enhanced yield sustainability from integrated nitrogen management - Shuaibing Wu; Xiaowen Gu; Yi Ding; Yongyao Zhang; Qi Miao; Jishi Zhang; Huifang Zheng; Botao Yu; Hao Ying; Zhenling Cui (European Journal of Agronomy, 2026)

Theoretical and experimental study on large pipeline deformation monitoring using the inverse finite element method based on the rotation angle - Gang Wang; Liang Ren; Jiajian Wang; Ying Wang; Jian Meng; Shaodong Cui (Engineering Structures, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Enhanced tolerance of triploid Betula pendula ‘Purple Rain’ to short-term chilling stress is associated with antioxidant capacity and BpSOD gene expression - Jie Zhang; Jingnan Li; Shicheng Li; Ling Lin; Long Liu; Xiaoyue Zhang; Ying Cui; Yujun Zhou; Jing Jiang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Deep Learning Framework for Early Warning of Shear Failure in Jointed Rock Masses - Zhigang Yao; Yong Fang; Luo Hu; Jianfeng Wang; Kaicheng Ying; Yapeng Fu; Jian Cui (Rock Mechanics and Rock Engineering, 2026)

A new fatty acid derivative derived from the deep-sea fungus Aspergillus sp. SCSIO41324 - Yu-Shi Chen; Ying-Ying Song; Sheng-Yi Deng; Xin-Kai Xiao; Xiao-Yan Pang; Wei-Jia Zhang; Yong-Hong Liu; Hong-Hua Cui; Jun-Feng Wang (Natural Product Research, 2026)

New alkaloids from the marine-derived fungus Penicillium sp. SWMU-WZ04-5 and their cytotoxic activity - Sijing Liu; Jinghao Cui; Mengyu Zhang; Ting Chen; Fengjian Lan; Xiujuan Fu; Siwei Chen; Dan Zhang; Ying Zhang; Hui Lei (Phytochemistry Letters, 2026)

Experimental investigation of pile anchors in sand under inclined cyclic loading for TLP supported floating offshore wind turbines - Jianbin Cui; Youhu Zhang; Shuzhao Li; Da Li; Ying Huang; Guodong Sun (Ocean Engineering, 2026)

In situ reduction and recovery of Rh(III) from low-concentration solutions using iron-electrocoagulation flocs - Guofu Dai; Chao Peng; Chen Wang; Ying Cui; Song Wen; Jie Jiang; Chenlong Duan; Peng Li (Minerals Engineering, 2026)

High-rate partial nitritation of high ammonia permeate from anaerobic membrane reactor treating food waste: Kinetics, enriched Nitrosomonas and enhanced tolerance to free ammonia and free nitrous acid - Ying Song; Wenzhao Zhao; Shen Cui; Qian Li; Yu Qin; Yuanfan Zhang; Meizhen Wang; Yu-You Li (Journal of Water Process Engineering, 2026)

The Chicxulub mega-earthquake: Stratigraphic evidence from the Cretaceous-Paleogene boundary of Colombian Pacific and northeastern Mexico - Hermann D. Bermúdez; Michelangelo Martini; Francisco J. Vega; Liliana Bolívar; Vivi Vajda; Francisco A. Vega-Sandoval; Daniela Bermúdez; Ying Cui (Journal of South American Earth Sciences, 2026)

Earliest centripetal flaking system in eastern Eurasia reveals human behavioral complexity in late Middle Pleistocene China - Yu-chao Zhao; Zhan-yang Li; Hai-wei Zhang; Xin-ya Shao; Hao-hong Cai; Ying Cui; Ya-Nan Li; Hai Cheng; Zhe Hou; Christopher J. Bae; Brian A. Stewart (Journal of Human Evolution, 2026)

Earthworms counteract drought-induced impairment of wheat performance at the jointing stage regardless of microplastic type - Ruixin Du; Hanwen Cui; Ying Liu; Rui Wu; Yi Zhang; Chuanxiong Huang; Conghui Liu; Jianglan Shi; Xiaohong Tian; Rui Yin (Journal of Hazardous Materials, 2026)

Confinement-enhanced Mg(OH)2-loaded resin for efficient removal of phosphorus in wastewater - Zhenning Lou; Yuxin Ma; Mengnan Huang; Haibiao Yu; Xiaogeng Feng; Junshuo Cui; Ying Xiong (Journal of Environmental Chemical Engineering, 2026)

Artificial intelligence-driven pre-estimation of printability and textural properties of starch-based gels in 3D food printing - Shihao Cui; Ying Cui; Andreas Blennow; Yuyue Zhong; Xingxun Liu (Food Hydrocolloids, 2026)

Dual-topology helical architectures enable exceptional reusable energy absorption and large recoverable strain in shape memory alloy metamaterials - Meng Zhou; Haohang Li; Ying Yang; Xiang Li; Helong Liu; Jie Chen; Shuke Huang; Yonglin Tan; Lishan Cui; Shijie Hao (Engineering Structures, 2026)

Millennial-scale changes in marine lithofacies during the Paleocene-Eocene Thermal Maximum: A deep-time analog for Anthropocene hydrologic and acidification impacts - Jingxin Jiang; Xiumian Hu; Eduardo Garzanti; Ying Cui; Thomas J. Algeo (Earth-Science Reviews, 2026)

Non-planar conjugated thiophene engineering in hydrazone-linked covalent organic polymers for highly efficient photosynthesis of H2O2 from air and water - Yan Chen; Wenzhe Fang; Ying Zhou; Zekai Zhang; Qiulian Zhu; Quanli Ke; Ziqi Tian; Guokai Cui; Hanfeng Lu (Chemical Engineering Journal, 2026)

Chemical structure and P-selectin inhibition of two linear and highly regular homofucans from the brown alga Fucus vesiculosus - Linxia Chen; Dilihumaer Ruzemaimaiti; Lige Cui; Guangyu Zhu; Jiali Zhang; Huifang Sun; Yan Ma; Ying Hong; Na Gao; Lina Nong; Wenxin Ma; Qinjie Qin; et al. (Carbohydrate Polymers, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Hydrogenophaga pseudoflava widely distributed in wastewater treatment plants exhibiting heterotrophic nitrification-aerobic denitrification: From characterization to genomics - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Jia-Ying Li; Ya-Nan Mi; Xin-Yu Gu (Bioresource Technology, 2026)

Designing the Next Generation of Endolysins: A Triple Strategy Integrating Bioinformatics Mining, Engineering Modification and Encapsulation Formulation - Yongkang Zhang; Xinge Cui; Luwei Chai; Yangwei Pan; Ying Yang; Hongbing Liu; Xingying Mou; Tao Le (Probiotics and Antimicrobial Proteins, 2026)

Integrating elite selection and micropropagation: a production line for early-stage domestication of Vaccinium bracteatum - Chuizheng Xia; Muhammad Junaid Rao; Ying Wu; Yuanyuan Li; Xuefeng Wang; Weicong Hong; Mengxue Wang; Yihong Jin; Jiani Zhu; Xuan Yu; Haidi Yuan; Jiao Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Regulatory patterns of antibody-dependent cellular phagocytosis–related genes in triple-negative breast cancer: An integrated multi-omics and single-cell analysis - Guihua Hong; Zhanyue Cui; Xiaowen Xu; Shiwei Lin; Changqing Yang; Ran Ding; Ludan Liang; Ying Chen; Ziyue Tian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

From protein-like to humic-like substances: Feed-derived regulation of dissolved organic matter transformation in RAS - Ying Bai; Ruijie Ma; Zhengguo Cui; Hao Li; Hongwu Cui; Yong Xu; Jianlei Chen; Keming Qu (Aquacultural Engineering, 2026)

The Roles of SOCS in Teleost Immunity: Cytokine Regulation and Host Defense - Ying Zhang; Li Yang; Xiuying Cui; Feng Gao; Yanjing Zhao; Xianghui Kong (Reviews in Aquaculture, 2026)
The Suppressor of Cytokine Signaling (SOCS) family comprises key regulatory molecules which are essential for maintaining immune homeostasis in vertebrates. Owing to a teleost‐specific whole‐genome duplication event, SOCS family members exhibit higher diversity and significant functional differentiation, forming a complex and precise immune regulatory network. This review comprehensively summarizes the current understanding of SOCS‐mediated cytokine regulation and host defense mechanisms in teleosts. SOCS proteins, particularly SOCS1 and SOCS3, exert dual regulatory effects in antiviral and antibacterial immunity as well as in inflammatory balance by negatively modulating key pathways such as JAK/STAT and NF‐κB, exemplifying their “double‐edged sword” role. Moreover, we provide the first comprehensive synthesis of environmental regulation of SOCS expression in teleosts, integrating emerging evidence on how to modulate SOCS levels after temperature stress, neuroendocrine activation via cortisol, hypoxia, and chemical pollutants and how to link environmental conditions to immune competence. This environmental perspective supplies direct implications for understanding stress‐induced immunosuppression in aquaculture. Finally, we discuss the potential application of targeting SOCS signaling in aquaculture practices, including applications in disease‐resistant breeding, vaccine development, and immunostimulant design. In‐depth understanding of SOCS diversity and function in fish will provide novel molecular insights and innovative strategies for precise disease control and sustainable aquaculture.

miR-141-5p positively regulates ACVRL1 expression to promote cervical cancer progression - Jianbing Liu; Yongzhi Jiao; Jinjuan Wang; Xiaohua Cui; Ying Gao; Yan Zhang; Jing Xu; Jianqing Hao; Yongli Hou; Wei Wang; Guang Yang; Li Li (Human Cell, 2026)

Two new abietane-type diterpenoids from the roots of Tripterygium wilfordii Hook.f. and their diacylglycerol acyltransferase activity - Hao Xu; Xue-Feng Wu; Ying-Xiao Xiao; Yuan Gao; Yi-Lin Li; Hyun-Sun Lee; Long Cui (Natural Product Research, 2026)

Oxygen supply models shape spatiotemporal distribution of total and active bacterial communities in seawater constructed wetlands - Wenli Liu; Qiufen Li; Ying Ma; Bo Sun; Xianzhe Gong; Zhengguo Cui (Journal of Water Process Engineering, 2026)

Ecological lock-in and functional mismatch in abandoned coastal ponds: mechanisms and management implications - Yi'na Li; Yanzi Cai; Junjun Bai; Ying Man; Dongxue Li; Qing Wang; Yujia Zhai; Ping Qi; Tian Xie; Baoshan Cui (Journal of Environmental Management, 2026)

Evidence of microplastics in human lung tissue: Relationship with clinical indicators - Yang Xiang; Cui-Lan Bai; Li Ma; Liang-Ying Liu; Zi-Feng Zhang; Ying Guo (Journal of Environmental Sciences, 2026)

Natural deep eutectic solvents (NADESs) as cryoprotectant for Lactiplantibacillus plantarum YR07: antifreeze mechanisms and applications - Sha sha Zheng; Li jun Tan; Qiong Pan; Yu fei Zhang; Wen di Zhang; Li fang Zou; Wei Cui; Yu Zhou; Ying ying Hu; Bao cai Xu (Food Research International, 2026)

Enhanced Therapeutic Effects of Extracellular Vesicles Targeting MiR-137 Contribute to Functional Recovery by Attenuating Neuronal Injury After Ischemic Stroke - Hui-Xin Zhang; Li-Qing Tao; Yi-Hang Chen; Tian-Yi Jiang; Zhi-Yuan Ye; Wen She; Chang-Ying Chen; Ya-Li Han; Cui Qi; Chong Shen; Jun Gao (Neuroscience Bulletin, 2026)

PfAgo-mediated a rapid and visual detection assay for porcine circovirus type 3 based on recombinase-aided amplification - Xi-Meng Chen; Jia-Qi Zhang; Hong-Bo Cui; Lan-Lan Zheng; Xue-Yan Ding; Hong-Ying Chen; Shi-Jie Ma (Analytica Chimica Acta, 2026)

Study of enhancing analgesic potential of μ-conotoxins from the computational and pharmacological insights - Fan Zhao; Yunxia Liu; Ying Cui; Yushan Ding; Liu Ru; Ting Meng; Hongtao Yang; Yongbo Song (Molecular Diversity, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A new dameselloid trilobite from the Changhia Formation (Cambrian, Drumian) in central Shandong, North China - Guang-Ying Ren; Jin-Liang Yuan; Yi-Fan Wang; Bai-Zheng An; Kai Chen; Xiao-Hui Cui; Jian Gao; Nan Li (Palaeoworld, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Seasonal shifts in phytoplankton community assembly mediated by hydrological connectivity in a sluice-regulated distributary estuarine network—as a case in the Pearl River Estuary - Yanzi Cai; Xia Li; Guogui Chen; Yiliang Xie; Yujia Zhai; Tian Xie; Mingyu Wang; Fang Gao; Meili Feng; Ying Man; Baoshan Cui (Journal of Hydrology, 2026)

Partitioned N-TiO2–N-TiO2@SWCNT/PET composite fabric for industrial wastewater habitat reconstruction and potential cross-niche carbon sequestration - Jian Qiu; Yang Hu; Ying Chen; Shilong Li; Yudong Yuan; Bin Chen; Ping Shi; Jianfa Zhao; Wenheng Jing; Wei Zhou; Yuan Bai; Lele Cui; et al. (Journal of Environmental Chemical Engineering, 2026)

Unveiling the mechanism: DOM from chemically pretreated corncobs drives denitrification via mediating microbial community succession - Ying Bai; Ruijie Ma; Zhengguo Cui; Hongwu Cui; Weiman Gong; Wei Dong; Hao Li; Yong Xu; Jianlei Chen; Keming Qu (Journal of Environmental Chemical Engineering, 2026)

Integrating transparency and circular economy principles into data-driven agrifood supply chains for environmental management - Jianqi Qiao; Andrea Appolloni; Mengchao Wu; Ying Cai; Ziqing Cui (Journal of Environmental Management, 2026)

Characterization of condensed tannin oxidative transformation pathways during red wine ageing: Insights from pseudo-targeted metabolomics - Yongce Huang; Dongsheng Cui; Yiming Zhang; Keji Yu; Ying Shi; Changqing Duan; Mengyao Qi; Yibin Lan (Food Chemistry, 2026)

Comprehensive assessment of hydrolyzed pig hoof keratin (HPHK) as a potential food ingredient: Stability, techno-functional properties, in vitro, and in silico bioactivities - Ruican Wang; Ying Zhang; Haoxin Cui; Wenhui Fu; Dongfei Tan; Qisijing Liu; Xuemeng Ji; Liye Zhu; Shuo Wang (Food Chemistry, 2026)

Synergistic optimization of yield, quality, and nitrogen use efficiency in indica rice: Influence of nitrogen management and C-N metabolism linkages - Hongjin Li; Tao Li; Jianghui Yu; Tianyu Du; Ping Zhang; Jingjing Cui; Zheshu Xu; Ying Zhu; Fangfu Xu; Qun Hu; Guodong Liu; Guangyan Li; et al. (Field Crops Research, 2026)

Refrigerant Substitution Pathways of VRF Air-Conditioning System Oriented to Kigali Amendment in China - Yuzheng Ying; Mengdi Cui; Yujue Zhou; Wenxing Shi; Baolong Wang (Energy and Buildings, 2026)

The changes in the relative biomass growth rate of plants reveal the different interaction modes under high-stress - Kangkang Mi; Wenping Cui; Ying Zhao; Tingting Ji; Yuyang Song (Ecological Modelling, 2026)

Tracing fluid evolution forming multistage wolframite mineralization in vein-type tungsten (-tin) deposit: new insight from LA-ICP-MS analysis of fluid inclusion - Zhi-Lin Cheng; Jun-Yi Pan; Pei Ni; Li-Li Chen; Jian-Ming Cui; Zhe Chi; Jun-Ying Ding (Mineralium Deposita, 2026)

Spatial Network Structure Characteristics and Resilience Evaluation of Urban Ice and Snow Activities in Cold Border Regions: A Case Study of Harbin City, China - Wenhao Du; Weilin Li; Xiaohong Chen; Ying Wang; Jinming Mou; Yi Cui; Han Wu; Xinyu Wang; Donghong Xie; Yujie Zhang (Chinese Geographical Science, 2026)

Numerical Investigation of Micro-Scale Mass Transfer in Stretched and Compressed Kelvin-Cell Packings for Shipboard Carbon Capture - Bohao Wu; Nan Wu; Yongqi Li; Ying Bi; Daan Cui; Haoheng Liu; Chao Chang; Yulong Ji (Journal of Marine Science and Engineering, 2026)
For shipboard CCUS facilities, the integration of chemical absorption columns is constrained by a limited vertical envelope, which motivates packings with axially stretched or compressed Kelvin cells to support compact layout and flow control. This study employs computational fluid dynamics to investigate microscale flow and mass transfer characteristics in Kelvin cells. A comparison among the regular Kelvin cell (RKC), the vertically elongated Kelvin cell (VEKC), and the vertically compressed Kelvin cell (VCKC) indicates that axial stretching and compression modify internal flow distributions and gas–liquid mass transfer during CO2 absorption. The liquid distribution transitions from a film along the struts with localized accumulation at the nodes in RKC to a continuous columnar stream in VEKC, and then to a stable hollow cylindrical liquid film promoted by lateral redistribution in VCKC. VCKC promotes a stable and expanded liquid film, whereas VEKC tends to induce columnar flow. Reducing the cell size and porosity improves mass transfer efficiency, and the liquid load governs mass transfer flux. These findings provide theoretical guidance for the design and optimization of compact packings for process intensification in shipboard carbon-capture applications.

3D porous cellulose/polyaniline aerogel composite as a high-performance electrode for selective electrosorption of rhenium - Ruichen Ma; Boxiao Zhao; Xiling Sun; Zhenning Lou; Junshuo Cui; Haibiao Yu; Yuejiao Wang; Weijun Shan; Xiaogeng Feng; Ying Xiong (Water Research, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Comprehensive evaluation on potentiality and key bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Ming-Teng Li; Yuan Sui (Process Safety and Environmental Protection, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Dough surface viscosity during resting process: Effects of water migration and gluten network dynamics - Wei He; Wan Wang; Xin Ying; Meili Huan; Chengang Ren; Lianhui Zhang; Qingbin Guo; Steve W. Cui; Ji Kang (Food Hydrocolloids, 2026)

In Situ small-angle X-ray scattering study of the gelatinization mechanism of maize starches with varying amylose content - Ying Cui; Xiaoning Liu; Qi Lv; Jinhui Chang; Andreas Blennow; Yu Tian; Sheng Chen; Xingxun Liu; Yuyue Zhong (Food Hydrocolloids, 2026)

Tobacco–rapeseed system with moderate mineral fertiliser promotes yield by synergistically improving bacterial network complexity and soil fertility - Qi Miao; Lu Liu; Chen Wang; Hao Ying; Yingxin Guo; Dexun Wang; Yanxia Hu; Zhenling Cui; Junwei Sun; Junying Li; Jing Tian (European Journal of Agronomy, 2026)

Corrigendum to “Construction of ultrathin PANI nanostructure on cation-exchange membranes for selective lithium extraction” [Desalination, 619 (2026) 119555] - Jiadi Ying; Zhen Cui; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Minfeng Zeng; Zhixin Yu; Yuqing Lin (Desalination, 2026)

Erratum to “Long-term stability of a tunnel excavated in expansive stratum: response to water infiltration and influence of surrounding ground stiffness” [Comput. Geotech. 188 (2025) 107580] - Sujian Ma; Ying Cui (Computers and Geotechnics, 2026)

Interfacial engineering of polyolefin separators via caffeic acid-titanium coating for high-efficiency lithium dendrite suppression - Zi-Yin Chen; Zhen Luo; Cui-Ran Gong; Yang-Qing Zheng; Ying Xu (Chemical Engineering Journal, 2026)

Electrocatalytic degradation of benzohydroxamic acid in the mining beneficiation wastewater via ferrocene-organic framework cathode coupled with oxygen-contact system: Enhanced cycled bimetallic heterogeneous electro-Fenton process - Jiangpeng Fu; Xiaoyu Han; Ying Li; Jiayang Ma; Haoyang Cui; Xin Zhao; Wenzheng Yu (Chemical Engineering Journal, 2026)

Characterization and biological activities of a high-yield galactosylated heparan sulfate from Bursatella leachii egg strings - Yan Ma; Ying Pan; Lutan Zhou; Lige Cui; Xuewen Wu; Mengchen Ji; Dilihumaer Ruzemaimaiti; Wenwen Ma; Haitian Wang; Linxia Chen; Weilie Xiao; Ronghua Yin; et al. (Carbohydrate Polymers, 2026)

Increased precipitation promotes aboveground biomass primarily by extending the growing season rather than by affecting leaf traits in alpine desert grasslands - Pengfei Ma; Haoze Zhang; Haijuan Wei; Guangshuai Cui; Liu Yang; Haixia Wei; Ying Guo; Xinru Zhang; Francisco I. Pugnaire; Lin Zhang (Plant and Soil, 2026)

Enzyme immobilization on nanomaterials in food industry: current status and future perspectives - Lang Du; Yingzhuo Liang; Sifan Cui; Jianyang Wei; Jianqiao Liu; Shuling Zhang; Yuqing Zhang; Liya Zhou; Ying He; Li Ma; Jing Gao; Yanjun Jiang (Critical Reviews in Food Science and Nutrition, 2026)

Localization of heterosis loci for quality traits and identification of candidate genes in Brassica napus - Guoqiang Zheng; Ying Wang; Jiaping Wei; Zefeng Wu; Jinxiong Wang; Qi Yang; Junmei Cui; Yan Fang; Xiaoyun Dong; Xinyi Zhang; Qian Luo; Jiayue Yang; et al. (Journal of Plant Physiology, 2026)

MsTIFY10a gene from alfalfa negatively regulates drought and salt tolerance in transgenic tobacco - Qi Chen; Yan Zhang; Ying Tian; Jing Xu; Qing-Wen Fu; Zhen-Yi Li; Feng-Ling Shi; Cui-Ping Gao; Zhi-Qiang Zhang (Journal of Plant Physiology, 2026)

The effect of pet dog exposure on gut antibiotic resistome and microbiome of their owners - Wenjing Cui; Yange Cui; Yuqing Hao; Yuan Li; Ying Wang; Fang Liu; Jinzhao Long; Yuefei Jin; Shuaiyin Chen; Guangcai Duan; Haiyan Yang (Journal of Hazardous Materials, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

The protective effects of dipeptides-WY and YW on blueberry anthocyanins and their interaction mechanism analysis - Yuxi Lang; Xu Si; Hui Tan; Jinlong Tian; Zhihuan Zang; Huijun Cui; Dongdong Zhao; Ying He; Liang Wang; Bin Li (Food Bioscience, 2026)

Fatigue behavior and remaining life evaluation of cracked rib-to-deck joints reinforced with inverted U-shaped plates - Ming-zhe Li; Chuang Cui; Qing-hua Zhang; Le-tian Da; Zhen-yu Cheng; Chuan Wei; Feng-kun Cui; Ying-fang Yang (Engineering Structures, 2026)

Construction of ultrathin PANI nanostructure on cation-exchange membranes for selective lithium extraction - Jiadi Ying; Zhen Cui; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Minfeng Zeng; Zhixin Yu; Yuqing Lin (Desalination, 2026)

Iron and platinum alternating active sites for efficient photocatalytic overall water splitting - Yanfei Fan; Yan Liu; Ying Liang; Kang Chen; Qingqing Li; Dongxu Pan; Shiqiu Zhang; Guanwei Cui; Bo Tang (Chemical Engineering Journal, 2026)

SlNCED1 Affects Pollen Maturation by Regulating the Expression of Tapetum Transcription Factor Genes in Tomato - Zhikai Song; Jinxiang Hu; Meng Xu; Ying Huang; Dedi Zhang; Zhenning Liu; Xiaoyu Cui; Shengjie Dai (Journal of Plant Growth Regulation, 2026)

Rapid excretion of raw microplastics and longer persistence of fragmented microplastics in the quail digestive system - Ziye Zhang; Ying Yang; Wenzhuo Shi; Wei Pan; Xiaoli Zhao; Song Cui; Lihui An (Environmental Chemistry Letters, 2026)

Aridity Threshold Triggers Abrupt Increase in Shrub Biomass Through Changes in Leaf Functional Traits - Guangshuai Cui; Lin Zhang; Liu Yang; Ying Guo; Jian Sun; Tianxiang Luo; Francisco I. Pugnaire; Eryuan Liang (Ecosystems, 2026)

Correction: CircMMP11 is a Potential Recurrence Biomarker and Facilitates Progression of Esophageal Squamous Cell Carcinoma - Jingnan Yuan; Ying Cui; JiWen Zhang; Yan Cai; Xun Xu (Biochemical Genetics, 2026)

CircMMP11 is a Potential Recurrence Biomarker and Facilitates Progression of Esophageal Squamous Cell Carcinoma - Jingnan Yuan; Ying Cui; JiWen Zhang; Yan Cai; Xun Xu (Biochemical Genetics, 2026)

Towards damage-less robotic fragile fruit grasping: Learning adaptive grasping force from multimodal data and human demonstration - Qingyu Wang; Jianwei Zhang; Alois Knoll; Di Cui; Huanyu Jiang; Mingchuan Zhou; Yibin Ying (Computers and Electronics in Agriculture, 2026)

PM2.5-bound bioaerosols during landfill leachate treatment: A profile of human pathogens, virulence factors, and antibiotic resistance genes - Ya-nan Wang; Wenyu Yang; Wenyu Wang; Yifan Zheng; Huawei Wang; Yingjie Sun; Bingpeng Wang; Xiongbo Cui; Ying Gao; Fenghua Zhang (Waste Management, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

Long-term intercropping mitigates warming-induced carbon loss via enhancing microbial and substrate resistance - Wei Wang; Yang Wang; Jian-Ming Li; Meng-Ying Li; Peng He; Yongxing Cui; Sheng-Jun Ji; Wen-Ying Wang; Levis Kavagi; Muhammd Ashraf; Yinglong Chen; Matthias C. Rillig; et al. (Soil Biology and Biochemistry, 2026)

Research progress on spike development of wheat - Yi Ding; Ying Zhang; Tengteng Zhang; Dan Zhao; Yufeng Yang; Kaiyue Wang; Ziqi Zheng; Chaoran Wang; Yongpeng Li; Runya Mao; Yifan Ye; Mengxue Li; et al. (Plant Science, 2026)

An experimental investigation on the performance of shared pile anchor in saturated sand for floating offshore wind turbines - Jianbin Cui; Youhu Zhang; Chuheng Wu; Ying Huang (Ocean Engineering, 2026)

Molecular insights into the temperature-responsive interfacial properties of sodium oleate–based combined collectors for spodumene flotation - Ying Zhang; Yuhua Wang; Ning Sun; Man Cui (Minerals Engineering, 2026)

Unveiling the nature of glassy impact spherules by analyzing pristine Chicxulub spherules from Gorgonilla Island - Hermann D. Bermúdez; Vivi Vajda; Kajsa G.V. Sigfridsson Clauss; Courtney Jean Rundhaug; Gavin Kenny; Liliana Bolívar; Daniela Bermúdez; Ying Cui (Journal of South American Earth Sciences, 2026)

Dose-dependent mutagenic effects of carbon-ion beams in foxtail millet: from phenotypic screening to physiological and molecular mechanisms - Ruiyuan Liu; Yan Zhan; Aiming Cui; Ying Qu; Wenjie Jin; Yan Du; Lixia Yu; Libin Zhou (Journal of Plant Physiology, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Occurrences of antibiotics and antimicrobial resistance in combined and separate sewage overflow effluents of Shanghai, China - Wujie Chen; Bingjie Cui; Zhuyu Sun; Ying Zhang; Pan Wang (Journal of Environmental Management, 2026)

Low-cost supported ionic liquid [TETA][HCOO]/X-5: Adsorption and regeneration performance for CO2 capture from flue gas - Chengyu Han; Chuanjia Qi; Ying Ming; Jiyun Tang; Yong Dong; Lin Cui (Fuel, 2026)

A quantitative detection method for maize kernel broken rate based on the optimisation of the MSA transformer algorithm - Yongkun Qiao; Mengmeng Qiao; Chenlong Fan; Tao Cui; Ying Liu; Caiyuan Zhang; Mingyou Sun; Yuhao Wu (Food Research International, 2026)

Study on the origin identification of Anji Baicha based on mineral elements - Yuanyuan Zhu; Yaning Lu; Chuanjian Cui; Ge Jin; Ying Xu; Xiaochun Wan; Ruyan Hou (Food Chemistry, 2026)

A systematic pipeline coupling UHPLC-MS/MS with diagnostic ions screening to reveal the impact of oak barrel toasting on hydrolysable tannin profiles in wine - Yongce Huang; Mengyao Qi; Mengqi Ling; Dongsheng Cui; Yiming Zhang; Chen Huang; Ying Shi; Keji Yu; Jiming Li; Shili Ruan; Changqing Duan; Yibin Lan (Food Chemistry, 2026)

Explaining the coexistence of complete ammonium-oxidizing bacteria and canonical nitrite-oxidizing bacteria under mainstream wastewater conditions from a substrate affinity perspective - Runan Yang; Shukang Cui; Jiaying Hou; Ying Zhu; Yuanji Shi; Meiying Xu; Linyan Yang; Xueming Chen (Environmental Research, 2026)

Water-tolerant carbanion engineering for efficient, selective, and reversible SO2 capture by multi-functional ionic liquids embedded hyper-crosslinked polymers - Guokai Cui; Yinfeng Chen; Ruina Zhang; Xing Li; Limin Xu; Xiongfei Nie; Ying Zhou; Quanli Ke; Xiaopo Niu; Zekai Zhang; Huayan Liu; Xiangping Zhang; et al. (Chemical Engineering Journal, 2026)

Prioritizing root endophytes: maize genotype and nitrogen interaction shape microbial contributions to nitrogen use efficiency - Desheng Hu; Shujie Zhang; Ming Chen; Pengjuan Cui; Ying Jiang; Yanlai Han; Yi Wang (Plant and Soil, 2026)

Research on individual differences in risk preferences for personnel evacuation during flood disasters in underground spaces - Yixuan Wei; Mengcan Wang; Minrui Ni; Ying Cui; Tianmei Sun; Chunqing Wang; Song Pan (Natural Hazards, 2026)

The Role of Toll-like Receptor 3 Signaling in Cognitive Impairment Induced by Propofol Addiction - Jiahui Wu; Liyun Deng; Rui Gao; Ying Cui; Yidan Tang; Changliang Liu; Tao Zhu; Chan Chen (Molecular Neurobiology, 2026)

Spatial planning based on the modeling the food-energy-water‑carbon nexus: A case study of the Yangtze River basin - Beibei Guo; Xian Zou; Yingxue Cui; Suchen Ying; Yinkang Zhou (Agricultural Systems, 2026)

Systematic Review and Meta-Analysis on Heavy Metals and Trace Elements in Mild Cognitive Impairment - Yaxin Dong; Lu Ren; TianRan Tang; Xinyi Zhang; Dan Han; Yingyi Luo; Liqiang Wang; Zonghui Cui; Sheng Ji; Jianheng Zheng; Ying Qing (Biological Trace Element Research, 2025)

Thiophene-silane coupling agent for enhancing the dispersibility of graphene and its adsorption capacity for Mo(VI) - Junshuo Cui; Shuang Liu; Liangyu Guo; Zhongjun Li; Zuozhen Zhang; Ying Xiong (Journal of Environmental Chemical Engineering, 2025)

Bio-inspired nanocarriers for oral delivery: Applications in intestinal health - Jia Guo; Zijun Wang; Li Huan; Haiying Yang; Shikai Zhang; Ying Xie; Saiqing Xu; Qiutan Cui; Yang Shan; Shenghua Ding (Food Research International, 2025)

Quercetin alleviates ethanol-induced hepatocyte senescence by interacting with glycinamide ribonucleotide transformylase - Chen Huimin; Peng Shufen; Cui Zhaoyu; Liu Jiaxin; Chen Li; Yin Xingzhu; Wu Bangfu; Zhao Ying; Wang Yu; Mo Li; Liang Chanhua; Li Dongyan; et al. (Food Research International, 2025)

Flexcube as an alternative aging vessel to the oak barrel: insights into flavor, oxygen, and matrix interactions - Dongsheng Cui; Yongce Huang; Mengqi Ling; Haibin Mu; Weiming Yang; Ying Shi; Changqing Duan; Mengyao Qi; Yibin Lan (Food Research International, 2025)

Food defect detection technologies based on deep learning and prospects in detection of unsound wheat kernels - Rong Wang; Zhiyao Zhao; Ying Sun; Yongbiao Ni; Jin Ye; Min Zhang; Liwen Cui (Food Chemistry, 2025)

Functional characterization of two Caspase-1 transcripts that associated with ASC and NLRC3 in apoptosis and inflammatory response in large yellow croaker Larimichthys crocea - Qiu Yu Hu; Kun Huang Han; Qiu Ye Huang; Wen Feng Cui; Qiao Yun Yang; Yi Dan Liu; Shang Qi Zhao; Xian Yuan Zeng; Ying Li; Wen Qi Zha; Yi Lei Wang; Yong Hua Jiang; et al. (Fish & Shellfish Immunology, 2025)

Soil extracellular enzyme stoichiometry reveals the nutrient limitations of soil microbial metabolism under precipitation changes in Ningxia desert steppe of China - Jiali Lian; Jing Chen; Cui Han; Ying Zhao; Xueqin Yang; Jianping Li (European Journal of Soil Biology, 2025)

Experimental investigation on a two-stage vapor compression industrial heat pump incorporating liquid separation condensation - Falin Wei; Yuzheng Ying; Mengdi Cui; Baolong Wang (Energy and Buildings, 2025)

Long-term stability of a tunnel excavated in expansive stratum: response to water infiltration and influence of surrounding ground stiffness - Sujian Ma; Ying Cui (Computers and Geotechnics, 2025)

Cone impact penetration in sand: from high-rate granular mechanics to rapid inversion of shear-strength parameters - Liping Ying; Yuqiong Li; Na Li; Zhiyuan Lv; Qinghao Liu; Gaozhan Cui (Computers and Geotechnics, 2025)

Elastic conductive polyurethane/PEDOT:PSS composite with self-healing and closed-loop recyclability - Wei-Chen Gao; Ben Fan; Junmei Hu; Yu-Dong Zhao; Xiang Sun; Defeng Cui; Jing Qiao; Wei-Bing Lu; Ying-Shi Guan (Chemical Engineering Journal, 2025)

Interface-enhanced CO2-to-C2+ electroreduction via magnesium-regulated PVP nanospheres confining Cuδ+ active sites - Haozhong Yuan; Yuan Zhuang; Senyao Meng; Renlong Ma; Kaixuan Wei; Guiwu Lu; Huiting Hu; Xing Zhou; Ying Cui; Tieyin Zhang; Zhixiang Zeng; Tianteng Yu; et al. (Chemical Engineering Journal, 2025)

Capture and release methods of extracellular vesicles based on functional magnetic beads - Zeying Liu; Ziwei Lu; Ying Li; Yichun Fan; Wenwen He; Yali Cui (Chemical Engineering Journal, 2025)

Phosphate functionalized polypyrrole electrode for high-efficiency indium electrosorption: Boosting capacity and fabricating In(PO3)3 - Zhenning Lou; Wei Zhang; Yuxin Ma; Junshuo Cui; Haibiao Yu; Xiaogeng Feng; Ying Xiong; Weijun Shan (Chemical Engineering Journal, 2025)

Controllable interfacial engineering for smart one-component epoxy adhesive with multi-trigger on-demand bonding functionality - Zhaoxin Li; Ying Zhao; Tianyang Cui; Yuan Hu; Jinglei Yang (Chemical Engineering Journal, 2025)

Full-enzymatic three-in-one cascade finishing for woolen textiles: anti-felting, low-temperature dyeing and antibacterial processing - Jiaqi Zhang; Leilei Wu; Jun Wang; Li Cui; Ying Liu; Yuanyuan Yu; Qiang Wang; Ping Wang (Bioresource Technology, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

Dynamics of convergent plate margins: Progress and challenge - Zhong-Hai Li; Yang Wang; Qihua Cui; Hui-Ying Fu; Fengyuan Cui; Pengpeng Huangfu (Science China Earth Sciences, 2025)

Multiomics integration unveils rapeseed adaptative responses to potassium deprivation: a synergy of morpho-physiological, transcriptomic, and metabolic reprogramming - Rui Cui; Si-si Sun; Min-nan Pei; Ying Liu; Yu-shan Xiao; Ying-na Feng; Ting Zhou; Ying-peng Hua (Plant and Soil, 2025)

The lactylation of glucose-6-phosphate dehydrogenase promotes malignant phenotypes in cancer cell lines - Yan Zhang; Ying Wu; Aoxing Cheng; Fengjuan Cui; Zhenye Yang; Jing Guo (Molecular Biology Reports, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Circular RNA hsa_circ_0124644 regulates apoptosis of endothelial cells in coronary artery disease - Ying Cui; Boxin Zhao; Shimeng Wang; Lin Gui; Yingyu Xiang; Zhiyong Zhang; Xueyuan Sun; Jingyao Fan; Jun Liu; Lijuan Huang (In Vitro Cellular & Developmental Biology - Animal, 2025)

Topographic differences in EEG microstates: distinguishing juvenile myoclonic epilepsy from frontal lobe epilepsy - Ying Li; Lidao Xu; Yibo Zhao; Mingxian Meng; Yanan Chen; Bin Wang; Beijia Cui; Jin Liu; Jiuyan Han; Na Wang; Ting Zhao; Lei Sun; et al. (Cognitive Neurodynamics, 2025)

A Review of Polyhalogenated Carbazoles (PHCZs) as an Emerging Contaminant: Environmental Occurrence, Toxicity and Remediation - Bingjie Cui; Innocent Tayari Mwizerwa; Xiao Chen; Zhuyu Sun; Ying Zhang; Pan Wang (Reviews of Environmental Contamination and Toxicology, 2025)

Pore-Structure-Controlled Acoustic Characteristics for Predicting Shallow Gas Distribution in Polar Offshore Drilling - Lei Li; Li He; Ying Zhao; Yu Song; Shiming Wei; Guojing Zhu; Qingying Tang; Tiancong Cui (Journal of Marine Science and Engineering, 2025)
Shallow gas drilling in polar seas poses severe geological hazards, particularly unexpected eruptions that threaten platform safety and the marine environment. Accurate prediction of shallow gas occurrence and eruption risk is therefore essential for safe deep-water operations. However, previous studies seldom considered the coupled effects of gas pressure and pore-structure evolution on acoustic wave velocity, leading to deviations in hazard assessment. In this study, laboratory experiments and numerical simulations were conducted to clarify these mechanisms. Results revealed a non-monotonic relationship between porosity and P-wave velocity in shallow gas-bearing sediments: P-wave velocity decreases with increasing porosity at low porosity levels but increases beyond a critical threshold. This is attributed to changes in particle interactions and cementation that enhance the shear modulus. The inflection porosity for shallow gas (78%) highlights the diagnostic role of pore-structure evolution in predicting shallow gas distribution. A mathematical correlation between P-wave velocity and formation pressure was further established, and MP-PIC simulations showed that higher pressure coefficients significantly accelerate eruption rates, with a 0.1 increase in the pressure coefficient raising the instantaneous eruption velocity by 5.27 m3/min. Based on these findings, a quantitative evaluation method was developed to assess shallow gas hazard risk, providing engineering guidance for site selection and real-time risk prediction, and contributing to safer offshore drilling and ecological protection in polar environments.

Design and test of a precision air-suction maize seed-metering device for plot planting based on CFD-DEM coupling - Jiaqi Li; Zishun Huang; Youcong Jiang; Zijian Cui; Meilin Zhang; Ying Zang; Wei Qin (Computers and Electronics in Agriculture, 2025)

Unravel the impact of land use type on taxonomic and functional structure of microbial communities in coastal urban and rural areas, China - Min Yang; Wenbo Cui; Yu Tao; Ying Chen; Zhen Liu; Taotao Zeng; Ai-jie Wang (Science of The Total Environment, 2025)

Towards sustainable separation of fuel additives - containing azeotrope by energy-saving extractive distillation process - Xiang Wang; Zhifan Chen; Jingyu Yu; Zhenlin Mu; Ying Xu; Yinglong Wang; Zhaoyou Zhu; Peizhe Cui; Guoxuan Li (Process Safety and Environmental Protection, 2025)

Sesamol inhibits fungal growth by destroying the redox dynamic equilibrium in Pestalotiopsis neglecta - Jing-Yu Ji; Li-Ying Huang; Bing Bi; Ya-Jun Wang; Jin-Yan Zhao; Sheng-Yu Zhang; Ze Wang; Shu-ming Cui; Qiao-ya Zhang; Guo-Cai Zhang (Physiological and Molecular Plant Pathology, 2025)

Seismic fragility and resilience assessment of pile-supported wharves with isolation systems in liquefied soil - Yao Cui; Sami Ur Rehman; Zhuoxin Wang; Ying Cui; Abid Ali; Muhammad Shameer Faisal (Ocean Engineering, 2025)

Microbial community dynamics and protein-level adaptation to petrochemical pollution in river systems on the northern margin of the Yellow River Delta, Shandong, China - Shudi Yao; Shixuan Cui; Dong Wang; Yumiao Zhou; Ying Wang; Likun Yang; Qiang Kong; Huanxin Zhang (Journal of Hazardous Materials, 2025)

Changes in continental weathering across the Permian-Triassic transition: A global review - Joseph Mayala Nsingi; Ying Cui; Emily Cepin; Brian Beaty; Noah Planavsky; Qingting Wu; Markus Adloff; Jiuyuan Wang; David Selby; Zeyang Liu; Yixin Dong; Shijun Jiang; et al. (Global and Planetary Change, 2025)

Retraction notice to “A comparative study on rapid qualitative and quantitative determination of olive oil adulteration” [Food Chem. 465 (2025) 142126] - Lijuan Du; Ying Yu; Yuling Cui; Guangbin Cui (Food Chemistry, 2025)

Safety and recyclability of active polyethylene terephthalate bottles: A comprehensive assessment using non-target screening and visual sensory evaluation - Can Xu; Sheng Chen; Qi-zhi Su; Jinxin Liang; Ying Zeng; Anqi Cui; Hanke Li; Ben Dong; Dan Li; Huai-ning Zhong (Food Chemistry, 2025)

The synergistic effect of double catalysis of TGase-mediated limited deamidation and cross-linking of zein to form multifunctional zein-based film for food preservation - Na Li; Yutong Sheng; Sihan Liao; Jingwen Zhang; Ying Liu; Ping Wang; Li Cui (Food Chemistry, 2025)

Comammox-based simultaneous nitrification and denitrification in mainstream membrane-aerated biofilm reactor – A modeling study - Shukang Cui; Runan Yang; Ying Zhu; Jiaying Hou; Yuanji Shi; Meiying Xu; Linyan Yang; Xueming Chen (Environmental Research, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Compartment engineering in yeast: a path to increased biochemical production - Yuyang Wang; Liyan Cao; Lanxin Rong; Chen Ding; Chang Liu; Qingqing Ye; Qingeng Huang; Cui-ying Zhang; Ning Xu; Jiwei Mao; Jee Loon Foo; Aiqun Yu (Chemical Engineering Journal, 2025)

Gellan gum/chitosan-based bilayer scaffold for the targeted delivery of curcumin and green tea, designed to enhance breast cancer treatment paradigms - Xiaopeng Yu; Hong Yu; Chuanjia Yang; Cen Wu; Ying Cui; Ning Xu (Carbohydrate Polymers, 2025)

Magnetic biochar-cored halophilic aerobic granules: Novel strategy for rapid formation and structural stability enhancement - Dong-Xu Zhou; You-Wei Cui; Ya-Nan Mi; Zhen-Ying Li; Rui-Chun Yang; Yuan Sui (Bioresource Technology, 2025)

Regulation of Necroptosis by Aspergillus fumigatus Exopolysaccharide in Human Macrophages Derived from THP-1 Cells: Involvement of the RIP1-RIP3-MLKL Signaling Axis - Wei Shen; Meng Wang; Ting Han; Yan Yao; Xinyi Ying; Yuyue Cui; Peng Du (Current Microbiology, 2025)

Preparation and optimization of pickering emulsion stabilized by organosilane-modified palygorskite to encapsulate natural colorants for cosmetic application - Peixuan Tan; Hongyan Cui; Chao Jiang; Chunying Jiang; Qiongyi Huang; Jingying Li; Ying Tang; Yongjun Feng (Applied Clay Science, 2025)

A novel non-biological dual identification system based on SBE-β-CD@CdTe for the simultaneous detection of multiple steroids in environmental water - Xia Cui; Ying Zhao; Nan Zhou; Yajing Hou; Yaning Zhu; Peng Zhang; Pengqi Guo (Analytica Chimica Acta, 2025)

The protective effect of glycyrrhizic acid on acetic acid–induced intestinal injury in Epinephelus coioides - Fei-Fei Huang; Qing-Guo Song; Xiao-Xiao Zhang; Zi-Zhen Sun; Ying Liang; Fei Shi; Yong-Le Wu; Cui-Yun Zou (Aquaculture International, 2025)

A new isoflavone glycoside from the stems of Eclipta prostrata (L.) L. with glycosidase inhibitory activity - Yuan Gao; Ying-Xiao Xiao; Hao Xu; Xue-Feng Wu; Yi-Lin Li; Hyun-Sun Lee; Long Cui (Natural Product Research, 2025)

Harnessing synthetic microbial communities for sustainable agriculture: Enhancing soil health and crop yields - Yunhe Cui; Yue Tao; Yang Luo; Rui Sun; Siyue Han; Yang Yang; Zhongmin Dai; Ying Zhang (Critical Reviews in Environmental Science and Technology, 2025)

Object perception in sparse 3D point cloud scenes for floor-rearing chicken farming robots using an improved PointNet++ algorithm - Donger Yang; Di Cui; Yibin Ying (Computers and Electronics in Agriculture, 2025)

DCDNet: A deep neural network for dead chicken detection in layer farms - Dihua Wu; Yibin Ying; Mingchuan Zhou; Jinming Pan; Di Cui (Computers and Electronics in Agriculture, 2025)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

Proteins extracted from placenta regulate osteogenic differentiation of human mesenchymal stem cells - Benjie Wei; Ying Chen; Shengmin Zhang; Laisen Cui; Shuo Zhang; Zhong Zhuang; Chunhui Sun; Na Ren; Hong Liu (Tissue and Cell, 2025)

First isolation and identification of tembusu virus from naturally infected quails highlighting its cross-species transmission risk - Pengju Xu; Xuying Wang; Yangbao Ding; Cui Wang; Chang Cui; Zhipei Lu; Kang Ouyang; Yeshi Yin; Ying Chen; Zuzhang Wei; Weijian Huang; Yifeng Qin (Research in Veterinary Science, 2025)

A novel chemical constituent from the stems of Akebia quinata and its diacylglycerol acyltransferase inhibitory activity - Yuan Gao; Ying-Xiao Xiao; Hao Xu; Xue-Feng Wu; Yi-Lin Li; Hyun-Sun Lee; Long Cui (Phytochemistry Letters, 2025)

Genomic insights into the reticulate evolution of viviparous Phrynocephalus lizards on the Qinghai-Tibetan Plateau - Xianguang Guo; Zhongyi Yao; Bo Cai; Xiao Xiao; Qiwei Xu; Ying Chen; Lin Cui; Xia Qiu; Jinzhong Fu; Yin Qi; Weizhao Yang (Molecular Phylogenetics and Evolution, 2025)

Voltage regulation of enzyme activity to control the slow release rate of novel solid carbon source to achieve high efficiency denitrification performance - Bowei Zhao; Chenghao Pei; You Wu; Jiayi Qin; Sizhe Yu; Yuanhao Dong; Ying Cui; Zhihong Liu; Xiao Zhang; Aijuan Zhou; Xiuping Yue (Journal of Environmental Management, 2025)

MoS2-PVA hydrogel interfacial evaporator for desalination: The role of surface hydroxyl groups-modification towards low evaporation enthalpy and high evaporation efficiency - Yongqian Cui; Xinxin Liang; Xinye Xu; Jingyi Wang; Xiaolong Zhang; Xin Huang; Ying Wang; Baoyang Lu; Chuanyi Wang (Journal of Environmental Chemical Engineering, 2025)

Enhancement of biogenic Mn(II) oxidation rate and achievement efficient removal of Cd2+ by biochar: Key role of extracellular superoxide production - Huawei Wang; Xiqing Cui; Zhibo Yang; Ya-nan Wang; Yingjie Sun; Ying Gao; Lei Gao (Journal of Environmental Chemical Engineering, 2025)

Critical review on magnetic biological effects of microorganisms in the field of wastewater treatment: Theory and application - Hui-Juan Yan; You-Wei Cui; Hui-Kai Liang; Zhen-Ying Li (Journal of Environmental Chemical Engineering, 2025)

Effect of oleic acid iodine value on the flotation performance of oleic acid-based collectors for spodumene - Ying Zhang; Ning Sun; Yuhua Wang; Liu Luo; Man Cui; Yu Li (Journal of Environmental Chemical Engineering, 2025)

Vacancy-rich Nd2S3/TiO2 S-scheme heterojunction for boosted photocatalytic tetracycline hydrochloride degradation: Interfacial engineering and mechanism insight - Qiang Wang; Ying Tang; Tiantian Li; Dan Cui; Weixia Yang; Li Zhang; Kezhen Qi; Feng Yu (Journal of Environmental Chemical Engineering, 2025)

Editorial preface to special issue: Dynamics of Earth's climate system and biogeochemical cycles in deep time - Ying Cui; Gerilyn S. Soreghan; Shuang Zhang; Donald E. Penman (Global and Planetary Change, 2025)

Nutrient cycles in transition: C:N:P stoichiometry by forest conversion to plantations - Ying Wang; Anna Gunina; Peter B. Reich; Defeng Yang; Han Y.H. Chen; Yakov Kuzyakov; Yongxing Cui; Jingwen Chen; Zhiming Guo; Tao Sun (Forest Ecology and Management, 2025)

Preparation of superhydrophilic functionalized nZVI-MOF-74(Co)-PDA@PVDF composite membranes for enhanced Cr(VI) removal - Mingchun Bi; Yuning Liang; Weimeng Chi; Yuchao Cui; Yuxuan Liu; Juan Ren; Ying Chen (Environmental Research, 2025)

Coupling phosphorus rate and type enhances maize yield by regulating salt ion homeostasis in coastal saline soil-crop systems - Shuaibing Wu; Xingshuai Tian; Botao Yu; Jishi Zhang; Huifang Zheng; Qi Miao; Hao Ying; Zhenling Cui (European Journal of Agronomy, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Excellent durability and multifunctional textiles with dual-mode evaporative and radiative cooling enabled by in-situ growth of SiO2 and electrostatic network coating - Luxuan Zhang; Bo Xu; Man Zhou; Ying Liu; Ying Zhang; Li Cui; Ping Wang; Qiang Wang; Yuanyuan Yu (Chemical Engineering Journal, 2025)

Ionic liquids for highly efficient capture C4 alcohol aldehyde isomer VOCs: experimental and molecular mechanisms - Wenxuan Zhao; Ying Xu; Wenna Liu; Xiang Wang; Zhaoyou Zhu; Yinglong Wang; Peizhe Cui; Guoxuan Li (Chemical Engineering Journal, 2025)

Copper-doped cobalt‑iron layered double hydroxide nanosheets to enhance multi-enzymatic activities for antibacterial effect - Shuairu Zhu; Chao He; Hongwei Xu; Mei Yang; Wanding Cui; Xiaohua Yuan; Binwu Ying (Chemical Engineering Journal, 2025)

Three birds with one stone: In-situ etching-constructing nanocubes protective layer toward highly reversible aqueous zinc-iodine batteries - Xin-Yue Wang; Dan Xie; Zhi-Wei Wang; Fang-Yu Tao; Chang Liu; Wan-Yue Diao; Yu-Ying Wu; Cui-Yan Tong; Jing-Ping Zhang (Chemical Engineering Journal, 2025)

Regulating chemical and electronic structure of Ni-based catalysts via introducing heteroatoms for boosting electrochemical oxidation of borohydride - Ying Yang; Zhihong Cui; Caini Yi; Meilin Chen; Hang Yang; Xiaolong Hou; Guimiao Wang; Shuo Wang; Yuping Liu; Guozhong Cao; Danmei Yu; Xiaoyuan Zhou (Chemical Engineering Journal, 2025)

Molecular evolution of chloroplast genome in Triumfetta (Grewioideae, Malvaceae) - Rushan Yan; Yujie Zeng; Chengyu Chen; Abdur Rab; Hui Li; Raza Ullah; Madiha Islam; Ying Cui; Mengyang Liu; Xiaoxuan Tian (Planta, 2025)

Effects of biochar pyrolysis temperature on soil carbon and nitrogen turnover and life cycle assessment - Ying Gao; Haojie Cui; Haixin Guo (Plant and Soil, 2025)

Microbial diversity outweighs plant diversity in mediating the response of ecosystem multifunctionality to altered precipitation in a desert steppe - Cui Han; Yi Zhang; Xu Luo; Ying Zhao; Xueqin Yang; Jiali Lian; Jianping Li (Plant and Soil, 2025)

Impacts of water–sediment on nutrient dynamics in the lower yellow river - Yimei Ying; Xu Wang; Meng Shang; Xinrui Cui; Ruijie Huang; Caili Su; Bing Han; Qian Huang (Environmental Geochemistry and Health, 2025)

HIPK2 Confers Protection Against Septic Myocardial Injury by Regulating Ferroptosis - Kexin Cui; Ying Zhang; Juanjuan Miao; Qihong Zhao (Cardiovascular Toxicology, 2025)

Effects of temperatures and fines content on the shear properties of calcareous sand - Yang Wu; Ying Cai; Liwei Wen; Norimasa Yoshimoto; Caishun Meng; Jie Cui (Bulletin of Engineering Geology and the Environment, 2025)

Association Between Whole Blood Iron and Nonalcoholic Fatty Liver Disease in Elderly: A Case–Control Study - Zhe-Ying Jiang; Wei-Jia Meng; Ying Wang; Hua-Qin Su; Bi-Xiu Mao; Cai-Li Wang; Feng-Lian Peng; Cui-Ping Li; Lian-Ping He (Biological Trace Element Research, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Recovery of disintegrated halophilic aerobic granular sludge through ferric ion addition: Dual roles in filamentous fungal inhibition and microbial adhesion enhancement - Hui-Kai Liang; You-Wei Cui; Hui-Juan Yan; Zhen-Ying Li (Water Research, 2025)

Portable devices and machine learning-assisted lateral flow assay for food safety analysis: Developments and perspectives - Ying Wang; Minglu Wang; Jiarui Cui; Hongyan Zhang (Trends in Food Science & Technology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

The core cellular network modulates immune phenotype switching in hepatitis B - Chuangeng Chen; Ziqi Zhen; Meng Cui; Xiaoli Hu; Lei Yu; Fengxia Zhou; Xiaorong Yu; Dehui Yang; He Wu; Ying Cui; Xiang Li; Xudong Cui; et al. (Science Bulletin, 2025)

CaCl₂+chitosan treatment inhibits softening and quality decline in postharvest raspberry fruit during cold storage by regulating cell wall and antioxidation metabolisms - Huajun Sun; Ying Liu; Fangzheng Cui; Lili Qian; Sijing Zhu; Yue Li (Postharvest Biology and Technology, 2025)

The calmodulin-binding transcriptional activator transcription factor family in foxtail millet (Setaria italica L.): Molecular characterization, codon bias, and evolutionary trajectory - Huilong Chen; Kexin Ji; Yun Bai; Yuxian Li; Ying Liu; Fang Liu; Yutong Cui; Weina Ge; Zhenyi Wang (Plant Gene, 2025)

Dual-functional berberine-magnolol co-assembled nanoparticles inhibit Fusarium graminearum growth and mycotoxin production - Chenguo Li; Wei He; Yao Cui; Shimin Wu; Qing'ao Song; Ying Li; Jimin Guo; Xizhen Ge; Pingfang Tian (Pesticide Biochemistry and Physiology, 2025)

Impact of cationic reagent structure on the performance of combined collectors in spodumene-feldspar flotation system - Ying Zhang; Yuhua Wang; Ning Sun; Haiqiang Feng; Yu Li; Man Cui (Minerals Engineering, 2025)

Temperature effects on sodium oleate flotation performance and interfacial interactions in spodumene flotation - Ying Zhang; Yuhua Wang; Ning Sun; Man Cui (Journal of Water Process Engineering, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

A salt-tolerant tetracycline degrading fungal strain of Candida palmioleophila: Characterization and degradation pathway - Zhen-Ying Li; You-Wei Cui; Hui-Juan Yan; Hui-Kai Liang; Rui-Chun Yang (Journal of Hazardous Materials, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Energy efficiency improvement of market-dominant air conditioners based on GraPHsep method - Mengdi Cui; Yuzheng Ying; Yuping Gao; Jinbo Li; Baolong Wang (Journal of Cleaner Production, 2025)

Exposure to plasticizers in city waste recycling: Focused on the size-fractioned particulate-bound phthalates and bisphenols - Ting-Ting Xu; Ying-Jie Zhang; Jing-Feng Yi; Cui-Lan Bai; Ying Guo (Journal of Environmental Sciences, 2025)

Impacts of volcanism on geochemical records during the Late Permian-Early Triassic transition in northern and middle Norwegian continental margins - Qingting Wu; Joseph M. Nsingi; Wolfram M. Kürschner; Brian J. Beaty; Noah J. Planavsky; Elke Schneebeli-Hermann; Weiqi Yao; Emily R. Cepin; Ying Cui (Global and Planetary Change, 2025)

Efficiency of microbial fermentation on microbial shifts, enzymatic activity, and transcriptions in black soldier fly larvae during the sugarcane waste conversion - Fareed Uddin Memon; ChiHo Li; Sheraz Ahmad; Ying Cui; Xingbao Feng; Peng Zeng; Farhan Nabi; Zhijun Huang; Gianluca Tettamanti; Ting Chen; Ling Tian (Environmental Pollution, 2025)

Ultra-stretchable and subzero-healable epidermal electrodes enabled by kirigami-networked microcrack engineering for human-machine interactions - Ying Xiao; Yilu Cui; Jie Wan; Yang Yang; Xiangrong Shi; Lingui Han; Ziming Wang; Dianpeng Qi; Bo Jiang; Kuiyuan Zhang (Chemical Engineering Journal, 2025)

Experimental Study of High-Efficiency Anchoring Device for Improving the Performance of Resin-Grouted Bolt - Lei Cui; Ying Zhang; Yishan Pan; Shaowei Liu (Rock Mechanics and Rock Engineering, 2025)

Chronic Anatabine Administration Attenuates Cardiovascular Activity by Targeting NF-κB/NLRP3/Caspase-1-Dependent Pyroptosis and Oxidative Stress in Paraventricular Nucleus of Hypertensive Rat - Qing Su; Shao-Jun Li; Jun-Yu Zhou; Jin-Bao Yang; Fang Zhao; Guo-Quan Zou; Jia-Xuan Ma; Qi Liu; Yuan-Yuan Feng; Cui-Ling Yang; Ying Li; Hong-Bao Li; et al. (Cardiovascular Toxicology, 2025)

Carnitine content and its influencing factors in marine animals collected from China’s offshore region and the Northwest Pacific Ocean - Yufeng Gao; Zhengguo Cui; Jianwei Li; Keming Qu; Qingkui Wang; Lanlan He; Xiangtao Liu; Xiner Zhao; Liuyizhi Zhang; Lingxiao Li; Ying Bai; Fangqun Dai; et al. (Acta Oceanologica Sinica, 2025)

Recent advances in pig behavior detection based on information perception technology - Jinyang Xu; Yibin Ying; Dihua Wu; Yilei Hu; Di Cui (Computers and Electronics in Agriculture, 2025)

Cooperative nuclear import of duck plague virus DNA polymerase subunits: pUL42 NLS Enhances pUL30 nuclear import and viral replication, with VP22 as a compensatory factor - Yuxi Cui; Mingshu Wang; Anchun Cheng; Qiao Yang; Xumin Ou; Di Sun; Yu He; Xinxin Zhao; Ying Wu; Shaqiu Zhang; Bin Tian; Juan Huang; et al. (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Feldspar dissolution controlled by coal-measure fluids and the impacts on pore structure of tight sandstone reservoirs: The case of the Jurassic Badaowan Formation in the Junggar Basin, Northwestern China - Zhi-Cheng Cui; Ke-Lai Xi; Ying-Chang Cao; Xiang Shan; Wei-Kai Huang; Hua-Jun Guo; Bo Peng; Nian-Ming Zan (Marine and Petroleum Geology, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Determination of potential α-glucosidase inhibitors in Jinxuan black tea based on bioaffinity ultrafiltration combined with UHPLC-Q-Exactive-MS - Guangneng Li; Jianyong Zhang; Hongchun Cui; Ying Gao; Yuliang Deng; Debao Niu; Junfeng Yin (Food Research International, 2025)

Efficient and selective adsorption of strategic metal In(III) from discarded waste leaching solution based on nanoconfinement-mediated zirconium phosphate - Zhenning Lou; Fan Yang; Haibiao Yu; Junshuo Cui; Xiaogeng Feng; Weijun Shan; Ying Xiong (Chemical Engineering Journal, 2025)

Review on environmental impacts of various types of power batteries using LCA - Jie Song; Gongxiang Cui; Ying Han; Xijing Yao; Xiaoqin Shen; Yugang Wang (Environment, Development and Sustainability, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

Soil disturbance induced by urban shield tunnelling in sandy pebble soil considering non-coaxiality and anisotropy - Jian Cui; Zhigang Yao; Tao Yu; Kaichen Ying; Yong Fang; Wanghao Xu; Yufang Zhang; Jian Li; Bo Liu (Tunnelling and Underground Space Technology, 2025)

Tetracycline degradation by a mixed culture of halotolerant fungi-bacteria under static magnetic field: Mechanism and antibiotic resistance genes transfer - Zhen-Ying Li; You-Wei Cui; Hui-Kai Liang; Hui-Juan Yan; Rui-Chun Yang (Journal of Hazardous Materials, 2025)

Modeling the impact of explosive volcanism on biogeochemical cycling at the peak of the Late Paleozoic icehouse - Lily S. Pfeifer; Qingting Wu; Ying Cui; Gerilyn S. Soreghan (Global and Planetary Change, 2025)

Hydrogeochemical characteristics of geothermal springs along the central section of Altyn Tagh fault: Implications for deep fluid circulation and tectonic activity - Zhaotong Sun; Jing Liu-Zeng; Yanxiu Shao; Wenxin Wang; Xiaocheng Zhou; Maoliang Zhang; Ying Li; Longfei Han; Fengzhen Cui (Geothermics, 2025)

Productivity of saline soils can be improved by integrating soil–crop system management - Qi Miao; Shuaibing Wu; Junchao Li; Jishi Zhang; Yunhong Wang; Gang Wu; Yixiang Sun; Hao Ying; Zhenling Cui (European Journal of Agronomy, 2025)

A novel ultrasound-triggered cardiac patch for targeted nitric oxide delivery to promote angiogenesis and reduce inflammation for the treatment of myocardial infarction - Lingling Xu; Qiaofeng Jin; Yihan Chen; Nan Cui; Ying Bai; Yihui Wang; Wenqu Li; Wenyuan Wang; Lufang Wang; Yali Yang; Li Zhang; Qing Lv; et al. (Chemical Engineering Journal, 2025)

High optical contrast and stable black electrochromic devices enabled by viologen and fluoran materials - Qilin Zhang; Xiong Liu; Yaowu He; Minming Yan; Imran Murtaza; Dongwen Zou; Tianhe Xu; Ying Cui; Lintao Zeng; Hong Meng (Chemical Engineering Journal, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Scalable solar-driven reforming of alcohol feedstock to H2 using Ni/Zn3In2S6 photocatalyst” [Chem. Eng. J. 513 (2025) 162965] - Denny Gunawan; Tahlia Stern; Jiajun Zhang; Jodie A. Yuwono; Jian Pan; Qiyuan Li; Haolin Yu; Michael Gunawan; Rosalie K. Hocking; Cui Ying Toe; Jason Scott; Rose Amal (Chemical Engineering Journal, 2025)

Cerium oxide nanoparticles as potent inhibitors of ferroptosis: role of antioxidant activity and protein regulation - Chenran Feng; Tong Yang; Jie Zhou; Chen Wang; Zheng Chu; Ying Zhang; Junzhe Zhang; Yin Kwan Wong; Cui Liu; Peng Gao; Ang Ma; Huan Tang; et al. (Journal of Molecular Medicine, 2025)

Identification of alternative splicing transcripts of Dorsal from Procambarus clarkii and their roles in innate immunity - Ying Huang; Rui Shen; Li-Fan Cui; Qian Ren (Aquaculture, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Differential impacts of invasive aquatic plants water lettuce (Pistia stratiotes) and water hyacinth (Eichhornia crassipes) on plankton community dynamics and its ecosystem functionality - Ziyao Shen; Jian Cui; Jinfeng Li; Ying Peng; Jian Li; Zhen Zhang; Andy Chan; Mianrun Chen; Dongrui Yao (Journal of Environmental Management, 2025)

Eccentricity pacing of the Paleocene-Eocene Thermal Maximum: Multi-section astrochronology and statistical insights in China - Runjian Chu; Huaichun Wu; Qiang Fang; Shijun Jiang; Ying Cui; Shihong Zhang; Tianshui Yang; Chengshan Wang (Global and Planetary Change, 2025)

Nitrogen reduction and split application increased grain yield and agronomic nitrogen use efficiency of oilseed flax (Linum usitatissimum. L) by increasing nitrogen status - Ming Wen; Yuhong Gao; Lizhuo Guo; Bin Yan; Peina Lu; Bin Wu; Yifan Wang; Yue Li; Zhengjun Cui; Peng Xu; Haidi Wang; Yuanyuan Cui; et al. (Field Crops Research, 2025)

Microbial response and the crucial function of predominant phyla in Sedum alfredii-mediated remediation of high concentration of multiple heavy metal soils - Han Zhang; Jianglong Cui; Ying Xiong; Guowen Li; Caili Du; Lieyu Zhang (Environmental Pollution, 2025)

Volcanic CO2 emissions from subduction of the tropical Paleo-Tethyan Ocean contributed to the early Permian deglacial warming - Wei Feng; Jianghai Yang; Peter A. Cawood; Rui Ma; Yinsheng Zhou; Ying Cui (Earth and Planetary Science Letters, 2025)

Scalable solar-driven reforming of alcohol feedstock to H2 using Ni/Zn3In2S6 photocatalyst - Denny Gunawan; Tahlia Stern; Jiajun Zhang; Jodie A. Yuwono; Jian Pan; Qiyuan Li; Haolin Yu; Michael Gunawan; Rosalie K. Hocking; Cui Ying Toe; Jason Scott; Rose Amal (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Petrology of Eclogite at Huwan, Western Dabie and Implications for Phase Equilibrium Modeling on LT-HP/UHP Eclogite - Bin Xia; Ying Cui; Yunfeng Shang; Jingtao Shi (Journal of Earth Science, 2025)

Long term global path planning for stratospheric airships under time-sequential uncertainty wind fields - JiaWen Xie; JingGang Miao; YuXuan Cui; ZongQi Zhao; Ying Lu (Advances in Space Research, 2025)

Effect of Yeast Selenium on Growth Performance, Muscle Selenium Deposition, and Antioxidant Capacity of Juvenile Cherax quadricarinatus - Ying Han; Chenchen Wang; Jimin Deng; Lizhen Zhong; Xiao Huang; Yuandong Sun; Xiaojuan Cui (Fishes, 2025)
This study aimed to investigate the effects of organic selenium-enriched yeast on the growth performance, muscle selenium deposition, and antioxidant capacity of juvenile Cherax quadricarinatus. Five experimental diets supplemented with 0.00 (control), 1.00, 2.00, 3.00, and 4.00 mg/kg of selenium-enriched yeast were fed to crayfish with an average initial body weight of (6.35 ± 1.66) g for 56 days. On days 0, 14, 28, 42, and 56 of the trial, 10 crayfish from each group were randomly sampled for body weight measurement. On day 28, the body weight of the crayfish fed diets containing 1.00, 2.00, 3.00, and 4.00 mg/kg selenium-enriched yeast was significantly higher (p

Cortical thickness alternation in obsessive-compulsive disorder patients compared with healthy controls - Chunyu Dong; Hao Zheng; Hailong Shen; Yu Wan; Yinghong Xu; Ying Li; Liangliang Ping; Hao Yu; Chuanxin Liu; Jian Cui; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2025)

Glycosidase inhibitory isoflavones from the seeds of Cullen corylifolium and their structure–activity relationship study - Ying-Xiao Xiao; Yi-Ran Jiang; Wen-Hui Xu; Yuan Gao; Tian-Tian Bei; Hao Xu; Xue-Feng Wu; Hyun-Sun Lee; Long Cui (Natural Product Research, 2025)

Climate change regulated carbonate production and accumulation in the Guaymas Basin over the past ca. 450,000 years - Hong Peng; Yuchen Zheng; Meng Zhou; Yasu Wang; Lihua Ran; Han Jiang; Ligia Pérez-Cruz; Rafael Venegas; Tobias Höfig; Andreas Teske; Daniel Lizarralde; Kathleen Marsaglia; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Fossil leaf cuticle: Best practices for preparation and paleo-CO2 analysis - Xiaoqing Zhang; Dana L. Royer; Carina E. Colombi; Juan Martin Drovandi; Jennifer C. McElwain; Gaëtan Guignard; Qin Leng; Barry H. Lomax; Nathan D. Sheldon; Rebekah A. Stein; Garland R. Upchurch; Yongdong Wang; et al. (Earth-Science Reviews, 2025)

Surface reconstruction via dissolution-reprecipitation of commercial alumina support to improve propane dehydrogenation performance - Haowei Wang; Wen-Cui Li; Ya-Dong Xie; Huan Yang; Ying Ma; An-Hui Lu (Chemical Engineering Journal, 2025)

Frequency influence on freestanding-mode triboelectric nanogenerators - Zhongjie Li; Bingyan Cui; Hengyu Guo; Ying Gong; Chao Yang; Qin Zhang; Xiaofan Li; Yan Peng; Junlei Wang (Chemical Engineering Journal, 2025)

Ultrafast self-gelling, superabsorbent, and adhesive chitosan-based hemostatic powders for rapid hemostasis and wound healing - Ashuang Liu; Shengyong Cui; Lei Song; Xiangshu Guo; Zhimao Huang; Shancan Wang; Kai Cheng; Ying Xiao; Youfen Fan; Rong Wang (Carbohydrate Polymers, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

U (uranium)-polymetallic mineral systems in the world: Genetic types, metallogenic settings and ore-forming mechanisms, and perspective for exploration - Deru Xu; Chanjuan Wang; Bin Li; Guoxiang Chi; Cui Yang; Wei Deng; Wenhao Li; Ying Li; Hengsong Zhang; Longfei Luo; Yaoyao Liao; Shaohao Zou; et al. (Science China Earth Sciences, 2025)

Investigating the mechanisms of flucarbazone-sodium resistance in Bromus japonicus Thunb - Yuning Lan; Xinhui Xue; Hailan Cui; Ruolin Wang; Ying Sun; Hongjuan Huang; Shouhui Wei; Xiangju Li; Zhaofeng Huang (Plant and Soil, 2025)

Light Treatment Ameliorates Sub-chronic MK-801-Induced Cognitive Deficits in Mice Through Up-regulating BDNF/p-CREB/p-ERK Signaling Pathway - Keke Cui; Yiying Zhou; Lizhi Zhang; Yudong Ying; Yan Xue; Xiaoqin Zhang; Qinwen Wang; Haowei Shen; Wenhua Zhou; Feng Gao; Zhengchun Wang (Molecular Neurobiology, 2025)

Plant species richness enhances aboveground primary productivity via net biodiversity effects and bacterial community interactions - Xu Luo; Yingzhong Xie; Shaoli Yue; Mingfan Yang; Cui Han; Yaxin Zhao; Ying Zhao; Jianping Li (Applied Soil Ecology, 2025)

Stable isotopes of black carbon and their implications to paleoclimate in the eastern Tethys during the PETM - Maurizia De Palma; Qingting Wu; Yixin Dong; Samantha Benjamin; Emily Cepin; Hermann Bermúdez; Zuoling Chen; Shijun Jiang; Ying Cui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Kuenenia-enriched hydroxyapatite granules enable stable high-rate nitrogen removal of high-strength food waste permeate in an EGSB-anammox system: Insights into granule performance and process scalability - Lan Lin; Wenzhao Zhao; Shen Cui; Ying Song; Yuanfan Zhang; Yu-You Li (Journal of Water Process Engineering, 2025)

Fertilization-recruited Actinomycetota enhances nutrient and energy metabolisms to favor plant growth and arsenic accumulation in Pteris vittata - Yong-He Han; Yi-Xi Li; Xi-Wen Cui; Ying Zhu; Hong Zhang; Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Water-induced phase separation ionogel for Recyclable information encryption - Ying Cui; Yunlong Liu; Qian Wang; Shuhong Li; Wenjun Wang; Xiaochen Dong (Chemical Engineering Journal, 2025)

A pH universal ORR catalyst with core-shell ZIF-derived binary cobalt/iron sites for Zn-air batteries - Yanou Qi; Weijun Shan; Haibiao Yu; Junshuo Cui; Zhenning Lou; Xiaogeng Feng; Ying Xiong (Chemical Engineering Journal, 2025)

Unraveling microbial community ecology and its effects on function and structure of halophilic aerobic granular sludge under varying salinities - Hui-Juan Yan; You-Wei Cui; Jun Chen; Hui-Kai Liang; Zhen-Ying Li (Bioresource Technology, 2025)

Prevalence and Predictors of Hemorrhagic Foci on Long-term Follow-up MRI of Recent Single Subcortical Infarcts - Shuai Jiang; Wen-Zuo Shang; Jing-Yu Cui; Yu-Ying Yan; Tang Yang; Yi Hu; Le Cao; Xun Yue; Ruo-Su Pan; Chen Ye; Jia-Yu Sun; Bo Wu (Translational Stroke Research, 2025)
Hemorrhagic foci surrounding the lacune in the long-term evolution of recent single subcortical infarcts (RSSIs) remains largely unexplored. We aimed to determine the prevalence, characteristics, and predictors of hemorrhagic foci in patients with RSSI. From a prospective, longitudinal study of RSSIs, we recruited patients who underwent multimodal MRI assessments both at baseline and approximately one year after the stroke onset. Hemorrhagic foci were identified using susceptibility-weighted imaging (SWI). Among 101 patients with RSSI, nearly half (n = 45, 44.6%) had hemorrhagic foci within the index RSSI lesions on follow-up SWI. RSSIs with hemorrhagic foci formation were associated with a longer time to follow-up imaging (median 449 versus 401 days, P = 0.005) and higher likelihood of being located in the anterior circulation compared to those without hemorrhagic foci (88.9% versus 64.3%, P = 0.003). Hemorrhagic foci were also associated with larger lesion size (P < 0.001), a higher proportion of cavitation formation (P = 0.003), higher baseline NIHSS scores (P = 0.004), and poorer functional outcomes (P = 0.001). In the subset of RSSIs in the lenticulostriate artery (LSA) territory, after adjustment for covariates, larger initial lesion volume (OR 1.80, 95% CI 1.13–2.87; P = 0.014) and greater decreases in LSA total length (OR 0.59, 95% CI 0.36–0.96; P = 0.035) were independently associated with hemorrhagic foci formation. The extent of ischemia in the initial infarct is predictive of the presence of hemorrhagic residues. Our findings contribute to the current understanding of the mechanisms underlying the evolution of RSSIs.

Research on the regulation mechanism of drought tolerance in wheat - Tengteng Zhang; Ying Zhang; Yi Ding; Yufeng Yang; Dan Zhao; Huiqiang Wang; Yifan Ye; Haojia Shi; Bowen Yuan; Zizheng Liang; Yulu Guo; Yue Cui; et al. (Plant Cell Reports, 2025)

Pathogenic characterization and drug resistance of neonatal sepsis in China: a systematic review and meta-analysis - Ruixue Wu; Xiaoyu Cui; Rui Pan; Na Li; Ying Zhang; Jianbo Shu; Yang Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Assessment of C2C-based point cloud comparison errors based on distribution characteristics of tunnel point clouds - Haitong Sui; Kensuke Asaba; Kazuo Sakai; Syuntaro Miyanaga; Ying Cui (International Journal of Remote Sensing, 2025)

Emerging role of lipid droplets in obscure puffer immune response against Vibrio harveyi - Xiaorui Song; Yaxing Yang; Nan Cui; Tianying Lei; Xingkun Jin; Ying Huang; Yan Shi; Zhe Zhao (Marine Life Science & Technology, 2025)
As dynamic and functionally active organelles, lipid droplets (LDs) mainly function in lipid anabolism, while recent studies showed that mammalian LDs also actively participated in innate immunity; however, the specific roles and regulation mechanism remain relatively unexplored, and the existing studies were mainly limited to mammals. In the present study, we first found that Vibrio harveyi , a serious pathogen in marine environment, could induce LDs accumulation in the liver of obscure puffer Takifugu obscurus on the histology, morphology and molecular levels, and the induction mainly conducted by promoting the synthesis of neutral lipids. Moreover, the antibacterial activity of LD proteins was significantly enhanced upon V. harveyi stimulation, and showed broad-spectrum characteristic. While the inhibition of LDs formation downregulated the expression of immune-related genes and immune signaling elements, highlighting the potential critical roles of LDs during the bacterial infection. The isolated LDs from obscure puffer liver were examined via proteomic analyses, and the data supported the conservative property of LDs from bacteria to humans, and revealed that numerous innate immune system-related components were enriched on the surface of LDs. These results will deepen the understanding of LDs biology and host immune defense mechanism, shedding light on the new strategies for the development of anti-infective therapies.

Hamiltonian based AUV navigation using adaptive finite-time trajectory tracking control - Jiankuo Cui; Mengxue Hou; Zheng Peng; Ying Wang; Jun-Hong Cui (Ocean Engineering, 2025)

The paleoenvironmental evolution of the Cambrian Miaolingian Epoch in South China - Yixin Dong; Jiuyuan Wang; Yijiang Zhong; Anqing Chen; Rongting Zheng; Peng Zhu; Chen Zhang; Zhong Han; Ying Cui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Climate and human activities shaping carbon-water-food interactions: Implications for governance in the Yangtze River Basin and its sub-basins, China - Yulong Li; Liang Zheng; Hongping Cui; Di Wu; Ying Wang (Journal of Environmental Management, 2025)

Hydrogeochemical characteristics of hot springs in the Longriba fault, northeastern Tibetan Plateau: Tectonic implications for geothermal fluid circulation - Yuwen Wang; Xiaocheng Zhou; Jingchao Li; Yunfei Bai; Yucong Yan; Jiao Tian; Miao He; Zhaojun Zeng; Bingyu Yao; Gaoyuan Xing; Shihan Cui; Ying Li; et al. (Journal of Asian Earth Sciences, 2025)

Timing of S-saturation in the formation of the Oubulage porphyry Cu-Au deposit, Inner Mongolia, Northern China - Yanan Zhang; Song Xue; Shangguo Su; Degao Zhai; Zijun Xu; Yingtian Liu; Ying Cui (Journal of Asian Earth Sciences, 2025)

Extraction of short-chain fatty acid ethyl Ester in Baijiu using covalent organic framework–based magnetic nanoparticles: Theoretical screening and experimental validation - Xiaolong Shang; Ying Han; Xudong Lian; Siting Ye; Ling Ao; Baoguo Sun; Rong Liu; Pan Zhen; Yongqing Zhang; Yintao Jia; Wei Dong; Xiaotao Sun; et al. (Food Chemistry, 2025)

Maternal green space exposure and congenital heart defects: A population-based study - Shihan Zhen; Lu Zheng; Qian Li; Zhouxin Yin; Hong Cui; Yan Li; Shuqi Wu; Kecheng Li; Ying Zhao; Fengchao Liang; Jiajin Hu (Environmental Research, 2025)

Decoding the end-Devonian Hangenberg oceanic anoxia event: Insights from ironstones in South China - Yuanjun Jonathan Lyu; Mei-Fu Zhou; Ying Cui; Rui-Zhong Hu; Zerui Ray Liu; Xiyao Li (Earth and Planetary Science Letters, 2025)

Corrigendum to “A spatiotemporal probiotic spore-loaded oxygen generator resumes gut microbiome balance and improves hypoxia for treating viral pneumonia” [Chem. Eng. J. 505 (2025) 159706] - Qikun Cheng; Mingzhi Xie; Hangjie Ying; Cuiyuan Jin; Lijun Yang; Dong Ma; Shumao Cui; Liyun Shi (Chemical Engineering Journal, 2025)

The toxic impacts of microplastics-borne benzo[a]pyrene and heavy metals on the health and behavior of seahorse Hippocampus erectus - Ying Liu; Nan Li; Dongwei Shang; Yanjing Yang; Pei Cui; Jinhui Sun (Journal of Oceanology and Limnology, 2025)

Soil heavy metals assessment of the Zhoukou riparian zone base of Shaying river basin, China: spatial distribution, source analysis and ecological risk - Yimei Ying; Meng Shang; Xu Wang; Xinrui Cui; Ruijie Huang; Zhixin Song; Yunjiao Han (Environmental Geochemistry and Health, 2025)

Comamonas squillarum sp. nov., Isolated from Intestine of Red Swamp Crayfish (Procambarus clarkii) - Shi Shi; Dao-Feng Zhang; Hong-Chuan Wang; Fu-Hui Jiang; Li-Fan Cui; Ying Huang (Current Microbiology, 2025)

The impact of changes in land transfer decisions on rural livelihood transitions: Evidence from dynamic panel data in China - Hongping Cui; Liang Zheng; Ying Wang (Applied Geography, 2025)

Ultrasensitive and Selective Nitrogen-Doped Fluorescent Carbon Dots Probe for Quantification Analysis of Trace Cu2+ in the Aqueous Environment - Zhenning Lou; Xinyu Zhou; Xiaomai Hao; Fan Yang; Wei Zhang; Xiaogeng Feng; Haibiao Yu; Junshuo Cui; Jing Gao; Ying Xiong; Yongfu Lian (Journal of Fluorescence, 2025)

Gut microbial communities and transcriptional profiles of black soldier fly (Hermitia illucens) larvae fed on fermented sericulture waste - Fareed Uddin Memon; Yanqing Zhu; Ying Cui; Xingbao Feng; Sheraz Ahmad; Peng Zeng; Farhan Nabi; Dengjian Hao; Zhijun Huang; Gianluca Tettamanti; Ling Tian (Waste Management, 2025)

Quantitative characterization method of point cloud distribution in tunnel for optimizing TLS scanning plan - Haitong Sui; Kensuke Asaba; Kazuo Sakai; Syuntaro Miyanaga; Ying Cui (Tunnelling and Underground Space Technology, 2025)

Ecological risk assessment for BDE-47 in marine environment based on species sensitivity distribution method - Ying Bai; Ruijie Ma; Zhengguo Cui; Liping Liu; Dongsheng Ding; Qingjing Hu; Bin Xia; Zhaochuan Li; Haibo Zhang; Keming Qu (Marine Environmental Research, 2025)

How do access and spatial dependency shape metro passenger flows - Mengying Cui; Lijie Yu; Shaoyu Nie; Zhe Dai; Ying-en Ge; David Levinson (Journal of Transport Geography, 2025)

The sedimentological signature of impact spherules and its relation to ejecta transport mechanisms during the Chicxulub asteroid impact (Cretaceous/Paleogene boundary) - Hermann D. Bermúdez; Liliana Bolívar; José A. Arz; Ignacio Arenillas; Vicente Gilabert; Robert DePalma; George Phillips; Daniela Bermúdez; Maurizia De Palma; Clemencia Gómez; Ying Cui (Journal of South American Earth Sciences, 2025)

Nanoparticles of iridium and other platinum group elements identified in Chicxulub asteroid impact spherules – Implications for impact winter and profound climate change - Vivi Vajda; Susan Nehzati; Gavin Kenny; Hermann D. Bermúdez; Ashley Krüger; Alexander Björling; Adriana Ocampo; Ying Cui; Kajsa G.V. Sigfridsson Clauss (Global and Planetary Change, 2025)

RETRACTED: A comparative study on rapid qualitative and quantitative determination of olive oil adulteration - Lijuan Du; Ying Yu; Yuling Cui; Guangbin Cui (Food Chemistry, 2025)

Regional and longitudinal dynamics of human milk protein components assessed by proteome analysis on a fast and robust micro-flow LC–MS/MS system - Junxia Cao; Xinling Cui; Hai Lu; Hui Wang; Wen Ma; Zhan Yue; Kemiao Zhen; Qiaosi Wei; Hongmei Li; Shilong Jiang; Wantao Ying (Food Chemistry, 2025)

The influence of polyphenols on the hydrolysis and formation of volatile esters in wines during aging: An insight of kinetic equilibrium reaction - Mengqi Ling; Dongsheng Cui; Baoqing Zhu; Demei Li; Haibin Mu; Jin Li; Ying Shi; Changqing Duan; Yibin Lan (Food Chemistry, 2025)

Response mechanisms of lactic acid bacteria under environmental stress and their application in the food industry - Xiaona He; Yu Cui; Qiaoyu Jia; Yongliang Zhuang; Ying Gu; Xuejing Fan; Yangyue Ding (Food Bioscience, 2025)

A spatiotemporal probiotic spore-loaded oxygen generator Resumes gut microbiome balance and Improves hypoxia for treating viral pneumonia - Qikun Cheng; Mingzhi Xie; Hangjie Ying; Cuiyuan Jin; Lijun Yang; Dong Ma; Shumao Cui; Liyun Shi (Chemical Engineering Journal, 2025)

Manganese halides with timely and delayed reversible thermal fluorescence quenching for dual-secure information encryption and anti-counterfeiting - Li Cong; Longyun Lv; Ying Liu; Yuxin Jia; Xuerui Chang; Yufan Lin; Juan Li; Bin-Bin Cui (Chemical Engineering Journal, 2025)

Advanced micro-textural engineering for the fabrication of high-performance superomniphobic surfaces - Chang Lv; Tao Wang; Yuanwei Ding; Haiyan Li; Yulong Ying; Lvlv Ji; Weihao Cui; Lei Liu; Sheng Wang (Chemical Engineering Journal, 2025)

Inoculation of plant growth-promoting rhizobacteria and rhizobia changes the protist community of alfalfa rhizosphere soil under saline-alkali environment - Yang Sun; Lu Tang; Ying Cui; Dihe Yang; Hong Gao; Jiaxin Chen; Ziying Zheng; Changhong Guo (Applied Soil Ecology, 2025)

Assessment of Peripheral Neuropathy Using Current Perception Threshold Measurement in Patients with Spinocerebellar Ataxia Type 3 - Xia-Hua Liu; Wei Lin; Hao-Ling Xu; Mao-Lin Cui; Zhuo-Ying Huang; Ying Li; Nan-Nan Zhang; Ning Wang; Zhi-Yong Wang; Shi-Rui Gan (The Cerebellum, 2025)

Contribution of nitrogen to main cereal crops yield and the key drivers in China - Xinyue Zhang; Zihan Wang; Yingcheng Wang; Xingshuai Tian; Kai He; Zhong Chen; Hao Ying; Yulong Yin; Zhenling Cui (Resources, Conservation and Recycling, 2025)

An integrated approach to modeling the influence of critical factors in low-carbon technology adoption by chemical enterprises in China - Lingling Guo; Miao Cui; Ying Qu; Peidong He (Journal of Environmental Management, 2025)

Bioenhanced remediation of dibutyl phthalate contaminated black soil by immobilized biochar microbiota - Yue Tao; Yao Wang; Yunhe Cui; Rui Sun; Bo Zhang; Jianhua Qu; Hongguang Cai; Ying Zhang (Journal of Environmental Management, 2025)

Remediation mechanism of high concentrations of multiple heavy metals in contaminated soil by Sedum alfredii and native microorganisms - Zihe Wang; Han Zhang; Ying Xiong; Lieyu Zhang; Jianglong Cui; Guowen Li; Caili Du; Kaiyang Wen (Journal of Environmental Sciences, 2025)

A preliminary investigation on the protective effects of β-glucan and mannan induced trained immunity in pufferfish Takifugu obscurus - Xiaorui Song; Tianying Lei; Nan Cui; Xingkun Jin; Ying Huang; Yan Shi; Zhe Zhao (Fish & Shellfish Immunology, 2025)

Identification and characterization of 16 tripartite motif-containing proteins from Takifugu obscurus - Li-Fan Cui; Rui Shen; Xiao-Rui Song; Yan Shi; Zhe Zhao; Ying Huang (Fish & Shellfish Immunology, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

Dy and K double-additive modified Co3O4 catalyst with high resistance to NO for catalyzing N2O decomposition - Haibiao Yu; Yanan Li; Yan Pan; Yuanting Du; Xiaogeng Feng; Junshuo Cui; Zhenning Lou; Weijun Shan; Ying Xiong (Chemical Engineering Journal, 2025)

Ag,Cd double gradient doping at front interface for high efficiency CZTSSe solar cells - Xiu-Chun Guo; Xin-Pan Cui; Ke Sun; Xue-Ying Luo; Wen-Hui Zhou; Dong-Xing Kou; Si-Xin Wu (Chemical Engineering Journal, 2025)

Integration of cobalt coordination polymer-based triboelectric nanogenerators as sustainable power sources for self-driven selective photocatalytic reactions - Fei Wang; Ying-Ying Zhang; Shuo Li; Lin Zhang; Yuanmeng Tao; Jiaxing Cui; Dandan Wang; Mingli Jiao; Chao Huang (Chemical Engineering Journal, 2025)

An AIE-TICT fluorescence probe cascade responsive to H2S, polarity and viscosity to track microenvironment changes in cellular model of ischemia-reperfusion injury - Liguo Ji; Aoxiang Fu; Yuying Zhang; Ying Xu; Yanbei Xi; Shaoli Cui; Na Gao; Linlin Yang; Wanbing Shang; Zhijun Yang; Guangjie He (Analytica Chimica Acta, 2025)

Analysis of nitrogen flow in the Yellow River Basin over a long time series - Ying Cui; Ruiping Li; Xu Chen (Environmental Monitoring and Assessment, 2024)

Dynamic trends in maize diseases and pests across six regions in China over two decades - Hong-ying Cui; Amber Sciligo; Xiao-ling Tan; Cang Hui; Yong-sheng Zhang; Wei Li; Zi-qiao Zhou; Zhen-qing Peng; Ping Ma; Zhi-shu Xiao; Fang Ouyang (Crop Protection, 2024)

Co-firing characteristic prediction of solid waste and coal for supercritical CO2 power cycle based on CFD simulation and machine learning algorithm - Ying Cui; Xinwang Wang; Shujun Jiang; Xiaoyong Gu; Zhongran Yao (Waste Management, 2024)

Carbon availability regulates fungal and bacterial populations in halophilic aerobic granular sludge treating saline wastewater - Hui-Kai Liang; You-Wei Cui; Zhen-Ying Li; Hui-Juan Yan; Xu Wang (Science of The Total Environment, 2024)

Preparation and application of ZnWO4/FeWO4 based photocatalyst: Organic pollutant degradation and microbicide - Jianbin Song; Ying Yang; Nan Cui; Samreen Sadiq; Iltaf Khan; Shu-yuan Liu; Kezhen Qi (Journal of Water Process Engineering, 2024)

Simultaneous removal of nitrogen and phosphorus from mariculture wastewater by mixotrophic-denitrification biofilm process based on pyrite and poly-3-hydroxybutyrate-co-hyroxyvelate - Lu Wang; Jun Liu; Xiaodan Lin; Zhihao Liu; Hongwu Cui; Ying Zhang (Journal of Water Process Engineering, 2024)

Relationship between root characteristics and saturated hydraulic conductivity in a grassed clayey soil - Ling-Xin Cui; Qing Cheng; Pui San So; Chao-Sheng Tang; Ben-Gang Tian; Cong-Ying Li (Journal of Hydrology, 2024)

Fluxapyroxad induced toxicity of earthworms: Insights from multi-level experiments and molecular simulation studies - Lanlan Zhang; Yao Liu; Ying Xu; Mengyuan Pei; Mengyao Yao; Xiaoni Chen; Yifei Cui; Fengyang Han; Yubo Lu; Cheng Zhang; Yanhua Wang; Peng Gao; et al. (Journal of Hazardous Materials, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Electrochemically mediated amine Regeneration-CO2 mineralization: Mechanism and influencing factors - Pengxiang Sun; Ying Jia; Chuanjia Qi; Lin Cui; Shouyan Chen; Yong Dong (Journal of Cleaner Production, 2024)

Optical characteristic of dissolved organic matter polar fractions by spectrum technologies and the relationship with indirect photodegradation of ofloxacin - Shukai Liu; Zhengguo Cui; Ying Bai; Dongsheng Ding; Qingjing Hu; Yuqiu Wei; Lin Zhu; Keming Qu; Rongguo Su (Journal of Environmental Chemical Engineering, 2024)

Icariin promotes skeletal muscle mitochondrial biogenesis by the AMPK-PPARδ-PGC-1α signaling pathway: A potential mechanism for beneficial muscle function homeostasis - Yunlong Dong; Cuiru Ren; Hongyuan Tang; Jiabao Yan; Ying Zhang; Linchao Fan; Guangning Kou; Zhenwei Cui (Food Bioscience, 2024)

Fabrication and characterization of bioactive curdlan and sodium alginate films for enhancing the shelf life of Volvariella volvacea - Asif Ali Khan; Feng-Jie Cui; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Syed Asim Shah Bacha; Zheng-Zi Ying; Ismail Khan; Umar Zeb; Abdullah A. Alarfaj; Mohammad Javed Ansari; Yan Yang; et al. (Food Bioscience, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Vitrification cryo-foil method for shoot tip cryopreservation and virus eradication in apple - Min-Rui Wang; Jun-Hua Bao; Xiao-Yan Ma; Zi-Han Yan; Zhen-Hua Cui; Li-Ying Zhu; Dong Zhang; Qiao-Chun Wang (Cryobiology, 2024)

Novel hierarchical ionic polymers for removal of perfluorooctane sulfonate and dichromate - Ke Kong; Jun Liang; Fangling Cui; Ying Zhang; Daqiang Yuan; Ruihu Wang (Chemical Engineering Journal, 2024)

Lignin-derived compounds assisted with Kocuria marina H-2 and Pseudomonas putida B6-2 co-culture enhanced naphthalene biodegradation - Jia-Qi Cui; Zhi-Qiang He; Kai Chen; Samuel Ntakirutimana; Zhi-Hua Liu; He Bai; Bing-Zhi Li; Ying-Jin Yuan (Bioresource Technology, 2024)

Effect of psychrotrophic Lactiplantibacillus plantarum L75 with exoploysaccharides-producing property on fermentation, bacterial community, and antioxidant activity of oat silage at low temperature - Rina Su; Xinyuan Cui; Hao Guan; Wencan Ke; Ying Liang; Hu Chen; Neha Sheoran; Mengya Jia; Yiling Yang; Lizhuang Hao; Guojun Zhao; Xusheng Guo (Animal Feed Science and Technology, 2024)

β-elemene Ameliorates Cisplatin Resistance of Gastric Cancer via Regulating Exosomal METTL3-m6A-ARF6 Axis - Huicong Song; Xuefeng Sun; Xiaohua Wang; Tianhai Xie; Zhihui Zheng; Ying Ji; Yanyan Cui (Cell Biochemistry and Biophysics, 2024)

Resilience analysis of the RCEP shipping network - Jiaguo Liu; Yating Fu; Kangkang Han; Ying Cui (Ocean & Coastal Management, 2024)

Laser Doppler vibrometer enables in-situ monitoring of peach firmness - Dachen Wang; Yilei Hu; Jiaqi Xiong; Yibin Ying; Ce Yang; Di Cui (Biosystems Engineering, 2024)

Typical alien invasive aquatic-plant species changed the stability rather than the diversity of plankton community in fresh water - Ziyao Shen; Jian Cui; Jinfeng Li; Ying Peng; Jian Li; Yu Liang; Yang Zhou; Zhen Zhang; Linhe Sun; Dongrui Yao (Science of The Total Environment, 2024)

Elevated sea surface temperature and enhanced primary productivity during Ocean Anoxic Event 1d in the eastern Tethys: Calcareous nannofossil evidence from southern Tibet, China - Yasu Wang; Shijun Jiang; Ying Cui; Ruize Liang; Hong Su (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Comparative quantitative phosphoproteomic and parallel reaction monitoring analysis of soybean roots under aluminum stress identify candidate phosphoproteins involved in aluminum resistance capacity - Ying He; Zhengbiao Wang; Wenmo Cui; Qingxiu Zhang; Meihui Zheng; Wen Li; Jie Gao; Zhenming Yang; Jiangfeng You (Journal of Hazardous Materials, 2024)

Metabolism of nitrogen and sulfamethoxazole, performance recovery mechanism, and antibiotic resistance genes (ARGs) behaviors in membrane aerated biofilm reactor (MABR) - Ting Li; Xiwei Cao; Lijun Gu; Ying Cui; Xinglin Li; Yi Li; Sher Jamal Khan; Baoan Li; Shuo Zhang (Journal of Cleaner Production, 2024)

Spatiotemporal variability of leaf critical senescence age across northern lands and its key drivers - Xingli Xia; Cuihai You; Ruiling Lu; Ning Wei; Chenyu Bian; Ying Du; Erqian Cui; Songbo Tang; Zhiqin Tu; Jiaye Ping; Kun Huang; Jianyang Xia (Global and Planetary Change, 2024)

The intensification of moisture resistance over MFI zeolite via heteroatom incorporation for diluted CO2 capture - Quanli Ke; Pengyun Pan; Mei Lu; Guonan Fang; Wei Zhang; Ruina Zhang; Guokai Cui; Xiaopo Niu; Feng Xiong; Ying Zhou; Bo Zhao; Hanfeng Lu (Fuel, 2024)

A time-saving pH-ultrasonic-shifting method for insoluble pea protein isolate to encapsulate polyphenol: Binding mechanism, structure, and functional characteristics - Linrong Yu; Qingchen Cui; Xiaolu Zhang; Liping Zhou; Mengshuang Li; Lei Tian; Xianggen Wu; Ying Jie (Food Hydrocolloids, 2024)

Molecular cloning and functional characterization of eight galectin genes from Takifugu obscurus - Ying Huang; Sheng-Hao Du; Li-Fan Cui; Fu-Hui Jiang; Zhe Zhao (Fish & Shellfish Immunology, 2024)

In situ iron coating of amorphous boron and characterization of its energy release behavior - Hongyang Li; Hong Li; Chao Wang; Zhenfeng Shen; Shentao Zeng; Sujun Shi; Qing Cai; Wenqi Xu; Ran Wang; Cui Luo; Ying Liu (Chemical Engineering Journal, 2024)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

Advanced design of metal single-atom (Pt, Mn, Fe or Cu) loaded S-Ni(OH)2 nanosheets array catalysts to achieve high-performance overall water splitting - Wenhui Fang; Tingting Tang; Min Li; Shixian Xin; Ying Wu; Yutao Cao; Zhize Yu; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

Comparative efficacy of alkaline slag, biomass ash, and biochar application for the amelioration of different acidic soils - Ernest Uwiringiyimana; Hong-wei Lai; Ni Ni; Ren-yong Shi; Xiao-ying Pan; Jia-ning Gao; Md Romel Biswash; Jiu-yu Li; Xiu-min Cui; Ren-kou Xu (Plant and Soil, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Diffusion behavior and environmental impact of odorants and TVOCs detected in a wastewater treatment plant for collaborative leachate treatment in Northwest China - Zilan Liao; Tong Gao; Pengyu Li; Tianlong Zheng; Lin Li; Cui Li; Wenwen Wang; Ying Wang; Junxin Liu (Chemosphere, 2024)

Hazards of toxic metal(loid)s: Exploring the ecological and health risk in soil–crops systems with long-term sewage sludge application - Shitao Gao; Yanmei Dong; Qingqi Jia; Shuxia Wu; Jiayun Bai; Chao Cui; Ying Li; Peng Zou; Miaoying An; Xinzhong Du; Hongbin Liu (Science of The Total Environment, 2024)

Effects of dissolved organic matter on distribution characteristics of heavy metals and their interactions with microorganisms in soil under long-term exogenous effects - Han Zhang; Wenjie Liu; Ying Xiong; Guowen Li; Jianglong Cui; Chen Zhao; Lieyu Zhang (Science of The Total Environment, 2024)

Experimental and mechanism study of Ca-based desulfurizer with composite modification for low concentration SO2 removal under low-temperature - Ying Jia; Jingxuan Jiang; Chenglong Wang; Pengxiang Sun; Yong Dong; Lin Cui (Process Safety and Environmental Protection, 2024)

A positive loop between relish and cuticle proteins and their roles in regulating AMPs expression during bacterial infection in Eriocheir sinensis - Xia Liang; Ying Huang; Hao Xu; Qian Ren; Di Cui; Xin Qi; Hai-Li Zhang (Fish & Shellfish Immunology, 2024)

Advancing the treatment of low carbon-to-nitrogen ratio municipal wastewater using a novel microaerobic sludge bed approach: Insights into enhanced performance and functional microbial community - Wenbo Li; Xiao Zhang; Bowei Zhao; Ying Cui; Philip Antwi; Rui Li; Aijuan Zhou; Jinping Li; Xiuping Yue (Environmental Research, 2024)

Recurrent marine anoxia in the Paleo-Tethys linked to constriction of seaways during the Early Triassic - Yuyang Wu; Alexandre Pohl; Li Tian; Jacopo Dal Corso; Ying Cui; Daoliang Chu; Jinnan Tong; Huyue Song; Hanchen Song; Haijun Song (Earth and Planetary Science Letters, 2024)

Electrochemical upcycling of biochar particles at anode-electrolyte interface in biochar-assisted water electrolysis for hydrogen production - Zhi Ying; Xinyue Chen; Xufei Gu; Hao Sun; Xiaoyuan Zheng; Binlin Dou; Guomin Cui (Chemical Engineering Journal, 2024)

Integrating L-cysteine coated polydopamine nanoparticles and deep eutectic solvents into chitosan matrix for multifunctional food packaging application - Ying Mao; Malin Cui; Xiaoyan Zhang; Hetong Lin; Da-Peng Yang (Chemical Engineering Journal, 2024)

Genetic relationships of Michelia compressa (Magnoliaceae) with Michelia species and its improvement by interspecific hybridization - Luomin Cui; Xiangdong Liu; Jiaqi Liu; Zhiquan Wang; Ziyang Wang; Ying Yang; Chaoguang Yu; Fangyuan Yu; Yunlong Yin; David Creech; Ming Yin; Sijun Zheng (Trees, 2024)

Influence of scion cultivar on the rhizosphere microbiome and root exudates of Phaseolus vulgaris in grafting system - Xiuli Wei; Yuanyuan Cui; Jiaqi Wang; Guoyuan Song; Ying Cao; Long Liu; Zhixin Liu; Jing Yang; Chen Li; Jiao Wang; Moran Li; Xiao Xiao (Plant and Soil, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Impact of corticosteroid doses on prognosis of severe and critical COVID-19 patients with Omicron variant infection: a propensity score matching study - Shiyao Wang; Ziying Chen; Xinran Zhang; Xiaojing Wu; Yuqiong Wang; Qi Zhang; Linna Huang; Xiaoyang Cui; Ying Cai; Xu Huang; Jingen Xia; Sichao Gu; et al. (Inflammopharmacology, 2024)
Background There is lack of research on corticosteroid use for severe and critical COVID-19 patients with Omicron variant infection. Methods This multi-center retrospective cohort study involved 1167 patients from 59 ICUs across the mainland of China diagnosed with severe or critical SARS-CoV-2 Omicron variant infection between November 1, 2022, and February 11, 2023. Patients were segregated into two groups based on their corticosteroid treatment—usual dose (equivalent prednisone dose 30–50 mg/day) and higher dose (equivalent prednisone dose > 50 mg/day). The primary outcome was 28-day ICU mortality. Propensity score matching was used to compare outcomes between cohorts. Results After propensity score matching, 520 patients in the usual dose corticosteroid group and 260 patients in the higher dose corticosteroid group were included in the analysis, respectively. The mortality was significantly higher in the higher dose corticosteroid group (67.3%, 175/260) compared to the usual dose group (56.0%, 291/520). Logistic regression showed that higher doses of corticosteroids were significantly associated with increased mortality at 28-day (OR = 1.62,95% CI 1.19–2.21, p = 0.002) and mortality in ICU stay (OR = 1.66,95% CI 1.21–2.28, p = 0.002). Different types of corticosteroids did not affect the effect. Conclusions The study suggests that higher-dose corticosteroids may lead to a poorer prognosis for severe and critical COVID-19 patients with Omicron variant infection in the ICU. Further research is needed to determine the appropriate corticosteroid dosage for these patients.

Occurrence, toxicity and removal of polystyrene microplastics and nanoplastics in human sperm - Ying Chen; Cheng Cheng; Wenqing Xu; Yanfan Cui; Yan Tian; Yulin Jiang; Yangyang Yuan; Ruirui Qian; Yujie Wang; Liping Zheng; Houyang Chen; Tao Luo (Environmental Chemistry Letters, 2024)

Evaluation of growth, immune characteristics and gut microbiota of juvenile sea cucumber Apostichopus japonicus fed with fermented feed from Corynebacterium glutamicum - Jiarong Cui; Xiaofei Tan; Zixuan Xu; Xinyu Sun; Liang Wang; Honglei Zhan; Yujia Liu; Ying Li; Bingnan Liu (Aquaculture International, 2024)

Examination of the effects of excess microalgae availability on the disruption of mussel byssus secretion - Ji-Yue Ni; Yan Zhou; Yu-Qing Wang; Shi-Hui Huang; Qian-Wen Cui; Wen-Yi Wang; Xiao-Ying Yang; Deborah M. Power; Yi-Feng Li (Aquaculture, 2024)

Expression pattern of the poplar GSTU family members in response to Alternaria alternate and PdbGSTU10 confers A. alternate resistance to Populus davidiana × P. bolleana - Ying Huang; Tianxiang Cui; Xiaodong Wang; Yi Niu; Gang Han; Chao Wang (Plant Science, 2024)

The receptor kinase OsANX limits precocious flowering and inflorescence over-branching and maintains pollen tube integrity in rice - Lan-Xin Zhang; Can-Can Shen; Ying-Xue Bai; Hao-Yue Li; Chen-Li Zhu; Chen-Guang Yang; Ammara Latif; Ying Sun; Cui-Xia Pu (Plant Science, 2024)

Driving mechanisms for the adaptation and degradation of petroleum hydrocarbons by native microbiota from seas prone to oil spills - Yumiao Zhou; Ying Wang; Shudi Yao; Xinyu Zhao; Qiang Kong; Lihua Cui; Huanxin Zhang (Journal of Hazardous Materials, 2024)

Investigation of the multiple taste enhancement properties of N-succinyl-amino acids and their relationship to chemical structure using dynamic sensory techniques - Pimiao Huang; Ying Liu; Lei Cai; Chun Cui (Food Chemistry, 2024)

The impact of a natural resource protection policy on economic development: Based on a policy evaluation of China’s coal resource tax reform - Shuhong Wang; Weiyao Li; Ying Zhang; Malin Song; Xueli Chen; Lianbiao Cui (Energy Policy, 2024)

Calcium isotope evidence of increased carbonate saturation state during the Frasnian–Famennian boundary event - He Zhao; Ying Cui; Lei Zhang; Zhong-Qiang Chen; Thomas J. Algeo; Yongsheng Liu; Zhaochu Hu; Jun Sun (Earth and Planetary Science Letters, 2024)

Autocatalytic oxidation of thiophene derivatives and co-degradation of refractory contaminants in Fenton reaction - Yaodan Cui; Yini He; Ying Jin; Zhichao Yang; Chao Shan; Qingrui Zhang; Weiming Zhang; Bingcai Pan (Chemical Engineering Journal, 2024)

Biotemplate synthesis of graphitic carbon-doped ZnO tube bundles rich in oxygen vacancies for dual-sensing of NO2/H2S at different temperatures - Zhao-Qi Cui; Rui Gao; Guo-Li Chen; Shi-Kai Shen; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Metal-doped biochar for selective recovery and reuse of phosphate from water: Modification design, removal mechanism, and reutilization strategy - Jianhua Qu; Wei Peng; Mengning Wang; Ke Cui; Jingdong Zhang; Fuxuan Bi; Guangshan Zhang; Qi Hu; Yifan Wang; Ying Zhang (Bioresource Technology, 2024)

Effect of using reclaimed water via furrow and subsurface drip systems under alternate partial root-zone irrigation mechanism on crops growth and soil properties - Mahmoud S. Hashem; Wei Guo; Xue-Bin Qi; Ping Li; Ying-jun She; Jiaxin Cui; Tong Li (Irrigation Science, 2024)
The growing population in the face of water scarcity inevitably necessitates the quest for alternative sources of irrigation water, which integrates them with irrigation strategies for improved agricultural productivity to meet the Sustainable Development Goals. A three-year field experiment was conducted in 2017, 2018, and 2019 to investigate the effect of water quality (reclaimed water (RW) and clean water (CW)), irrigation techniques (subsurface drip irrigation (SDI) and furrow irrigation (FUI)), irrigation methods (full irrigation (FI) and alternate partial root-zone irrigation (APRI) (70% ETc)), and their interactions on the fresh fruit yield (FY), irrigation water use efficiency (IWUE), and nitrogen use efficiency (NUE) of tomatoes. Further, electrical conductivity (EC), pH, and organic matter (OM) of soil were evaluated. The experiments were undertaken over three growing spring seasons in a greenhouse at the Chinese Academy of Agricultural Sciences in Henan Province, China. Throughout the three years of this study, the yield, the IWUE, and the NUE values of all treatments under RW were higher than those corresponding values under CW. The trend was the same under SDI as it was under FUI. Statistical analyses revealed that there was no significant effect ( P > 0.05) of water quality, irrigation technique, and irrigation methods on the soil EC, pH, and OM over the three years. In addition, the interaction between the different experimental factors over the three years of the study was not significant. In conclusion, the application of RW under SDI can result in saving CW and increasing productivity without any negative effect on the investigated soil properties. Furthermore, when RW-SDI is used in conjunction with APRI, it can result in increasing IWUE.

Process, advances, and perspectives of graphene oxide-SELEX for the development of aptamer molecular probes: A comprehensive review - Zhuoer Chen; Ying Yang; Xinge Cui; Luwei Chai; Hongbing Liu; Yangwei Pan; Yongkang Zhang; Yujia Xie; Tao Le (Analytica Chimica Acta, 2024)

Age-related alterations in vortex veins on indocyanine green angiography - Chen-Xi Cai; Shan-Shan Yu; Xiao-Mei Xiong; Bing-Qian Liu; Zhen-Qiang Lin; Qiang Wang; Jin-Li Cui; Ze-Hao Liu; Tao Li; Lin Lu; Ying Lin (GeroScience, 2024)
To determine age-related alterations in vortex veins in healthy subjects. A total of 228 healthy subjects (aged 4 to 86 years) were recruited and divided into four groups (G1, <21 years; G2, 21–40 years; G3, 41–60 years; and G4, 61–86 years). The clinical characteristics of the participants were recorded, and parameters including the number of vortex vein roots (NVVR), the central vortex vein diameter (CVVD), the mean root area of the vortex vein (MRAVV), and the weighted mean of the thickest branch diameter (WMTBD) were obtained by marking the vortex veins on indocyanine green angiography (ICGA). The NVVR in the age group over 60 years old was significantly lower than that in other age groups ( P < 0.05). The CVVD, MRAVV, and WMTBD of all age groups increased with increasing age ( P < 0.05). The NVVR was unevenly distributed among the quadrants ( P < 0.001). The proportions of type four vortex veins (complete systems including ampulla) and anastomotic branches of the vortex veins were significantly increased in elderly participants over 50 years of age ( P < 0.05). Subfoveal choroidal thickness was significantly correlated with age, NVVR, CVVD and MRAVV ( P < 0.05). This is the first study to reveal age-related alterations in vortex veins on ICGA in a healthy population. Aging may lead to partial vortex occlusion and residual vortex dilation. As age increases, anastomotic branches increasingly appear between the originally independent vortex veins. Translational relevance: Aging may lead to partial vortex occlusion and residual vortex dilation.

PFDA promotes cancer metastasis through macrophage M2 polarization mediated by Wnt/β-catenin signaling - Zhenyan Cui; Zekun Liu; Xiaoyu Yuan; Kean Lu; Mengyao Li; Sinan Xu; Kelie Chen; Fang Zheng; Ying Li; Paul Héroux; Yihua Wu; Dajing Xia (Chemosphere, 2024)

A review on micro- and nanoplastics in humans: Implication for their translocation of barriers and potential health effects - Cui-Lan Bai; Dan Wang; Yu-Ling Luan; Si-Nan Huang; Liang-Ying Liu; Ying Guo (Chemosphere, 2024)

Effect of hydraulic retention time on denitrification performance and microbial communities of solid-phase denitrifying reactors using polycaprolactone/corncob composite - Hongwu Cui; Yuna Feng; Weibin Lu; Lu Wang; Hao Li; Yu Teng; Ying Bai; Keming Qu; Yingying Song; Zhengguo Cui (Marine Pollution Bulletin, 2024)

International container intermodal competitiveness: An empirical study from Chinese hub ports - Hui Meng; Haonan Xu; Ying Cui; Jiaguo Liu (Ocean & Coastal Management, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Suppression of the vortex-induced vibration of the cylinder by the baffle plates at different submerged depths - Yongjian Zhong; Huichao Li; Baoshou Zhang; Fujun Diao; Boyang Li; Ying Cui (Ocean Engineering, 2024)

Paleoenvironment reconstruction of the eastern Tethys during the pre-onset excursion preceding the PETM - Yixin Dong; Anthony Gachetti; Qingting Wu; Maurizia De Palma; Xiumian Hu; Stefanie Brachfeld; Zhilin Yang; Jiuyuan Wang; Yasu Wang; Shijun Jiang; Ying Cui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Phytochrome B interacts with LIGULELESS1 to control plant architecture and density tolerance in maize - Qingbiao Shi; Ying Xia; Qibin Wang; Kaiwen Lv; Hengjia Yang; Lianzhe Cui; Yue Sun; Xiaofei Wang; Qing Tao; Xiehai Song; Di Xu; Wenchang Xu; et al. (Molecular Plant, 2024)

Early detection of nicosulfuron toxicity and physiological prediction in maize using multi-branch deep learning models and hyperspectral imaging - Tianpu Xiao; Li Yang; Dongxing Zhang; Tao Cui; Xiaoshuang Zhang; Ying Deng; Hongsheng Li; Haoyu Wang (Journal of Hazardous Materials, 2024)

Changes in pCO2 and climate paced by grand orbital cycles in the late Cenozoic - Yifei Zhang; Qiang Fang; Huaichun Wu; Christian Zeeden; Ying Cui; Meinan Shi; Shihong Zhang; Tianshui Yang; Haiyan Li (Global and Planetary Change, 2024)

Elastic, Janus 3D evaporator with arch-shaped design for low-footprint and high-performance solar-driven zero-liquid discharge - Ying Chen; Ruien Hou; Longjuan Yang; Chen Chen; Jianguo Cui; Tong Zhou; Yan Zhao; Jiaxin Song; Zimeng Fan; Yu Tang; Fengjuan Chen (Desalination, 2024)

pH-dependent growth of alumina nanorods with a high aspect ratio for enhanced propane dehydrogenation performance - Haowei Wang; Wen-Cui Li; Ying Ma; Yu Zhang; Shu-Zhen Zhou; An-Hui Lu (Chemical Engineering Journal, 2024)

Oral carbon dot nanozymes with red fluorescence and superoxide dismutase-like activity for colitis bioimaging and inflammation management - Mingxin Zhang; Yunlong Liang; Yanan Zhang; Lingmin Zhang; Ning Wang; Ying Zhou; Yufeng Wang; Manli Cui; Zhaoxiang Yu; Mingzhen Zhang; Yana Ma (Chemical Engineering Journal, 2024)

Microalgal extracellular polymeric substances (EPS) and their roles in cultivation, biomass harvesting, and bioproducts extraction - Yun Zhou; Xiaocai Cui; Beibei Wu; Ziqi Wang; Ying Liu; Tian Ren; Siqing Xia; Bruce E. Rittmann (Bioresource Technology, 2024)

LncRNA CCRR maintains Ca2+ homeostasis against myocardial infarction through the FTO-SERCA2a pathway - Hua Yang; Lina Xuan; Shengjie Wang; Huishan Luo; Xiaomeng Duan; Jianjun Guo; Shijia Cui; Jieru Xin; Junwei Hao; Xiufang Li; Jun Chen; Feihan Sun; et al. (Science China Life Sciences, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Characterization of adaptive expression regulation of yellowtail kingfish (Seriola lalandi) leptin, receptor, and receptor overlapping transcript genes in response to fasting and re-feeding strategies - Xin Cai; Ying Li; Aijun Cui; Yan Jiang; Bin Wang; Zhaojun Meng; Yongjiang Xu (Fish Physiology and Biochemistry, 2024)

New insights into the influences of firework combustion on molecular composition and formation of sulfur- and halogen-containing organic compounds - Caiqing Yan; Haibiao Chen; Fei Xu; Qinglong Fu; Ying Zhou; Ruizhi Zhou; Ruiyu Li; Mei Zheng; Mingjie Xie; Bin Jiang; Zhisheng Zhang; He Meng; et al. (Science of The Total Environment, 2024)

High dissolved oxygen regulation by side-stream supersaturated oxygenation impedes black-odor removal from rivers affected by combined sewer overflows - Qiuheng Zhu; Zhiyuan Wang; Ying Xiong; Guowen Li; Jianglong Cui; Xiaolong Zhu; Lieyu Zhang; Qiuwen Chen (Journal of Cleaner Production, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

H*ads dynamics engineering via bimetallic Pd–Cu@MXene catalyst for enhanced electrocatalytic hydrodechlorination - Lan-Ying Liu; Min-Hua Cui; John Justo Ambuchi; Shi-Ming Niu; Xin-Hui Li; Wo-Long Wang; He Liu; Guo-Shuai Liu; Ai-Jie Wang (Environmental Research, 2024)

Engineering multifunctional phase change composites enabled by dual-interpenetrating hybrid scaffold for excellent thermal conductivity and electromagnetic absorption - Boyang Hu; Hong Guo; Ying Cui; Jiaye Li; Min Cao; Weiyan Qi; Xiwei Cao; Baoan Li (Chemical Engineering Journal, 2024)

H2O2 self-supplied CuFeOx nanosystem as fenton-like reaction agents for endogenous/exogenous responsive synergetic antibacterial therapy - Lei Zhao; Yawen Chen; Qinglin Wei; Xinyi Lv; Ying Cui; Wenjun Wang; Xiaozhou Mou; Xuejiao Song; Xiaochen Dong; Yu Cai (Chemical Engineering Journal, 2024)

Amphidiploid production of a distant hybrid Populus simonii × P. euphratica cv. ‘Xiaohuyang-1’ and resulting in phenotypic variation - Ying Zhang; Zi-Yu Wang; Xiao-Tong Cui; Xiao-Xiao Zhang; Jin-Wang Zhang; Long Tie; Jun Wang (New Forests, 2024)

Correction to: Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2024)

Enhancing the health benefits of air quality improvement: a comparative study across diverse scenarios - Chuang Han; Chuanlong Cheng; Ying Liu; Qidi Fang; Chunyu Li; Feng Cui; Xiujun Li (Environmental Science and Pollution Research, 2024)

Development and trends of chicken farming robots in chicken farming tasks: A review - Donger Yang; Di Cui; Yibin Ying (Computers and Electronics in Agriculture, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

The EDLL motif-containing transcription factor MaERF96L positively regulates starch degradation during banana fruit ripening - Wan-shan Xie; Yun-yi Xiao; Zong-li Liu; Xiao-nan Li; Mei-zhi Cui; Jian-wen Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Ying-ying Yang (Postharvest Biology and Technology, 2024)

Application research of intelligent system based on BIM and sensors monitoring technology in construction management - Wei Cui; Ying Chen; Bo Xu (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Five new meroterpenes from the seeds of Psoralea corylifolia and their diacylglycerol acyltransferase activity - Xiao-Jing Shao; Meng-Xue Xiu; Xue-Hui Wang; Wen-Hui Xu; Ying-Xiao Xiao; Yuan Gao; Yi-Ran Jiang; Tian-Tian Bei; Hyun-Sun Lee; Long Cui (Phytochemistry Letters, 2024)

Catalytic ozonation of reverse osmosis concentrate from coking wastewater reuse by surface oxidation over Mn-Ce/γ-Al2O3: Effluent organic matter transformation and its catalytic mechanism - Rui Hu; Jia-Ying Li; Qiyi Yu; Sui-Qin Yang; Xinbo Ci; Bing Qu; Liwei Yang; Zheng-Qian Liu; Hongquan Liu; Jingjing Yang; Shiquan Sun; Yu-Hong Cui (Journal of Hazardous Materials, 2024)

A comprehensive evaluation of lipid profiles and nutritional quality in different animal source muscle tissues - Shuang Cui; Ying Wang; Zheng Zhou; Yu-Ying Zhang; Xu-Hui Huang; Da-Yong Zhou; Lei Qin (Food Bioscience, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Divergent growth and responses of conifer and broad-leaved trees to warming-drying climate in a semi-arid region, northern China - Ying Zhao; Junxia Li; Yuting Jin; Tsun Fung Au; Di Cui; Zhenju Chen (European Journal of Forest Research, 2024)

A Novel Bacillus amyloliquefaciens Specifically Improving the Solubility and Antioxidant Activities of Edible Bird’s Nest - Xin-Lin Li; Jian-Mei Lian; Xiao-Ling Chen; Qun-Yan Fan; Ying Yan; Feng-Jie Cui (Current Microbiology, 2024)

MYEOV with High Frequencies of Mutations in Head and Neck Cancers Facilitates Cancer Cell Malignant Behaviors - Deming Ou; Ying Wu; Jibin Zhang; Jun Liu; Zeyu Liu; Minfeng Shao; Xiaoying Guo; Shiman Cui (Biochemical Genetics, 2024)

Coastal ecological security assessment in Laizhou Bay, China: from the perspective of demographic-social-economic-natural complex ecosystem - Zhanying Wang; Meng Zhang; Zhengguo Cui; Yuqiu Wei; Ying Bai; Keming Qu (Environmental Science and Pollution Research, 2024)

Research on channel selection of low-carbon product considering advertising promotion under substitute competition - Haiyan Li; Qihan Cui; Lei Dou; Han Song; Ying Dai; Xinran Hu (Environment, Development and Sustainability, 2024)

Patient-derived pathogenic microbe deposition enhances exposure risk in pediatric clinics - Wan Wang; Zongyao Qiu; Hui Li; Xiaorong Wu; Ying Cui; Lixiang Xie; Bozhen Chang; Peipei Li; Hong Zeng; Tao Ding (Science of The Total Environment, 2024)

Immobilisation remediation of arsenic-contaminated soils with promising CaAl-layered double hydroxide and bioavailability, bioaccessibility, and speciation-based health risk assessment - Xiao-Chen Chen; Zhen-Jia Huang; Ao Wang; Jian-Ying Yu; Jian-Yu Zhang; Zi-Jun Xiao; Xiao-Yu Cui; Xian-Hua Liu; Nai-Yi Yin; Yan-Shan Cui (Journal of Hazardous Materials, 2024)

Influences of coexisting aged polystyrene microplastics on the ecological and health risks of cadmium in soils: A leachability and oral bioaccessibility based study - Xiao-Chen Chen; Ao Wang; Jun-Jie Wang; Zeng-Di Zhang; Jian-Ying Yu; Ying-Jie Yan; Jian-Yu Zhang; Jia Niu; Xiao-Yu Cui; Xian-Hua Liu (Journal of Hazardous Materials, 2024)

Updated loss factors and high-resolution spatial variations for reactive nitrogen losses from Chinese rice paddies - Yiwei Shang; Yulong Yin; Hao Ying; Xingshuai Tian; Zhenling Cui (Journal of Environmental Management, 2024)

Development of novel variable building skin with solar concentrating technology for obtaining energy benefits and optimizing indoor daylighting - Bo Wang; Xinshuo Zhang; Mengli Zhang; Yong Cui; Ying He (Energy and Buildings, 2024)

Waste cigarette butts-templated synthesis of in-situ graphitic carbon-doped ZnO fibers boosting dual-selectivity NO2/butanone at different temperatures - Zhao-Qi Cui; Ze Wei; Cong Chen; Yuan-Yuan Sun; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Machine learning assisted combined systems of wastewater treatment plants with constructed wetlands optimal decision-making - Wei Dai; Ji-Wei Pang; Ying-Jun Zhao; Jie Ding; Han-Jun Sun; Hai Cui; Hai-Rong Mi; Yi-Lin Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Rice N-biofertilization by inoculation with an engineered photosynthetic diazotroph - Yan Zeng; Mengmei Wang; Yunkai Yu; Lida Wang; Lingwei Cui; Chang Li; Ying Liu; Yanning Zheng (World Journal of Microbiology and Biotechnology, 2024)

Molecular hybridization method for obtaining paeonol-based fibrate derivatives with potent lipid-lowering and hepatoprotective activity - Lina Quan; Ying Guo; Siyao Wang; Mengfei Sun; Yan Pang; Chunli Cui; Jinrui Wang; Jinlian Wei; Peifeng Wei; Yundong Xie (Medicinal Chemistry Research, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Study on the Adsorption Performance of a Vortex Suction Cup under Varying Diameters of Underwater Structure Tubes - Qinyun Tang; Ying Du; Zhaojin Liu; Shuo Zhang; Qiang Zhao; Yingxuan Li; Liquan Wang; Tong Cui; Gang Wang (Journal of Marine Science and Engineering, 2024)
In certain precision work scenarios, underwater robots require the ability to adhere to surfaces in order to perform tasks effectively. An efficient and stable suction device plays a pivotal role in the functionality of such underwater robots. The vortex suction cup, distinguished by its uncomplicated design, high suction efficiency, and capability for non-contact adhesion, holds significant promise for integration into underwater robotic systems. This paper presents a novel design for a vortex suction cup and investigates its suction force and torque when encountering surfaces with varying curvature radii using Computational Fluid Dynamics (CFD) simulations and experimental testing. These findings offer valuable insights for the development of robots capable of adapting to underwater structures of different dimensions. Results from both experiments and simulations indicate that reducing the curvature radius of the adhered surface results in a decrease in suction force and an increase in torque exerted on the suction cup. As the adhered surface transitions from flat to a curvature radius of 150 mm, the adhesion force of our proposed vortex suction cup decreases by approximately 10%, while the torque increases by approximately 20% to 30%. Consequently, the adhesion efficiency of the suction cup decreases by about 25% to 30%.

Selective breeding of cold-tolerant black soldier fly (Hermetia illucens) larvae: Gut microbial shifts and transcriptional patterns - Chong Ma; Zhijun Huang; Xingbao Feng; Fareed Uddin Memon; Ying Cui; Xinyu Duan; Jianfeng Zhu; Gianluca Tettamanti; Wenfeng Hu; Ling Tian (Waste Management, 2024)

Exploring the differences between express and ride-pooling: A dual perspective on user perception and functional positioning in urban traffic system - Ying Lu; Shuyue Yao; Hongzhi Lin; Jianqiang Cui; Wenhui Yu (Travel Behaviour and Society, 2024)

A framework to quantitatively assess the influence of land use and land cover on coastal wetland hydrological connectivity from a landscape resistance perspective - Ying Man; Jizeng Du; Zhongmin Lian; Qing Wang; Baoshan Cui (Science of The Total Environment, 2024)

Minimal learning parameters-based simplified robust adaptive saturated control for dynamic positioning ship with input magnitude and rate saturations - Kun Liang; Jiawei Cui; Peng Lu; Yu Chen; Xiaogong Lin; Yaowei Sun; Qiang Zhang; Xinling Wen; Ying Duan (Ocean Engineering, 2024)

A TiO2 nanotube photoanode (blue TiO2 nanotube/RuO2/BiVO4) for efficient acetaminophen degradation and nitrogen removal - Xiaolin Sun; Ting Su; Xue Cui; Hongbin Yu; Ying Lu; Weichao Qin; Mingxin Huo (Journal of Water Process Engineering, 2024)

The structural change and determinants of global carbon footprint network embodied in international migration: A social network analysis - Ying Li; Chen Jiang; Xiaofan Li; Jinzhu Zhang; Yutao Wang; Xuechun Yang; Qi Cui; Yu Liu (Journal of Cleaner Production, 2024)

Revealing the activity and selectivity of atomically dispersed Ni in Zn3In2S6 for benzyl alcohol photoreforming - Denny Gunawan; Li Yuan Lau; Jodie A. Yuwono; Priyank V. Kumar; Louis Oppong-Antwi; Inga Kuschnerus; Shery L.Y. Chang; Rosalie K. Hocking; Rose Amal; Jason Scott; Cui Ying Toe (Chemical Engineering Journal, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

Early Triassic Legoupil Formation in Schmidt Peninsula, Antarctic Peninsula: Provenance and Depositional Settings - Chao Zhang; Ying-Chun Cui; Chen-Guang Liu; Fang-Hua Cui; Lu-Yuan Wang; Wei-Qiang Zhang (Journal of Earth Science, 2024)

Establishment of tissue culture regeneration system of Ficus tikoua - Xufei Li; Qianxia Li; Ying Cui; Tongfei Liu; Yanni Zhang (In Vitro Cellular & Developmental Biology - Plant, 2024)

Livelihood sustainability of rural households in response to external shocks, internal stressors and geographical disadvantages: empirical evidence from rural China - Hongping Cui; Ying Wang; Liang Zheng (Environment, Development and Sustainability, 2024)

Effects of extreme temperature events on deaths and its interaction with air pollution - Chuanlong Cheng; Ying Liu; Chuang Han; Qidi Fang; Feng Cui; Xiujun Li (Science of The Total Environment, 2024)

The role of fungi in the formation and instability of halophilic aerobic granular sludge in a continuous flow reactor - Hui-Kai Liang; You-Wei Cui; Jin-Lei Yan; Hui-Juan Yan; Zhen-Ying Li; Yu-Bo Cui (Journal of Water Process Engineering, 2024)

Recent advances and trends of carbon-based biocarriers for performance enhancement of anaerobic membrane bioreactor system - Ying Liu; Xuyan Cui; Xinbo Zhang; Junzhi Ren; Hongxia Li; Zhiwen Wang; Wenshan Guo; Huu Hao Ngo (Journal of Water Process Engineering, 2024)

Differential response of Hg-methylating and MeHg-demethylating microbiomes to dissolved organic matter components in eutrophic lake water - Zhengyu Wu; Zhike Li; Bo Shao; Ji Chen; Xiaomei Cui; Xiaoyu Cui; Xianhua Liu; Ying Xin Zhao; Qiang Pu; Jiang Liu; Wei He; Yiwen Liu; et al. (Journal of Hazardous Materials, 2024)

Enhanced hydroisomerization of n-heptane over bifunctional catalysts with highly dispersed Pd nanoparticles supported on H-Yβ composite zeolite - Yu-Hong Kang; Xiao-Qi Zhang; Juan Gao; Guang-Hui Liu; Yan-Jun Li; Yong Gao; Jin-Jun Bai; Ai-Min Wang; Xian-Yong Wei; Cui-Ying Lu (Chemical Engineering Journal, 2024)

Acetylcholine Analog-Modified Albumin Nanoparticles for the Enhanced and Synchronous Brain Delivery of Saponin Components of Panax Notoginseng - Ying Yu; Li Yun Wang; Yan Chi Liu; Hao Cui; Cheng Yuan; Cheng Xiao Wang (Pharmaceutical Research, 2024)

Establishment of an immortalized cell line derived from human adenomyosis ectopic lesions - Zilu Wang; Fengxin Cui; Yinuo Chen; Hongyun Liu; Yiran Zhang; Yaxin Shi; Yinuo Zhang; Yanfei Wang; Na Liang; Li Xu; Ying Liu; Zhiyong Liu; et al. (Tissue and Cell, 2024)

Clonally derived chicken primordial germ cell lines maintain biological characteristics and proliferative potential in long-term culture - Ying-Jie Niu; Wenjie Ren; Guangzheng Liu; Kai Jin; Dan Zheng; Qisheng Zuo; Yani Zhang; Xiang-Shun Cui; Guohong Chen; Bichun Li (Theriogenology, 2024)

Biogeochemical responses to global warming during the Paleocene–Eocene Thermal Maximum in the eastern Tethys - Qingting Wu; Ying Cui; Yasu Wang; Shijun Jiang; Yixin Dong; Jun Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Multispectral and molecular dynamics study on the impact of trans, trans-2,4-decadienal and 4-hydroxy-2-nonenal on myoglobin redox stability - Jiajing Qi; Xiaoyin Yang; Ying Cui; Yimin Zhang; Xin Luo; Yanwei Mao; Baochen Xu; Lixian Zhu; Rongrong Liang (Food Chemistry, 2024)

Involvement of TLRs/NF-κB/ESE-1 signaling pathway in T-2 toxin-induced cartilage matrix degradation - Yawen Shi; Rui Wang; Yanan Li; Yixin Cui; Ying He; Hui Wang; Yinan Liu; Meng Zhang; Yonghui Chen; Mingzhao Jia; Kunpan Chen; Xingran Ruan; et al. (Environmental Pollution, 2024)

Insight into hydrogen production through halotolerant and cellulose-degrading Clostridium thermopalmium - Sheng-Jie Chen; Ming-Jun Zhu; Si-Ying Cui (Chemical Engineering Journal, 2024)

Piperlongumine inhibits esophageal squamous cell carcinoma in vitro and in vivo by triggering NRF2/ROS/TXNIP/NLRP3-dependent pyroptosis - Yue Cui; Xiao-bo Chen; Ying Liu; Qian Wang; Jie Tang; Man-jun Chen (Chemico-Biological Interactions, 2024)

Response of antibiotic resistance genes expression and distribution on extracellular polymeric substances and microbial community in membrane biofilm during greywater treatment - Xiaocai Cui; Ying Liu; Ting Wei; Yun Zhou (Bioresource Technology, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

7-Methoxy-13-dehydroxypaxilline: New indole diterpenoid from an endophytic fungus Penicillium sp. Nb 19 - Jing Yu; Jia-Peng Wang; Shi-Fang Liu; Cui-Yun Yin; De-Ying Tang; Yi-Hang Li; Li-Xia Zhang (Natural Product Research, 2024)

Crosstalk between aryl hydrocarbon receptor and Wnt/β-catenin signaling pathway: Possible culprit of di (2-ethylhexyl) phthalate-mediated cardiotoxicity in zebrafish larvae - Yang Yang; Yue Tao; Xiaodong Yi; Guanyu Zhong; Yanyan Gu; Yunhe Cui; Ying Zhang (Science of The Total Environment, 2024)

Metabolic insights into how multifunctional microbial consortium enhances atrazine removal and phosphorus uptake at low temperature - Siyue Han; Yue Tao; Longwei Zhao; Yunhe Cui; Ying Zhang (Journal of Hazardous Materials, 2024)

Experimental study and modelling of continuous SO2-depolarized electrolysis in hybrid sulfur cycle for hydrogen production - Zhi Ying; Aoli Yang; Muyang Zhao; Jingyang Yang; Xiaoyuan Zheng; Binlin Dou; Guomin Cui (Journal of Cleaner Production, 2024)

Low glycemic index noodle and pasta: Cereal type, ingredient, and processing - Congli Cui; Yong Wang; Jian Ying; Weibiao Zhou; Dong Li; Li-jun Wang (Food Chemistry, 2024)

3D Printing windows and rheological properties for normal maize starch/sodium alginate composite gels - Ying Cui; Fan Yang; Chang-sheng Wang; Andreas Blennow; Changyong Li; Xingxun Liu (Food Hydrocolloids, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

High capillary effect and solar dual-drive nanofibrillated cellulose aerogels for efficient crude oil spill cleanup - Bingjie Fan; Xueming Bao; Shanshan Pan; Ying Liu; Yuanyuan Yu; Li Cui; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Synergistic effect between Ni single atoms and Ni nanoparticles for effectively boosting sustainable co-electrolysis of CO2 and hydrazine - Min Li; Ye Hu; Wenhui Fang; Shixian Xin; Ying Wu; Yutao Cao; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

Antimicrobial peptide dendrimers assisted Nanocomposite-Loaded lyotropic liquid crystalline for multimodal surgical site infection management - Xiao Yue; Ziqiao Zhong; Chen Wang; Ziyu Zhao; Xuejuan Zhang; Guanlin Wang; Wenhao Wang; Xiao Xia; Ziqiang Zhou; Yingtong Cui; Ying Huang; Chuanbin Wu; et al. (Chemical Engineering Journal, 2024)

Baicalin exerts neuroprotective actions by regulating the Nrf2-NLRP3 axis in toxin-induced models of Parkinson's disease - Jiahua Huang; Xinyue Zhang; Xueping Yang; Qingyun Yv; Fanlong Ye; Sheng Chen; Ying Cui; Linting Gu; Min Zhu; Wenwei Li (Chemico-Biological Interactions, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Changes in years of life lost and life expectancy by reducing air pollution - Ying Liu; Shuxia Yang; Chunyu Li; Qidi Fang; Chuang Han; Chuanlong Cheng; Yunxian Cao; Feng Cui; Xiujun Li (Air Quality, Atmosphere & Health, 2024)

Plant colorants for natural hair coloration: Dyeing optimization and photostability assessment - Hongyan Cui; Rui Cai; Zhongjie Hua; Ying Tang (Sustainable Chemistry and Pharmacy, 2023)

Functional characterization of two NAC transcription factors HfNAP1 and HfNAC090 associated with flower programmed cell death in daylily (Hemerocallis fulva) - Ying Wang; Yike Gao; Yuxuan Cui; Yi lv; Jing Zhou; Qixiang Zhang (Plant Science, 2023)

Effect of the molecular weight of DOM on the indirect photodegradation of fluoroquinolone antibiotics - Shukai Liu; Zhengguo Cui; Dongsheng Ding; Ying Bai; Jianlei Chen; Hongwu Cui; Rongguo Su; Keming Qu (Journal of Environmental Management, 2023)

Recent advances in Ganoderma lucidum polysaccharides: Structures/bioactivities, biosynthesis and regulation - Zi-Ying Zhang; Feng-Jie Cui; Lei Sun; Xin-Yi Zan; Wen-Jing Sun (Food Bioscience, 2023)

Antibacterial properties and mechanism of nanometer zinc oxide composites - Ying Wang; Jiawei Liu; Ting Wang; Li-Zhi Liu; Chengcheng Tian; Ye Cui; Wenjun Shao; Xia Hua; Ying Shi; Yuanxia Wang (Food Packaging and Shelf Life, 2023)

High-pressure pasting performance and multilevel structures of short-term microwave-treated high-amylose maize starch - Yu Tian; Ying Wang; Klaus Herbuger; Bent L. Petersen; Ying Cui; Andreas Blennow; Xingxun Liu; Yuyue Zhong (Carbohydrate Polymers, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

microRNA-944 inhibits breast cancer cell proliferation and promotes cell apoptosis by reducing SPP1 through inactivating the PI3K/Akt pathway - Ying Zhang; Shan Li; Xiangguo Cui; Yiliang Wang (Apoptosis, 2023)

Different strategies of Cd tolerance and accumulation in low-Cd-accumulating and high-Cd-accumulating ramie cultivars - Wei She; Hucheng Xing; Ruiping Quan; Ying Zhang; Yucheng Jie; Ruifang Yang; Guoxian Cui (Acta Physiologiae Plantarum, 2023)

Exploring the spatial–temporal evolution and driving mechanisms for coupling coordination between green transformation of urban construction land and industrial transformation and upgrading: a case study of the urban agglomeration in the middle reaches of the Yangtze River - Fulong Cui; Ying Wang; Guihai Liu (Environmental Science and Pollution Research, 2023)

Photo-electrochemical oxidation flow system for stormwater herbicides removal: Operational conditions and energy consumption analysis - Zhaozhi Zheng; Kefeng Zhang; Cui Ying Toe; Rose Amal; Ana Deletic (Science of The Total Environment, 2023)

Identifying the key factors affecting the trimethylamine N-oxide content of teleost fishes collected from the marginal seas of China and the epipelagic zone of the northwest Pacific Ocean - Qingjing Hu; Wanyu Zhao; Keming Qu; Ning An; Lingxiao Li; Yuqiu Wei; Ying Bai; Tao Jiang; Jufa Chen; Fangqun Dai; Hongsheng Wang; Zhengguo Cui (Science of The Total Environment, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

Federated learning with SARIMA-based clustering for carbon emission prediction - Tianxu Cui; Ying Shi; Bo Lv; Rijia Ding; Xianqiang Li (Journal of Cleaner Production, 2023)

A multilevel social-ecological network approach for reconciling coastal saltmarsh conservation and development - Ying Man; Kang Liu; Tian Xie; Fangwen Zhou; Wei Shi; Zezheng Liu; Qing Wang; Baoshan Cui (Journal of Environmental Management, 2023)

Functional characterization of obscure puffer ToNK-lysin: A novel immunomodulator possessing anti-bacterial and anti-inﬂammatory properties - Yaxing Yang; Xiaorui Song; Nan Cui; Tianying Lei; Ying Huang; Yan Shi; Yadong Hu; Xinghu Zhou; Zhe Zhao (Fish & Shellfish Immunology, 2023)

Deep utilization of salinity gradient energy between concentrated seawater and river water by multi-stage reverse electrodialysis - Zhi-Yuan Guo; Wei-Zhe Cui; Zhi-Yong Ji; Kaniki Tumba; Jing Wang; Liu-Jia Fu; Zhao-Xiang Zhang; Jie Liu; Ying-Ying Zhao; Zhong-De Zhang; Jun-Sheng Yuan (Desalination, 2023)

Using sulfide as nitrite oxidizing bacteria inhibitor for the successful coupling of partial nitrification-anammox and sulfur autotrophic denitrification in one reactor - Yiyi Zhao; Ying Dong; Xue Chen; Zhibin Wang; Zhaojie Cui; Shou-Qing Ni (Chemical Engineering Journal, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Generative adversarial networks with multi-scale and attention mechanisms for underwater image enhancement - Ziyang Wang; Liquan Zhao; Tie Zhong; Yanfei Jia; Ying Cui (Frontiers in Marine Science, 2023)
The images captured underwater are usually degraded due to the effects of light absorption and scattering. Degraded underwater images exhibit color distortion, low contrast, and blurred details, which in turn reduce the accuracy of marine biological monitoring and underwater object detection. To address this issue, a generative adversarial network with multi-scale and an attention mechanism is proposed to improve the quality of underwater images. To extract more effective features within the generative network, several modules are introduced: a multi-scale dilated convolution module, a novel attention module, and a residual module. These modules are utilized to design a generative network with a U-shaped structure. The multi-scale dilated convolution module is designed to extract features at multiple scales and expand the receptive field to capture more global information. The attention module directs the network’s focus towards important features, thereby reducing the interference from redundant feature information. To improve the discriminative power of the adversarial network, a multi-scale discriminator is designed. It has two output feature maps with different scales. Additionally, an improved loss function for the generative adversarial network is proposed. This improvement involves incorporating the total variation loss into the traditional loss function. The performance of different methods for enhancing underwater images is evaluated using the EUVP dataset and UIEB dataset. The experimental results demonstrate that the enhanced underwater images exhibit better quality and visual effects compared to other methods.

Elemental sulfur-driven autotrophic denitrification process for effective removal of nitrate in mariculture wastewater: Performance, kinetics and microbial community - Lu Wang; Jun Liu; Yongfu Li; Zhihao Liu; Long Zhang; Hong Che; Hongwu Cui; Ying Zhang (Chemosphere, 2023)

NAT10 regulates the repair of UVB-induced DNA damage and tumorigenicity - Zizhao Yang; Emma Wilkinson; Yan-Hong Cui; Haixia Li; Yu-Ying He (Toxicology and Applied Pharmacology, 2023)

Effects of dietary resveratrol supplementation in cattle on the anti-oxidative capacity and meat quality of beef steaks under high‑oxygen packaging - Ying Cui; Jiajing Qi; Jiqiang Li; Yimin Zhang; Xiaoyin Yang; Luo Xin; Lebao Niu; Baochen Xu; Zhanyu Qian; Lixian Zhu; Rongrong Liang (Meat Science, 2023)

Phthalates (PAEs) and reproductive toxicity: Hypothalamic-pituitary-gonadal (HPG) axis aspects - Ying Zhang; Yang Yang; Yue Tao; Xiangyong Guo; Yunhe Cui; Zixu Li (Journal of Hazardous Materials, 2023)

Atomic hydrogen-mediated enhanced electrocatalytic hydrodehalogenation on Pd@MXene electrodes - Lan-Ying Liu; Guo-Shuai Liu; Shi-Ming Niu; He Liu; Min-Hua Cui; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Eustatic change across the Paleocene-Eocene Thermal Maximum in the epicontinental Tarim seaway - Jingxin Jiang; Xiumian Hu; Juan Li; Eduardo Garzanti; Shijun Jiang; Ying Cui; Yasu Wang (Global and Planetary Change, 2023)

Prevalence, distribution, accumulation, and risk of environmental corticosteroids and estrogens in biofilms from the Pearl River Delta - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Wei Tao; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang (Environmental Pollution, 2023)

Tandem fractionation technologies (TAFT) benefit multi-functional porous carbon toward lignin valorization - Kai Chen; Tao Xu; Shi-Chang Liu; Li Wang; Jia-Qi Cui; Zhi-Hua Liu; Bing-Zhi Li; Ying-Jin Yuan (Chemical Engineering Journal, 2023)

Genomic characterization of three bacteriophages infecting donkey-derived Escherichia coli - Jia-Qi Cui; Wen-Hua Liu; Can Zhang; Ling Zou; Hui-Ying Ren (Virus Genes, 2023)

One-pot preparation of bi-functional POSS-based hybrid monolith via photo-initiated polymerization for isolation of extracellular vesicles - Qi Zhang; Mengxi Chen; Fang Xu; Wen Wu; Xintong Luo; Ying Wang; Jiaxi Li; Xuanhao Cui; Yujia Tan; Zhi Li; Yujie Lin; Haiyang Zhang; et al. (Analytica Chimica Acta, 2023)

Data‐driven estimation of nitric oxide emissions from global soils based on dominant vegetation covers - Xingshuai Tian; Yulong Yin; Kai He; Ruonan Qiu; Jiahui Cong; Zihan Wang; Huitong Yu; Zhong Chen; Yiyan Chu; Hao Ying; Zhenling Cui (Global Change Biology, 2023)
Soils are a major source of global nitric oxide (NO) emissions. However, estimates of soil NO emissions have large uncertainties due to limited observations and multifactorial impacts. Here, we mapped global soil NO emissions, integrating 1356 in‐situ NO observations from globally distributed sites with high‐resolution climate, soil, and management practice data. We then calculated global and national total NO budgets and revealed the contributions of cropland, grassland, and forest to global soil NO emissions at the national level. The results showed that soil NO emissions were explained mainly by N input, water input and soil pH. Total above‐soil NO emissions of the three vegetation cover types were 9.4 Tg N year −1 in 2014, including 5.9 Tg N year −1 (1.04, 95% confidence interval [95% CI]: 0.09–1.99 kg N ha −1 year −1 ) emitted from forest, 1.7 Tg N year −1 (0.68, 95% CI: 0.10–1.26 kg N ha −1 year −1 ) from grassland, and 1.8 Tg N year −1 (0.98, 95% CI: 0.42–1.53 kg N ha −1 year −1 ) from cropland. Soil NO emissions in approximately 57% of 213 countries surveyed were dominated by forests. Our results provide updated inventories of global and national soil NO emissions based on robust data‐driven models. These estimates are critical to guiding the mitigation of soil NO emissions and can be used in combination with biogeochemical models.

Agrochemical-mediated cardiotoxicity in zebrafish embryos/larvae: What we do and where we go - Yang Yang; Yue Tao; Zixu Li; Yunhe Cui; Jinzhu Zhang; Ying Zhang (Critical Reviews in Environmental Science and Technology, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Nanomedicine targets endogenous copper ions for disease diagnosis and therapy - Xiao Li; Ying Cui; Tianhua Zhou; Jianguang Li; Pei Lu; Lihui Yuwen; Lianhui Wang; Lixing Weng (Chemical Engineering Journal, 2023)

Chitosan-based mussel-inspired hydrogel for rapid self-healing and high adhesion of tissue adhesion and wound dressings - Yongyan Yang; Ying Ma; Jingfei Wang; Liru You; Ruiting Zhang; Qingye Meng; Shuangling Zhong; Wenqi He; Xuejun Cui (Carbohydrate Polymers, 2023)

A Complementary Streamflow Attribution Framework Coupled Climate, Vegetation and Water Withdrawal - Shanhu Jiang; Yongwei Zhu; Liliang Ren; Denghua Yan; Ying Liu; Hao Cui; Menghao Wang; Chong-Yu Xu (Water Resources Management, 2023)

The ionome and proteome landscape of aging in laying hens and relation to egg white quality - Guang Li; Yuqing Feng; Jian Cui; Qihang Hou; Tanfang Li; Meiting Jia; Zhengtian Lv; Qiuyu Jiang; Ying Wang; Ming Zhang; Lin Wang; Zengpeng Lv; et al. (Science China Life Sciences, 2023)

Downregulation of TCL6 protected human trophoblast cells from LPS-induced inflammation and ferroptosis - Yue Wang; Shasha Liu; Hongyan Cui; Ying Chang (Functional & Integrative Genomics, 2023)

Isolation and Identification of a Phosphate-Solubilizing Pantoea dispersa with a Saline–Alkali Tolerance and Analysis of Its Growth-Promoting Effects on Silage Maize Under Saline–Alkali Field Conditions - Ying Cui; Yujie Zhao; Run Cai; Hao Zhou; Jiaxin Chen; Lirong Feng; Changhong Guo; Dan Wang (Current Microbiology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

One-pot synthesis of 2D Ag/BiOCl/Bi2O2CO3 S-scheme heterojunction with oxygen vacancy for photocatalytic disinfection of Fusarium graminearum in vitro and in vivo - Yunlei Zhou; Zhuangzhuang Wang; Huanshun Yin; Xiaoting Cui; Ying Tian; Zhen Qiao; Suo Wang; Runye Hu; Wenjing Lv; An Mao; Jun Wang (Chemosphere, 2023)

Microbial niches and dynamics of antibiotic resistance genes in a bio-enhanced granular-activated carbon biofilm treating greywater - Ting Wei; Ziqi Wang; Ying Yang; Wanchen Xiang; Ying Liu; Beibei Wu; Xiaocai Cui; Bing Guo; Yun Zhou (Chemosphere, 2023)

Design, integration, and evaluation of a robotic peach packaging system based on deep learning - Qingyu Wang; Dihua Wu; Zhizhong Sun; Mingchuan Zhou; Di Cui; Lijuan Xie; Dong Hu; Xiuqin Rao; Huanyu Jiang; Yibin Ying (Computers and Electronics in Agriculture, 2023)

Key determinants controlling the seasonal variation of coastal zooplankton communities: A case study along the Yellow Sea - Yuqiu Wei; Xueyang Chen; Ying Liu; Yingzhe Wang; Keming Qu; Jun Sun; Zhengguo Cui (Marine Pollution Bulletin, 2023)

The characteristics of CDOM structural composition and the effect on indirect photodegradation of sulfamerazine - Ying Bai; Zhengguo Cui; Dongsheng Ding; Chenfei Hong; Hongwu Cui; Qingjing Hu; Mingying Zhou; Keming Qu (Science of The Total Environment, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

Chromones from the whole plant of Hypericum elodeoides and their bioactivities - Yanbing Mu; Letian Cui; Ping Ying; Huiping Wen; Dujuan Zhan; Lingyi Kong; Jun Luo (Phytochemistry Letters, 2023)

CTAB assisted evaporation-induced self-assembly to construct imidazolium-based hierarchical porous covalent organic polymers for ReO4-/TcO4- removal - Yuejiao Wang; Mengnan Huang; Haibiao Yu; Junshuo Cui; Jing Gao; Zhenning Lou; Xiaogeng Feng; Weijun Shan; Ying Xiong (Journal of Hazardous Materials, 2023)

Calcium isotopes reveal shelf acidification on southern Neotethyan margin during the Smithian-Spathian boundary cooling event - Feihong Ye; Laishi Zhao; Lei Zhang; Ying Cui; Thomas J. Algeo; Zhong-Qiang Chen; Zhengyi Lyu; Yuangeng Huang; Ghulam M. Bhat; Aymon Baud (Global and Planetary Change, 2023)

Tuning functional ionic deep eutectic solvents as green sorbents and catalysts for highly efficient capture and transformation of CO2 to quinazoline-2,4(1H,3H)-dione and its derivatives - Guokai Cui; Yisha Xu; Daqing Hu; Ying Zhou; Chunliang Ge; Huayan Liu; Wenyang Fan; Zekai Zhang; Biao Chen; Quanli Ke; Yaoji Chen; Bing Zhou; et al. (Chemical Engineering Journal, 2023)

Surfactant-assisted ethylenediamine for the deconstruction and conversion of corn stover biomass - Jia-Qi Cui; Ya-Qi Li; Samuel Ntakirutimana; Zhi-Hua Liu; Bing-Zhi Li; Ying-Jin Yuan (Bioresource Technology, 2023)

Evaluation of the respective contribution of anode and cathode for triclosan degradation in a bioelectrochemical system - Min-Hua Cui; Qian Zhang; John Justo Ambuchi; Lan-Ying Liu; Lei Chen; Shi-Ming Niu; Chao Zhang; Hong-Bo Liu; Chao Tie; Xue-Juan Bi; He Liu; Ai-Jie Wang (Bioresource Technology, 2023)

Interferons as negative regulators of ILC2s in allergic lung inflammation and respiratory viral infections - Cui Wang; Zhaoxiang Du; Ranhui Li; Ying Luo; Cuiming Zhu; Nan Ding; Aihua Lei (Journal of Molecular Medicine, 2023)

Knockdown of USF2 inhibits pyroptosis of podocytes and attenuates kidney injury in lupus nephritis - Ying Xie; Xiaoying Li; Wenli Deng; Nan Nan; Huimei Zou; Lei Gong; Min Chen; Jie Yu; Peilei Chen; Daolin Cui; Fan Zhang (Journal of Molecular Histology, 2023)

In-situ detection equipment for radon-in-water: unattended operation and monthly investigations - Chunqian Li; Meng Li; Guangquan Chen; Huaming Yu; Chenglun Zhang; Wen Liu; Jinjia Guo; Shibin Zhao; Lijun Song; Xiliang Cui; Ying Chai; Lu Cao; et al. (Acta Oceanologica Sinica, 2023)

Denitrification performance and in-situ fermentation mechanism of the wastepaper-flora slow-release carbon source - Ying Cui; Bowei Zhao; Xiao Zhang; Xiao Ma; Aijuan Zhou; Sufang wang; Xiuping Yue; Jianzheng Li; Jia Meng (Bioresource Technology, 2023)

Integrating polygenic and clinical risks to improve stroke risk stratification in prospective Chinese cohorts - Qingmei Cui; Fangchao Liu; Jianxin Li; Xiaoge Niu; Zhongying Liu; Chong Shen; Dongsheng Hu; Keyong Huang; Shufeng Chen; Jie Cao; Xiaoqing Liu; Ling Yu; et al. (Science China Life Sciences, 2023)

Phod-harboring bacterial communities mediated slow and fast phosphorus transformation in alkaline soil of a Robinia pseudoacacia afforestation chronosequence - Ying Wang; Lin Yang; Jiawen Zhang; Yan Li; Haibin Kang; Xiaoxiong Bai; Yongxing Cui; Min Zhang; Liguo Dong; Xuan Yu (Plant and Soil, 2023)

A callus-derived regeneration and Agrobacterium-mediated gene transformation developed for bilberry, Vaccinium myrtillus - Yanping Song; Wenbo Luo; Ying Wu; Xiaojie Li; Nick W. Albert; Yinhai Zhang; Xiangtao Chen; Kui Lin-Wang; Cecilia H. Deng; Zhubing Hu; Bingsong Zheng; Xiaofei Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Study on the feasibility of carbon source recovery by upflow anaerobic sludge blanket in simulated municipal wastewater - Xiao Zhang; Bowei Zhao; Rui Li; Ying Cui; Fei Xie; Aijuan Zhou; Jinping Li; Xiuping Yue (Science of The Total Environment, 2023)

Characteristics and emissions of isoprene and other non-methane hydrocarbons in the Northwest Pacific Ocean and responses to atmospheric aerosol deposition - Ying-Cui Wu; Xu-Xu Gao; Hong-Hai Zhang; Yong-Zheng Liu; Jian Wang; Feng Xu; Gui-Ling Zhang; Zhao-Hui Chen (Science of The Total Environment, 2023)

Insight into micropollutant abatement during ultraviolet light-emitting diode combined electrochemical process: Reaction mechanism, contributions of reactive species and degradation routes - Rui Hu; Sui-Qin Yang; Jia-Ying Li; Fengyi Sun; Zheng-Qian Liu; Jingjing Yang; Yu-Hong Cui; Beiping Zhang (Science of The Total Environment, 2023)

Conservation and divergence of flg22, pep1 and nlp20 in activation of immune response and inhibition of root development - Yan Huang; Junmei Cui; Meng Li; Rongqian Yang; Yang Hu; Xiaosong Yu; Ying Chen; Qiqi Wu; Huipeng Yao; Guozhi Yu; Jinya Guo; Huaiyu Zhang; et al. (Plant Science, 2023)

The BrAFP1 promoter drives gene-specific expression in leaves and stems of winter rapeseed (Brassica rapa L.) under cold induction - Xiaoyun Dong; Zigang Liu; Jiaping Wei; Guoqiang Zheng; Hui Li; Ying Wang; Haiyan Tian; Junmei Cui; Zefeng Wu; Xiaodong Cao; Chunmei Xu (Plant Science, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Changes in environmental performance with firm relocation and its influencing mechanism: An evidence of chemical industry in jiangsu, China - Ying Peng; Hongyun Zhu; Jian Cui (Journal of Environmental Management, 2023)

Distribution and dynamics of antibiotic resistance genes in a three-dimensional multifunctional biofilm during greywater treatment - Ying Liu; Beibei Wu; Xiaocai Cui; Qingqing Ren; Tian Ren; Yun Zhou (Environmental Pollution, 2023)

Occurrence and Risk of Organophosphate Flame Retardants in Multiple Urban Water of Beijing, China - Yanmeng Zhang; Weihua Cui; Na Zhang; Pan Qin; Ying Zhang; Xiaochun Guo; Zhi Wang; Shaoyong Lu (Water, Air, & Soil Pollution, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Quantitative evaluation of sea reclamation activities on tidal creek connectivity - Ying Man; Fangwen Zhou; Qing Wang; Baoshan Cui (Frontiers in Marine Science, 2023)
Deltas are in a dynamic balance due to the impact of fluvial and coastal flooding, and hydrological connectivity plays an important role. In recent decades, the dynamic equilibrium has been influenced by upstream and local human activities, including sea reclamation activities. However, in most instances, the influence of human activities has not been explicitly distinguished and quantified in detail. In this paper, the influence of sea reclamation activities on hydrological connectivity in the Yellow River Delta was quantified by parameterizing the resistance surfaces (a spatial layer that assigns a value to each landscape feature, indicating the degree to which that variable impedes or promotes movement) that includes sea reclamation activities. By optimizing a functional relationship between landscape features and hydrological connectivity (water flow movement patterns), the values in the resistance surfaces could be assigned. We first calculated hydrological distances among bifurcations from 1985 to 2020 with a 5-year interval representing the hydrological connectivity of each tidal creek. The sea reclamation activities in the YRD were classified into four: reclaimed land, sea enclosure activity, freshwater resource facilities, and engineering in the oil field to create resistance surfaces. We identified that the periods of 1990–1995 and 2000–2005 were under the most severe influence of sea reclamation activities. Sea enclosure activity, freshwater resource facilities, and engineering in oil fields played major roles in composing resistance surfaces. Mariculture (quantified relative resistance value, 1.00), reservoir (0.92), agriculture (0.91), and river (0.97) were the features with the highest resistance values in the initial and mature development stages. The formation of resistance (costs to movement) was due to human activities and natural factors, for example, the evolution of tidal creeks. To develop the resource in tidal flats sustainably, systematic monitoring and sufficient conservation awareness were required. This study contributed to coastal management and planning by providing a quantified assessment of different types of sea reclamation activities.

Probability of rainstorm and flood disasters due to extreme precipitation in Fen River Basin, China - Ying Li; Jin Sun; Xiaoqi Cui; Chenchen Jia; Jinlong Chao (Environmental Science and Pollution Research, 2023)

A new chamigrane sesquiterpene from the rice fermentation of Antrodiella albocinnamomea - Min Guo; Ying-Zhong Liang; Xiu-Ming Cui; Lin-Jiao Shao; Yin-Fei Li; Xiao-Yan Yang (Natural Product Research, 2023)

Hazardous substances and their removal in recirculating aquaculture systems: A review - Hao Li; Zhengguo Cui; Hongwu Cui; Ying Bai; Zhendong Yin; Keming Qu (Aquaculture, 2023)

Dissolved biochar fractions and solid biochar particles inhibit soil acidification induced by nitrification through different mechanisms - Ren-Yong Shi; Ni Ni; Ru-Hai Wang; Jackson Nkoh Nkoh; Xiao-Ying Pan; Ge Dong; Ren-Kou Xu; Xiu-Min Cui; Jiu-Yu Li (Science of The Total Environment, 2023)

The potential health risks of short-chain chlorinated paraffin: A mini-review from a toxicological perspective - Ying-Wen Mu; Dong Cheng; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2023)

OsCIP1, a secreted protein, binds to and stabilizes OsCR4 to promote aleurone layer development, seed germination and early seedling growth in rice - Lin-Lin Yan; Jing Mi; Can-Can Shen; Rong Qian; Jiao Wang; Cui-Xia Pu; Ying Sun (Plant Science, 2023)

Thermodynamic analysis of a food waste plasma gasification-based multigeneration system with dehumidification and carbon capture - Jifu Zhang; Haiyang Cheng; Zaifeng Xu; Yaru Zhou; Kexin Yin; Xianlong Wang; Ying Gao; Chaoyue Sun; Yinglong Wang; Peizhe Cui (Journal of Cleaner Production, 2023)

Correlating electrochemical biochar oxidation with electrolytes during biochar-assisted water electrolysis for hydrogen production - Yueyue Du; Zhi Ying; Xiaoyuan Zheng; Binlin Dou; Guomin Cui (Fuel, 2023)

Effects of Torulaspora delbrueckii co-fermented with Saccharomyces cerevisiae on physicochemical and aromatic profiles of blueberry fermented beverage - Yu Wang; Xiao-Yan Qi; Yu Fu; Qi Zhang; Xiao-Han Wang; Meng-Yao Cui; Ying-Ying Ma; Xue-Ling Gao (Food Chemistry, 2023)

Determination of dry soil layer and its soil heat flux distribution using actively heated distributed temperature sensing - Meng-Ya Sun; Bin Shi; Yu-Jun Cui; Chao-Sheng Tang; Xing Zheng; Jin Liu; Zi Ying; Yi-Jie Sun; Yun-Qiang Wang; Jing-Xiong Zhou (Engineering Geology, 2023)

Distribution characteristics and environmental effects of non-methane hydrocarbons in the East China Sea - Wen-Zhu Qiao; Ying-Cui Wu; Ping Wang; Jian Wang; Li-Min Zhou; Si-Tong Li; Hong-Hai Zhang (Continental Shelf Research, 2023)

Remediation of atrazine-contaminated soil in a fluidized-bed DBD plasma reactor - Nan Jiang; Ying Qu; Jinwei Zhu; Hongchang Wang; Ju Li; Yun Shu; Yutao Cui; Yuling Tan; Bangfa Peng; Jie Li (Chemical Engineering Journal, 2023)

Molecular mechanism of adsorbing triclocarban by the activated sludge in wastewater treatment systems - Hao Wang; Hanlin Cui; Xiaodan Ma; Carolyn R. Cornell; Liying Zhang; Yijun Ren; Minghan Li; Ying Liu; Shu-Hong Gao; Zhiling Li; Ai-Jie Wang; Jizhong Zhou; et al. (Chemical Engineering Journal, 2023)

Tuning ionic liquid-based functional deep eutectic solvents and other functional mixtures for CO2 capture - Yisha Xu; Ruina Zhang; Ying Zhou; Daqing Hu; Chunliang Ge; Wenyang Fan; Biao Chen; Yaoji Chen; Wei Zhang; Huayan Liu; Guokai Cui; Hanfeng Lu (Chemical Engineering Journal, 2023)

Sediment recycling and adakite petrogenesis: Constraints from the late Ordovician tonalite in the North Qilian suture zone - Yuxiao Chen; Ying Cui; Lipeng Zhang; Shanming Fu; Kai Wu; Shuguang Song; Weidong Sun; Tangfu Xiao (Chemical Geology, 2023)

The Complete Genome Sequence of a Gossypol-Degrading Bacterial Strain, Raoultella sp. YL01 - Si Chen; Weishu Zhang; Huiling Zhang; Ying Cui; Feng Wang; Jing Wu; Hongjun Chao; Dazhong Yan (Current Microbiology, 2023)

The effect of episodic foresight on intertemporal decision-making: the role of future self-continuity and perceived control - Hong-Yue Sun; Yuan-Ping Jiang; Xin Wang; Li-Ying Cui; Hong-Mei Sun (Cognitive Processing, 2023)

Real-ambient particulate matter exposure-induced FGFR1 methylation contributes to cardiac dysfunction via lipid metabolism disruption - Benying Li; Yanan Liang; Hongxu Bao; Daochuan Li; Ying Zhang; Xinyu Dun; Zijian Xu; Andong Ji; Zhen Zhang; Yahui Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Insights on nitrogen and phosphorus removal mechanism in a single-stage Membrane Aeration Biofilm Reactor (MABR) dominated by denitrifying phosphorus removal coupled with anaerobic/aerobic denitrification - Ming Li; Xiwei Cao; Ziqing Wu; Jiaye Li; Ying Cui; Jun Liu; Baoan Li (Journal of Water Process Engineering, 2023)

The eisosomes contribute to acid tolerance of yeast by maintaining cell membrane integrity - Chao Li; Jun Lu; Xue-Jiao Yan; Chang-Wen Li; Liang-Cai Lin; Dong-Guang Xiao; Cui-Ying Zhang (Food Microbiology, 2023)

Fate, ecotoxicity, and remediation of phthalic acid ester in soils - Yue Tao; Yunhe Cui; Guangxue Zhu; Guanyu Zhong; Ying Zhang (Current Opinion in Environmental Science & Health, 2023)

Dynamic microbial community composition, co-occurrence pattern and assembly in rhizosphere and bulk soils along a coniferous plantation chronosequence - Ying Wang; Liguo Dong; Min Zhang; Yongxing Cui; Xiaoxiong Bai; Bin Song; Jiawen Zhang; Xuan Yu (CATENA, 2023)

Coupled Time-Domain Investigation on a Vertical Axis Wind Turbine Supported on a Floating Platform - Jianhui Cui; Yongjian Zhai; Ying Guo; Wanru Deng; Liqin Liu (Journal of Ocean University of China, 2023)

Evaluation of the effect of biofilm formation on the reductive transformation of triclosan in cathode-modified electrolytic systems - Shi-Ming Niu; Qian Zhang; Thangavel Sangeetha; Lei Chen; Lan-Ying Liu; Ping Wu; Chao Zhang; Wei-Mon Yan; He Liu; Min-Hua Cui; Ai-Jie Wang (Science of The Total Environment, 2023)

Metagenomic study of carbon metabolism in black soil microbial communities under lead-lanthanum stress - Yue Tao; Lu Shen; Siyue Han; Zixu Li; Yunhe Cui; Yulong Lin; Jianhua Qu; Ying Zhang (Journal of Hazardous Materials, 2023)

Quaternary ammonium compounds promoted anoxic sludge granulation and altered propagation risk of intracellular and extracellular antibiotic resistance genes - Mingyan Zhao; Jingfeng Gao; Haoran Zhang; Yingchao Cui; Zhiqi Wang; Yifan Zhao; Yi Zhang; Ying Liu (Journal of Hazardous Materials, 2023)

Novel flavan-3-ol-dithiothreitol conjugates derived from the degradation of grape seed proanthocyanidins and their neuroprotective potential - Meng Huang; Meng Li; Ying Zhang; Huan Gong; Yuju Zhou; Danping Zhu; Lingxi Li; Ning Ma; Yan Cui (Food Chemistry, 2023)

Soil microbial trait-based strategies drive the storage and stability of the soil carbon pool in Robinia pseudoacacia plantations - Min Zhang; Xiaoxiong Bai; Ying Wang; Yan Li; Yongxing Cui; Sile Hu; M. Adams Jonathan; Liguo Dong; Xuan Yu (CATENA, 2023)

Indirect photodegradation of ofloxacin in simulated seawater: Important roles of DOM and environmental factors - Shukai Liu; Zhengguo Cui; Ying Bai; Dongsheng Ding; Junshuang Yin; Rongguo Su; Keming Qu (Frontiers in Marine Science, 2023)
Dissolved organic matter (DOM) plays a non-negligible role in the indirect photodegradation of organic contaminants. This research investigated the roles of DOM and the environmental factors (salinity, pH, NO 3 − , and HCO 3 − ) in the indirect photodegradation of ofloxacin (OFX) in simulated seawater. Results showed that DOM can significantly accelerate the indirect photodegradation of OFX, and 1 O 2 and 3 DOM * were the main reactive intermediates (RIs) that could promote the indirect photodegradation of OFX. Fluorescence excitation–emission matrix spectroscopy–parallel factor analysis (EEMs-PARAFAC) was used to divide DOM into four fluorescence components. The indirect photodegradation rate of OFX was affected by DOM structure, and terrigenous DOM usually produced more RIs to promote the indirect photodegradation of OFX. Increased salinity significantly promotes the indirect photodegradation of OFX, while increased NO 3 − concentration had no effect on the OFX indirect photodegradation. pH affected the formation of RIs and the structure of OFX, thereby affecting the indirect photodegradation of OFX. The indirect photodegradation rate of OFX increased in the HCO 3 − solution, which is due to the formation of carbonate radical (CO 3 − ). This study is essential in understanding the role of DOM in OFX indirect photodegradation and providing a novel insight into the fate, removal, and transformation of OFX.

Improved ResNet-50 deep learning algorithm for identifying chicken gender - Dihua Wu; Yibin Ying; Mingchuan Zhou; Jinming Pan; Di Cui (Computers and Electronics in Agriculture, 2023)

Marine renewable energy project: The environmental implication and sustainable technology - Ying Cui; Huida Zhao (Ocean & Coastal Management, 2023)

Effects of strength and weight of pre-ground improvement on seismic behavior of shallow overburden tunnel - Yasuo Sawamura; Kai Konishi; Ying Cui; Kiyoshi Kishida; Makoto Kimura (Tunnelling and Underground Space Technology, 2023)

Adaptation of bacterial community in maize rhizosphere for enhancing dissipation of phthalic acid esters in agricultural soil - Yu-Hong Huang; Yu-Jie Yang; Xiaolian Wu; Cui-Lan Zhu; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2023)

The long-acting herbicide mesosulfuron-methyl inhibits soil microbial community assembly mediating nitrogen cycling - Junli Cao; Ying Zhang; Gaochen Dai; Kai Cui; Xiaohu Wu; Fanxin Qin; Jun Xu; Fengshou Dong; Xinglu Pan; Yongquan Zheng (Journal of Hazardous Materials, 2023)

An efficient methodology for modeling to predict wine aroma expression based on quantitative data of volatile compounds: A case study of oak barrel-aged red wines - Mengqi Ling; Xiaoxuan Bai; Dongsheng Cui; Ying Shi; Changqing Duan; Yibin Lan (Food Research International, 2023)

Barley β-glucan inhibits digestion of soybean oil in vitro and lipid-lowering effects of digested products in cell co-culture model - Jiaying Li; Yurong Zhou; Jiayan Zhang; Ling Cui; Haina Lu; Ying Zhu; Yansheng Zhao; Songtao Fan; Xiang Xiao (Food Research International, 2023)

Efficient uranium electrochemical deposition with a functional phytic Acid-Doped Polyaniline/Graphite sheet electrode by Adsorption-electrodeposition strategy - Mengnan Huang; Lisha Xie; Yuejiao Wang; Hongjiang He; Haibiao Yu; Junshuo Cui; Xiaogeng Feng; Zhenning Lou; Ying Xiong (Chemical Engineering Journal, 2023)

Mitophagy-promoting miR-138-5p promoter demethylation inhibits pyroptosis in sepsis-associated acute lung injury - Fen Liu; Ying Yang; Wei Peng; Ning Zhao; Jiaquan Chen; Zeyao Xu; Yamei Cui; Kejian Qian (Inflammation Research, 2023)

Parthenolide inhibits proliferation of cells infected with Kaposi’s sarcoma-associated herpesvirus by suppression of the NF-κB signaling pathway - Ying Li; Huiling Xu; Xiaohua Tan; Qinghua Cui; Wenyi Gu; Zemin Pan; Lei Yang; Shuyuan Wu; Xiaolu Wang; Dongmei Li (Archives of Virology, 2023)

Numerical Investigation on the Hydrodynamic Response of Pentamaran—Resistance Analysis of Different Outrigger Inclination Angles - Pengwei Hu; Ying Cui; Chenyu Zhao; Yanan Li; Boyang Li (Journal of Marine Science and Engineering, 2023)
Due to the interference between the main hull and the outrigger of the pentamaran, resistance is greatly affected. Therefore, research on the pentamaran front outrigger inclination angle has further practical significance for reducing resistance. In this study, the pentamaran front outrigger inclination angle was analyzed by CFD method, the ship motion in waves was simulated by overlapping grid technology, and the resistance of the pentamaran in static water and waves was predicted by using the unsteady RANS equation. First, a series of validation studies were carried out for the numerical methods used in the study. Then, the influence of the front outrigger inclination angle on the pentamaran resistance performance under different working conditions is calculated and discussed. In order to analyze the influence of the change of the front outrigger inclination angle on the resistance, free surface wave-making and hull pressure are further discussed. The results show that the influence of the front outrigger inclination angle change on the resistance of the pentamaran has a certain rule, and the resistance of the pentamaran can be reduced by adjusting the front outrigger inclination angle.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Source-specific ecological risks and critical source identification of PPCPs in surface water: Comparing urban and rural areas - Yanqi Wu; Shuai Song; Xinchuang Chen; Yajuan Shi; Haotian Cui; Ying Liu; Shengjie Yang (Science of The Total Environment, 2023)

A review and evaluation of nonroad diesel mobile machinery emission control in China - Pengju Bie; Liang Ji; Huanxing Cui; Gang Li; Shunli Liu; Ying Yuan; Kebin He; Huan Liu (Journal of Environmental Sciences, 2023)

Pilot test of low-rank coal pyrolysis coupled with gasification to hydrogen-rich gas for direct reduced iron: Process modeling, simulation and thermodynamic analysis - Qian Liu; Ying-jie Zhao; Yi Huang; Feng Pei; Yang Cui; Li-juan Shi; Li-ping Chang; Qun Yi (Fuel, 2023)

Preparation, structural characterization and neuroprotective effects to against H2O2-induced oxidative damage in PC12 cells of polysaccharides from Pleurotus ostreatus - Liuya Wang; Kun Li; Yidan Cui; Haihai Peng; Ying Hu; Zhenyuan Zhu (Food Research International, 2023)

pH-dependent microbial niches succession and antibiotic resistance genes distribution in an oxygen-based membrane biofilm reactor treating greywater - Beibei Wu; Qingqing Ren; Libo Xia; Ying Liu; Xiaocai Cui; Anqi Dai; Ting Wei; Yun Zhou (Environmental Research, 2023)

Ecosystem responses of two Permian biocrises modulated by CO2 emission rates - Wen-qian Wang; Feifei Zhang; Shuang Zhang; Ying Cui; Quan-feng Zheng; Yi-chun Zhang; Dong-xun Yuan; Hua Zhang; Yi-gang Xu; Shu-zhong Shen (Earth and Planetary Science Letters, 2023)

Insight into a strategy to improve charge carrier migration in lead-free bismuth-based halide perovskite for efficient selective oxidation of thioanisole under visible light - Zihao Cui; Yaqiang Wu; Shuhui Zhang; Hui Fu; Guoqiang Chen; Zaizhu Lou; Xiaolei Liu; Qianqian Zhang; Zeyan Wang; Zhaoke Zheng; Hefeng Cheng; Yuanyuan Liu; et al. (Chemical Engineering Journal, 2023)

Lanthanum-modified polydopamine loaded Acinetobacter lwoffii DNS32 for phosphate and atrazine removal: Insights into co-adsorption and biodegradation mechanisms - Siyue Han; Yue Tao; Yunhe Cui; Jiaming Xu; Hanxun Ju; Linlin Fan; Lin Zhang; Ying Zhang (Bioresource Technology, 2023)

Impacts of mowing and N addition on soil organic phosphorus mineralization rates in a semi-natural grassland in Northeast China - Haiying Cui; Mingcai Fan; Yunbo Wang; Xiaochong Zhang; Wanling Xu; Yanan Li; Wenzheng Song; Jian-Ying Ma; Wei Sun (Plant and Soil, 2023)

Antiplatelet therapy for secondary prevention of lacunar stroke: a systematic review and network meta-analysis - Xiaowen Hou; Kaiwen Cen; Ying Cui; Yuhong Zhang; Xu Feng (European Journal of Clinical Pharmacology, 2023)

New insight into and characterization of DOC and DON for inland waterbodies in the Songnen Plain, Northeast China - Ying Zhao; Yaoping Cui (Aquatic Sciences, 2023)

Enhancement of iron-based nitrogen removal with an electric–magnetic field in an upflow microaerobic sludge reactor (UMSR) - Abdulatti Algonin; Bowei Zhao; Ying Cui; Fei Xie; Xiuping Yue (Environmental Science and Pollution Research, 2022)

Exploring the key factors affecting the seasonal variation of phytoplankton in the coastal Yellow Sea - Yingzhe Wang; Ying Liu; Xueyang Chen; Zhengguo Cui; Keming Qu; Yuqiu Wei (Frontiers in Marine Science, 2022)
Marine phytoplankton play crucial roles in the ocean’s biological pump and have great impacts on global biogeochemical cycles, yet the knowledge of environmental variables controlling their seasonal dynamics needs to be improved further, especially in the coastal ecosystems. In order to explore the determinants affecting the seasonal variation of phytoplankton, here we conducted three surveys during spring, summer and autumn along the coastal Yellow Sea. Among the phytoplankton community, 49 species of diatoms and 9 species of dinoflagellates were observed in spring, 63 species of diatoms and 10 species of dinoflagellates in summer, and 62 species of diatoms and 11 species of dinoflagellates in autumn. These results thus suggested that there were obvious differences in the number of species across the three seasons, of which diatoms were the most diverse group, followed by dinoflagellates. Additionally, diatoms were the most dominant species of the phytoplankton community and varied largely during different seasons. According to the redundancy analysis, the abundance of phytoplankton community was mainly related to water temperature and dissolved inorganic nitrogen (DIN) during the three seasons, indicating that water temperature and DIN could be the key factors controlling the seasonal variability of phytoplankton community along the coastal Yellow Sea. Also, significant correlations were observed between phytoplankton abundance and heavy metals Zn, As, and Hg during the three seasons, suggesting that these metals also had potential influences on the seasonal dynamics of phytoplankton community in the coastal Yellow Sea.

Therapeutic Effects of Human Pluripotent Stem Cell-Derived Mesenchymal Stem Cells on a Murine Model of Acute Type-2-Dominated Airway Inflammation - Si-Yuan Ma; Ning Zhao; Lele Cui; Ying Li; Hang Zhang; Jing Wang; Jie Pang; Ming Wang; Chengshuo Wang; Sun Ying; Zi-Bing Jin; Luo Zhang (Stem Cell Reviews and Reports, 2022)

Correction to: Genome sequencing of Colletotrichum gloeosporioides ES026 reveals plausible pathway of HupA - Haiyang Xia; Hamza Armghan Noushahi; Aamir Hamid Khan; Ying Liu; Andreea Cosoveanu; Lingli Cui; Jing Tang; Shehzad Iqbal; Shaohua Shu (Molecular Biology Reports, 2022)

Genome sequencing of Colletotrichum gloeosporioides ES026 reveals plausible pathway of HupA - Haiyang Xia; Hamza Armghan Noushahi; Aamir Hamid Khan; Ying Liu; Andreea Cosoveanu; Lingli Cui; Jing Tang; Shehzad Iqbal; Shaohua Shu (Molecular Biology Reports, 2022)

Pollution Characteristics, Sources, and Health Risk Assessments of Potentially Toxic Elements in Community Garden Soil of Lin’an, Zhejiang, China - Yue Yan; Rongrong Chen; Hexian Jin; Gul Rukh; Ying Wang; Shiyu Cui; Dan Liu (Bulletin of Environmental Contamination and Toxicology, 2022)

An Efficient Strategy for Enhancing Glucose Recovery of Wheat Straw by Ionic Liquid Combined Ball Milling Pretreatment - Ying Sui; Yu Cui; Yuanxiu Wang; Yiming Zhao; Guoxin Sun (BioEnergy Research, 2022)

Transcriptomic Analysis Provides Insights into Microplastic and Heavy Metal Challenges in the Line Seahorse (Hippocampus erectus) - Ying Liu; Dongwei Shang; Yanjing Yang; Pei Cui; Jinhui Sun (Fishes, 2022)
Microplastics (MPs) are ubiquitous pollutants that have potentially harmful and toxic effects. MPs are frequently ingested by aquatic animals, as microplastics share a similar size and color to their food. Heavy metals are harmful and difficult to degrade, have a wide range of sources and an extended residual time from exposure to recovery. Although the effects of MPs and heavy metals on the performance of aquatic species have been extensively studied, the molecular mechanisms of MP and heavy metal (Pb, Cd and Cu) exposure on aquatic organisms remain unclear. Here, the effects of MPs and heavy metal accumulation on the line seahorse, Hippocampus erectus, were investigated at the molecular level using transcriptome analysis. Using gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses, we found that immune, metabolic, and apoptotic pathways were affected in the heavy metal group, whereas the DNA damage repair and metabolism pathways were mainly involved in the MP group. Both types of stress caused significant changes in the genes related to the antioxidant pathway in H. erectus larvae. Transcriptome differences between the treatment groups were analyzed, and sensitive candidate genes (Hsp70, Hsp90, Sod, etc.) were screened. The response characteristics of seahorses to MP environmental stress were also investigated. Using seahorse as a biological model and candidate sensitive genes as a basis, our results provide a theoretical basis for detecting MPs and heavy metals pollution in coastal areas.

Two novel amide alkaloids from Portulaca oleracea L. and their anti-inflammatory activities - Xiujuan Lan; Ziyue Ying; Shengnan Guo; Yang Duan; Xinyu Cui; Aijing Leng; Xixiang Ying (Natural Product Research, 2022)

Saline-alkali stress reduces soil bacterial community diversity and soil enzyme activities - Dihe Yang; Lu Tang; Ying Cui; Jiaxin Chen; Lei Liu; Changhong Guo (Ecotoxicology, 2022)

Bioaccumulation of contaminants in wild seahorses collected from coastal China - Ying Liu; Dongwei Shang; Yanjing Yang; Pei Cui; Jinhui Sun (Frontiers in Marine Science, 2022)
Eighty-four wild seahorses, including three of China’s dominant species, were collected from seven coastal provinces to evaluate their common contaminant contents. Heavy metals (including Cu, Pb, Cd, Cr, and Hg), Benzo(a)pyrene (B[a]P), and microplastics were detected in the collected seahorses. The results indicate that considerable contamination variations are present in seahorses from different regions and species. Elevated concentrations of Cu and Cr, compared to other heavy metals, were observed in most sampled locations. In addition, B[a]P concentrations were far greater in Hippocampus mohnikei and H.trimaculatus compared with H.kelloggi ( P < 0.05). Substantial changes in microplastic concentrations were also observed in seahorses from different locations, and significant differences were observed between sampled species ( P < 0.05). Further, a correlation analysis obtained strong correlations among four heavy metals (Cu, Pb, Cd, and Cr), except Hg. A significant correlation was identified between B[a]P and microplastics ( P < 0.01), suggesting potential synergistic effects between these two contaminants. In brief, this study indicates that wild seahorse populations are experiencing environmental pollution.

Reading-related Brain Function Restored to Normal After Articulation Training in Patients with Cleft Lip and Palate: An fMRI Study - Liwei Sun; Wenjing Zhang; Mengyue Wang; Songjian Wang; Zhen Li; Cui Zhao; Meng Lin; Qian Si; Xia Li; Ying Liang; Jing Wei; Xu Zhang; et al. (Neuroscience Bulletin, 2022)

LncRNA ZFAS1 regulates the hippocampal neurons injury in epilepsy through the miR-15a-5p/OXSR1/NF-κB pathway - Zengmian Wang; Zhimin Na; Ying Cui; Chunjie Wei; Shuqiu Wang (Metabolic Brain Disease, 2022)

Metabolic changes of the reduction of manganese intake in the hepatic encephalopathy rat: NMR- and MS-based metabolomics study - Jingjing Lu; Ying Li; Cui Zhang; Xiuying Yang; Jinwei Qiang (BioMetals, 2022)

Intensity, frequency and rate of insect herbivory for an alpine Rhododendron shrub: elevational patterns and leaf-age effects - Guangshuai Cui; Lin Zhang; Wei Shen; Ying Guo; Eryuan Liang (Alpine Botany, 2022)

A new alkaloid from Portulaca oleracea L. and its anti-inflammatory activity - Fangxuan Liu; Xinyu Cui; Yang Duan; Shengnan Guo; Jinpeng Liu; Xixiang Ying (Natural Product Research, 2022)

Polygenic control of the wavy coat of the NCT mouse: involvement of an intracisternal A particle insertional mutation of the protease, serine 53 (Prss53) gene, and a modifier gene - Masayuki Mori; Chang Liu; Takahiro Yoshizawa; Hiroki Miyahara; Jian Dai; Yuichi Igarashi; Xiaoran Cui; Ying Li; Xiaojing Kang; Keiichi Higuchi (Mammalian Genome, 2022)

Particle breakage mechanism and particle shape evolution of calcareous sand under impact loading - Xing Wang; Ying Wang; Cheng Liao; Jie Cui; Jian-Hua Shen; Xin-Zhi Wang; Chang-Qi Zhu (Bulletin of Engineering Geology and the Environment, 2022)

Dyadobacter diqingensis sp. nov., isolated from Baima snow mountain of Diqing Tibetan Autonomous Prefecture in Yunnan province, south-west China - Lei Ran; Man Peng; Wei-Qun Wang; Yu-Zhou Feng; Juan Wang; Yu Wang; Cui-Ying Li; Xin-Xing Liu; Wei-Xun Chunyu; Shu-Kun Tang (Archives of Microbiology, 2022)

Source Characteristics and Path Attenuation for the Yangbi, China Seismic Sequence in 2021 - Ying Zhou; Hongwei Wang; Ruizhi Wen; Tianming Miao; Jianwen Cui (Pure and Applied Geophysics, 2022)

Microalgae cell disruption and lipid composition and recovery improvements induced by algicidal effects of bacteria - Chunfang Deng; Yan Cui; Ying Liu (Journal of Applied Phycology, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Trachyte reservoir characteristics and favorable reservoir identification and prediction in the J34 block, Eastern Sag - Chenglong Ma; Ying Wu; Tuan Gu; Bin Zhang; Yu Gang Li; Ying Jie Zhang; Wen Bo Dong; Jie Cui (Acta Geophysica, 2022)

Research on garden landscape reconstruction based on geographic information system under the background of deep learning - Ying Cui (Acta Geophysica, 2022)

Making comparable measurements of bacterial respiration and production in the subtropical coastal waters - Cui Guo; Ying Ke; Bingzhang Chen; Shuwen Zhang; Hongbin Liu (Marine Life Science & Technology, 2022)
Accurate estimates of bacterial carbon metabolic rates are indispensable for understanding the regulation of carbon fluxes in aquatic environments. Here, changes in bacterial growth, production, and cell volume in both pre-filtered and unfiltered seawater during 24 h incubation were monitored. The methodological artifacts during Winkler bacterial respiration (BR) measurements in subtropical Hong Kong coastal waters were assessed. Bacterial abundance increased by 3- and 1.8-fold in the pre-filtered and unfiltered seawater after incubation, respectively. Bacterial production (BP) and cell volume also showed significant enhancement. Compared with the BR measurements obtained by the Winkler method, the instantaneous free-living BR measurements, after correction, decreased by ~ 70%. The time-integrated free-living BR and BP during 24 h incubation in the pre-filtered sample provided an improved estimate of bacterial growth efficiency, which increased by ~ 52% compared to the common estimations using the noncomparable measurements of integrated free-living BR and instantaneous total BP. The overestimation of BR also exaggerated the contribution of bacteria to community respiration, affecting the understanding on the metabolic state of the marine ecosystems. Furthermore, the BR estimates by the Winkler method may be more biased in environments with a higher bacterial growth rate and tightly coupled grazing mortality, as well as in those with higher nutrient concentrations. These results reveal obvious problems associated with the BR methodology and raise a warning for caution when comparing BP and BR, as well as when making estimations of carbon flow through the complex microbial networks in aquatic ecosystems.

Correction to: GLP-1 Receptor Agonist Inhibited the Activation of RIPK1 for Alleviation the Neuronal Death and Neuroinfammation in APP/PS1 Mice - Xiaodong Kong; Yuting Yang; Huijie Li; Weiyun Cui; Xiaohui Wu; Min Gong; Ying Li (International Journal of Peptide Research and Therapeutics, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Manure fertilization enhanced microbial immigration in the wheat rhizosphere - Ye Liu; Shuikuan Bei; Oladele Olatunde; Ying Li; Xingjie Wu; Hongyan Zhang; Zhenling Cui; Christopher Rensing; Jingjing Peng (Journal of Soils and Sediments, 2022)

Effect of electronic cigarette and tobacco smoking on the human saliva microbial community - Xue Wang; Qili Mi; Ji Yang; Ying Guan; Wanli Zeng; Haiying Xiang; Xin Liu; Wenwu Yang; Guangyu Yang; Xuemei Li; Yinshan Cui; Qian Gao (Brazilian Journal of Microbiology, 2022)

Late Cambrian tonalite-trondhjemite association in the eastern segment of North Qilian suture zone: petrogenesis and geodynamic implications - Yuxiao Chen; Ying Cui; Shuguang Song; Shanming Fu; Lipeng Zhang; Weidong Sun; Tangfu Xiao (International Geology Review, 2022)

Antibiotic resistomes in water supply reservoirs sediments of central China: main biotic drivers and distribution pattern - Kai Zhang; Kuangjia Li; Rui Xin; Ya Han; Ziwei Guo; Wei Zou; Wei Wei; Xiangchao Cui; Zhongshuai Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Stable Isotopes Reveal Water Vapor Sources of Precipitation over the Jiaolai Plain, Shandong Peninsula, China - Ying Wang; Bu-li Cui; Dong-sheng Li; Ya-xuan Wang; Wan-xin Yu; He-hua Zong (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Pyramidal and conditional convolution attention network for hyperspectral image classification using limited training samples - Zikun Yu; Ying Cui; Chao Shao; Shan Gao; Chao Wang (International Journal of Remote Sensing, 2022)

Migration and Deposition Characteristics of Particles in Sand Layers with Fluctuating Water Levels - Xianze Cui; Tao Wen; Jin Li; Dazhou Wu; Yong Fan; Ying Jin; Siyuan He; Yucong Pan (Water, Air, & Soil Pollution, 2022)

Phosphorus addition regulates the responses of soil multifunctionality to nitrogen over-fertilization in a temperate grassland - Haiying Cui; Wei Sun; Manuel Delgado-Baquerizo; Wenzheng Song; Jian-Ying Ma; Keying Wang; Xiaoli Ling (Plant and Soil, 2022)

Norovirus detection in wastewater and its correlation with human gastroenteritis: a systematic review and meta-analysis - Yue Huang; Nan Zhou; Shihan Zhang; Youqin Yi; Ying Han; Minqi Liu; Yue Han; Naiyang Shi; Liuqing Yang; Qiang Wang; Tingting Cui; Hui Jin (Environmental Science and Pollution Research, 2022)

Bibliometric Review of Biodiversity Offsetting During 1992–2019 - Shuling Yu; Baoshan Cui; Chengjie Xie; Ying Man; Jing Fu (Chinese Geographical Science, 2022)

miR-1290 promotes IL-8-mediated vascular endothelial cell adhesion by targeting GSK-3β - Hongxin Xu; Ying Cui; Xianwei Liu; Xiao Zheng; Jiaqing Liu; Xinxin Hu; Fuhua Gao; Xiaoyan Hu; Mei Li; Xiaoqing Wei; Ying Gao; Ying Zhao (Molecular Biology Reports, 2022)

HTRPCA: Hypergraph Regularized Tensor Robust Principal Component Analysis for Sample Clustering in Tumor Omics Data - Yu-Ying Zhao; Cui-Na Jiao; Mao-Li Wang; Jin-Xing Liu; Juan Wang; Chun-Hou Zheng (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Cellular Apoptosis Induced by Deoxynivalenol - Qing’ai Chen; Ying Cui; Jiaru Zhao; Wanlin Zeng; Ni Jin; Lan Yang; Jun Yuan (Indian Journal of Microbiology, 2022)

Isofraxidin exerts anti-diabetic, antilipidemic, and antioxidant effects and protects renal tissues via inhibition of NF-ĸB in Streptozotocin-induced diabetic rats - Wei Lu; Ying Cui; Lili Zhang (Molecular & Cellular Toxicology, 2022)

NtCycB2 negatively regulates tobacco glandular trichome formation, exudate accumulation, and aphid resistance - Zhaojun Wang; Xiaoxiao Yan; Hongying Zhang; Ying Meng; Yang Pan; Hong Cui (Plant Molecular Biology, 2022)

Germ plasm and the origin of the primordial germ cells in the oriental river prawn Macrobrachium nipponense - Ying Chen; Xiang Fang; Xiao-Qing Tian; Zheng Cui; Hai-Yang Feng; Gao-Feng Qiu (Cell and Tissue Research, 2021)

The expression of diacylglycerol kinase isoforms α and ζ correlates with the progression of experimental autoimmune encephalomyelitis in rats - Huilin Cui; Yige Huang; Ying Wu; Jinfeng Ma; Ximei Cao; Jianshan Xie; Yu Zhang (Histochemistry and Cell Biology, 2021)

Comparison of the Bulk and Rhizosphere Soil Prokaryotic Communities Between Wild and Reintroduced Manglietiastrum sinicum Plants, a Threatened Species with Extremely Small Populations - Dai-Fa Su; Qing-Qing Shen; Jun-Yu Yang; Zhi-Ying Li; Wei Xiao; Yong-Xia Wang; Zhang-Gui Ding; Xiao-Long Cui (Current Microbiology, 2021)

Induced production of a new polyketide in Penicillium sp. HS-11 by chemical epigenetic manipulation - You-Min Ying; Ling Li; Hang-Fei Yu; Yi-Lian Xu; Lu Huang; Wei Mao; Cui-Ping Tong; Zhi-Dong Zhang; Zha-Jun Zhan; Yun Zhang (Natural Product Research, 2021)

A cross-sectional study of chemotherapy-related AKI - Xin Kang; Xizi Zheng; Damin Xu; Tao Su; Ying Zhou; Jing Ji; Qi Yu; Yimin Cui; Li Yang (European Journal of Clinical Pharmacology, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

Transient silencing of VvCSN5 enhances powdery mildew resistance in grapevine (Vitis vinifera) - Kai-Cheng Cui; Min Liu; Gui-Hua Ke; Xing-Yuan Zhang; Bo Mu; Min Zhou; Yang Hu; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

GLP-1 Receptor Agonist Inhibited the Activation of RIPK1 for Alleviation the Neuronal Death and Neuroinflammation in APP/PS1 Mice - Xiaodong Kong; Yuting Yang; Huijie Li; Weiyun Cui; Xiaohui Wu; Min Gong; Ying Li (International Journal of Peptide Research and Therapeutics, 2021)

Complex analysis of the personalized pharmacotherapy in the management of COVID-19 patients and suggestions for applications of predictive, preventive, and personalized medicine attitude - Lei-Yun Wang; Jia-Jia Cui; Qian-Ying OuYang; Yan Zhan; Yi-Min Wang; Xiang-Yang Xu; Lu-Lu Yu; Hui Yin; Yang Wang; Chen-Hui Luo; Cheng-Xian Guo; Ji-Ye Yin (EPMA Journal, 2021)
Aims Coronavirus disease 2019 (COVID-19) is rapidly spreading worldwide. Drug therapy is one of the major treatments, but contradictory results of clinical trials have been reported among different individuals. Furthermore, comprehensive analysis of personalized pharmacotherapy is still lacking. In this study, analyses were performed on 47 well-characterized COVID-19 drugs used in the personalized treatment of COVID-19. Methods Clinical trials with published results of drugs use for COVID-19 treatment were collected to evaluate drug efficacy. Drug-to-Drug Interactions (DDIs) were summarized and classified. Functional variations in actionable pharmacogenes were collected and systematically analysed. “Gene Score” and “Drug Score” were defined and calculated to systematically analyse ethnicity-based genetic differences, which are important for the safer use of COVID-19 drugs. Results Our results indicated that four antiviral agents (ritonavir, darunavir, daclatasvir and sofosbuvir) and three immune regulators (budesonide, colchicine and prednisone) as well as heparin and enalapril could generate the highest number of DDIs with common concomitantly utilized drugs. Eight drugs (ritonavir, daclatasvir, sofosbuvir, ribavirin, interferon alpha-2b, chloroquine, hydroxychloroquine (HCQ) and ceftriaxone had actionable pharmacogenomics (PGx) biomarkers among all ethnic groups. Fourteen drugs (ritonavir, daclatasvir, prednisone, dexamethasone, ribavirin, HCQ, ceftriaxone, zinc, interferon beta-1a, remdesivir, levofloxacin, lopinavir, human immunoglobulin G and losartan) showed significantly different pharmacogenomic characteristics in relation to the ethnic origin of the patient. Conclusion We recommend that particularly for patients with comorbidities to avoid serious DDIs, the predictive, preventive, and personalized medicine (PPPM, 3 PM) strategies have to be applied for COVID-19 treatment, and genetic tests should be performed for drugs with actionable pharmacogenes, especially in some ethnic groups with a higher frequency of functional variations, as our analysis showed. We also suggest that drugs associated with higher ethnic genetic differences should be given priority in future pharmacogenetic studies for COVID-19 management. To facilitate translation of our results into clinical practice, an approach conform with PPPM/3 PM principles was suggested. In summary, the proposed PPPM/3 PM attitude should be obligatory considered for the overall COVID-19 management.

Local climate adaptation and gene flow in the native range of two co‐occurring fruit moths with contrasting invasiveness - Li‐Jun Cao; Bing‐Yan Li; Jin‐Cui Chen; Jia‐Ying Zhu; Ary A. Hoffmann; Shu‐Jun Wei (Molecular Ecology, 2021)
Invasive species pose increasing threats to global biodiversity and ecosystems. While previous studies have characterized successful invaders based on ecological traits, characteristics related to evolutionary processes have rarely been investigated. Here we compared gene flow and local adaptation using demographic analyses and outlier tests in two co‐occurring moth pests across their common native range of China, one of which (the peach fruit moth, Carposina sasakii ) has maintained its native distribution, while the other (the oriental fruit moth, Grapholita molesta ) has expanded its range globally during the past century. We found that both species showed a pattern of genetic differentiation and an evolutionary history consistent with a common southwestern origin and northward expansion in their native range. However, for the noninvasive species, genetic differentiation was closely aligned with the environment, and there was a relatively low level of gene flow, whereas in the invasive species, genetic differentiation was associated with geography. Genome scans indicated stronger patterns of climate‐associated loci in the noninvasive species. While strong local adaptation and reduced gene flow across its native range may have decreased the invasiveness of C . sasakii , this requires further validation with additional comparisons of invasive and noninvasive species across their native range.

Gut Microbial Metabolites in Parkinson’s Disease: Implications of Mitochondrial Dysfunction in the Pathogenesis and Treatment - Yixuan Liang; Li Cui; Jiguo Gao; Mingqin Zhu; Ying Zhang; Hong-Liang Zhang (Molecular Neurobiology, 2021)
The search for therapeutic targets for Parkinson’s disease (PD) is hindered by the incomplete understanding of the pathophysiology of the disease. Mitochondrial dysfunction is an area with high potential. The neurobiological signaling connections between the gut microbiome and the central nervous system are incompletely understood. Multiple lines of evidence suggest that the gut microbiota participates in the pathogenesis of PD. Gut microbial dysbiosis may contribute to the loss of dopaminergic neurons through mitochondrial dysfunction. The intervention of gut microbial metabolites via the microbiota-gut-brain axis may serve as a promising therapeutic strategy for PD. In this narrative review, we summarize the potential roles of gut microbial dysbiosis in PD, with emphasis on microbial metabolites and mitochondrial function. We then review the possible ways in which microbial metabolites affect the central nervous system, as well as the impact of microbial metabolites on mitochondrial dysfunction. We finally discuss the possibility of gut microbiota as a therapeutic target for PD.

MR T1 mapping for quantifying brain manganese deposition in type C hepatic encephalopathy rats - Cui Zhang; Ying Li; Jingjing Lu; Xiuying Yang; Jie Wang; Jinwei Qiang (BioMetals, 2021)

Development of highly efficient and reusable magnetic nitrogen-doped carbon nanotubes for chlorophenol removal - Xue Zhang; Chunyue Cui; Qingzhu Zheng; Ying Wang; Jing Chang; Shuxian Wang (Environmental Science and Pollution Research, 2021)

Eutrophication regulation of Wuxing Lake based on eco-dynamics model - Feng Gao; Hong Cui; Suiju Lv; Ying Qiao (Arabian Journal of Geosciences, 2021)

Occurrence and cycle of dimethyl sulfide in the western Pacific Ocean - Feng Xu; Shi‐Bo Yan; Hong‐Hai Zhang; Ying‐Cui Wu; Qian‐Yao Ma; Yu‐Chen Song; Guang‐Chao Zhuang; Gui‐Peng Yang (Limnology and Oceanography, 2021)
Oceanic production and occurrence of dimethyl sulfide (DMS) and its subsequent ventilation to the atmosphere significantly contribute to the global sulfur cycle and impact the climate regulation. Spatial distributions of DMS, dimethylsulfoniopropionate (DMSP, precursor of DMS), and dimethyl sulfoxide (DMSO, oxidation product of DMS), production and removal processes of DMS (including biological production, microbial consumption, photo‐degradation, and sea‐to‐air exchange), and biogenic contributions to the atmospheric sulfate burden were simultaneously studied in the western Pacific Ocean during winter. Sea surface DMS, DMSP, and DMSO were strongly correlated and had similar distribution patterns. The DMS photo‐degradation efficiency ratio (normalized using incident photon flux density) for ultraviolet B radiation (UVB): ultraviolet A radiation (UVA): photosynthetically active radiation (PAR) was 391: 36: 1. However, considering the solar spectral composition, the actual contributions of UVB, UVA, and PAR to DMS photo‐degradation in surface waters were 40.6% ± 10.7%, 41.2% ± 15.6%, and 18.2% ± 7.2%, respectively. When integrated across the entire mixed layer, UVA and PAR became the dominant drivers, accounting for 45.2% ± 18.0% and 38.0% ± 17.3% of DMS photo‐degradation, respectively, as UVB was significantly attenuated in seawater. The DMS budget of the entire mixed layer indicated that microbial consumption, photo‐degradation, and ventilation accounted for about 74.3% ± 11.9%, 19.3% ± 9.3%, and 6.5% ± 4.0% of total DMS removal, respectively. Even if ventilation was a minor DMS removal pathway, DMS emissions still contributed approximately 45.2% ± 25.6% of the atmospheric non‐sea‐salt sulfate burden over the western Pacific Ocean.

Petrogenesis and tectonic implications of cambrian Nb-enriched I- and aluminous A-type granites in the North Qilian suture zone - Yuxiao Chen; Ying Cui; Shuguang Song; Kai Wu; Weidong Sun; Tangfu Xiao (International Geology Review, 2021)

Physical Modelling of Offshore Wind Turbine Foundations for TRL (Technology Readiness Level) Studies - Subhamoy Bhattacharya; Domenico Lombardi; Sadra Amani; Muhammad Aleem; Ganga Prakhya; Sondipon Adhikari; Abdullahi Aliyu; Nicholas Alexander; Ying Wang; Liang Cui; Saleh Jalbi; Vikram Pakrashi; et al. (Journal of Marine Science and Engineering, 2021)
Offshore wind turbines are a complex, dynamically sensitive structure due to their irregular mass and stiffness distribution, and complexity of the loading conditions they need to withstand. There are other challenges in particular locations such as typhoons, hurricanes, earthquakes, sea-bed currents, and tsunami. Because offshore wind turbines have stringent Serviceability Limit State (SLS) requirements and need to be installed in variable and often complex ground conditions, their foundation design is challenging. Foundation design must be robust due to the enormous cost of retrofitting in a challenging environment should any problem occur during the design lifetime. Traditionally, engineers use conventional types of foundation systems, such as shallow gravity-based foundations (GBF), suction caissons, or slender piles or monopiles, based on prior experience with designing such foundations for the oil and gas industry. For offshore wind turbines, however, new types of foundations are being considered for which neither prior experience nor guidelines exist. One of the major challenges is to develop a method to de-risk the life cycle of offshore wind turbines in diverse metocean and geological conditions. The paper, therefore, has the following aims: (a) provide an overview of the complexities and the common SLS performance requirements for offshore wind turbine; (b) discuss the use of physical modelling for verification and validation of innovative design concepts, taking into account all possible angles to de-risk the project; and (c) provide examples of applications in scaled model tests.

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

Distinct roles of alternative oxidase pathway during the greening process of etiolated algae - Ying Liu; Hua Zhang; Yan Cui; Yanli Zheng; Hui Chen; Zhangli Hu; Qingyu Wu (Science China Life Sciences, 2021)

High-resolution estimation of ambient sulfate concentration over Taiwan Island using a novel ensemble machine-learning model - Lulu Cui; Qingwei Ma; Rui Li; Hongbo Fu; Ziyu Zhang; Liwu Zhang; Ying Chen (Environmental Science and Pollution Research, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

Non-linear relationships and interactions of meteorological factors on mumps in Jinan, China - Shaoqian Lin; Shiman Ruan; Xingyi Geng; Kaijun Song; Liangliang Cui; Xiaoxue Liu; Yingjian Zhang; Meng Cao; Ying Zhang (International Journal of Biometeorology, 2021)

Graphene oxide affects growth and physiological indexes in Larix olgensis seedlings and the soil properties of Haplic Cambisols in Northeast China - Jinfeng Song; Na Luo; Ying Sang; Chengwei Duan; Xiaoyang Cui (Environmental Science and Pollution Research, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Stable isotopes and chloride ion of precipitation events in the northeastern Tibetan Plateau, China - Bu-li Cui; Dong-sheng Li; Bao-fu Jiang; Ying Wang; Ya-xuan Wang; Long-sheng Wang; Xiao-yan Li (Journal of Mountain Science, 2021)

In vitro antifungal susceptibility of Sporothrix globosa isolates from Jilin Province, northeastern China: comparison of yeast and mycelial phases - Yang Song; Shanshan Li; Ying Shi; Lipei Zhao; Yu Cui; Lei Yao; Yu Zhen; Ruili Chen; Yan Cui (Brazilian Journal of Microbiology, 2021)

MicroRNA-520c-3p suppresses vascular endothelium dysfunction by targeting RELA and regulating the AKT and NF-κB signaling pathways - Yan Jiao; Dandan Zhao; Fuhua Gao; Xiaoyan Hu; Xinxin Hu; Mei Li; Ying Cui; Xiaoqing Wei; Ce Xie; Ying Zhao; Ying Gao (Journal of Physiology and Biochemistry, 2021)

Detection and genetic characteristics of porcine bocavirus in central China - Lan-Lan Zheng; Jian-Tao Cui; Han Qiao; Xin-Sheng Li; Xiao-Kang Li; Hong-Ying Chen (Archives of Virology, 2021)

Connexin 36 Mediates Orofacial Pain Hypersensitivity Through GluK2 and TRPA1 - Qian Li; Tian-Le Ma; You-Qi Qiu; Wen-Qiang Cui; Teng Chen; Wen-Wen Zhang; Jing Wang; Qi-Liang Mao-Ying; Wen-Li Mi; Yan-Qing Wang; Yu-Xia Chu (Neuroscience Bulletin, 2020)

Contrasting effects of N fertilization and mowing on ecosystem multifunctionality in a meadow steppe - Haiying Cui; Wei Sun; Manuel Delgado-Baquerizo; Wenzheng Song; Jian-Ying Ma; Keying Wang; Xiaoli Ling (Soil Ecology Letters, 2020)

The Effect of Iodine-Containing Vitamin Supplementation During Pregnancy on Thyroid Function in Late Pregnancy and Postpartum Depression in an Iodine-Sufficient Area - Zixiao Wang; Chenyang Li; Ying Teng; Yunping Guan; Li Zhang; Xi Jia; Dandan Cui; Jing Li; Haixia Guan (Biological Trace Element Research, 2020)

Development and establishment of a QuEChERS-based extraction method for determining tembotrione and its metabolite AE 1417268 in corn, corn oil and certain animal-origin foods by HPLC-MS/MS - Kai Cui; Xiaohu Wu; Lusheng Zhu; Ying Zhang; Gaochen Dai; Junli Cao; Jun Xu; Fengshou Dong; Xingang Liu; Yongquan Zheng (Food Additives & Contaminants: Part A, 2020)

Characteristics of the spike and ORF3 genes of porcine epidemic diarrhea virus in Henan and Shanxi provinces of China - Jian-tao Cui; Han Qiao; Cheng-yao Hou; Hui-Hua Zheng; Xin-Sheng Li; Lan-lan Zheng; Hong-Ying Chen (Archives of Virology, 2020)

The Variation of Growth Rate, Photosynthetic Activity, and Biodiesel Productivity in Synechocystis sp. PCC 6803 under Antibiotic Exposure - Mengwen Cui; Ying Liu; Jian Zhang (BioEnergy Research, 2020)

Sulfamethoxazole and tetracycline induced alterations in biomass, photosynthesis, lipid productivity, and proteomic expression of Synechocystis sp. PCC 6803 - Mengwen Cui; Ying Liu; Jian Zhang (Environmental Science and Pollution Research, 2020)

The COVID-19 Vaccine Race: Challenges and Opportunities in Vaccine Formulation - Jieliang Wang; Ying Peng; Haiyue Xu; Zhengrong Cui; Robert O. Williams (AAPS PharmSciTech, 2020)

New glycosylsphingolipids from Psychotria serpens L - Yu-Mei Wang; Ai-Zhi Wu; Ying Zhong; Guang-Tian Peng; Qian Fan; Chen-Chen Zhu; Cui-Xian Zhang (Natural Product Research, 2020)

Accumulation of Cu, Cd, Pb, Zn and total P from synthetic stormwater in 30 bioretention plants - Ying Mei; Hang Zhou; Long Gao; Yi-Ming Zuo; Kun-Hao Wei; Na-Qi Cui (Environmental Science and Pollution Research, 2020)

Influence of Soil Properties and Aging on Antimony Toxicity for Barley Root Elongation - Peng Zhang; Tong-Liang Wu; Syed Tahir Ata-Ul-Karim; Yuan-Ying Ge; Xu Cui; Dong-Mei Zhou; Yu-Jun Wang (Bulletin of Environmental Contamination and Toxicology, 2020)

The nucleic acid positive rate and genotype distribution of human cytomegalovirus in human milk banks in China - Xiaoyu Min; Lin Wang; Aili Cui; Chunli Zhang; Dan Wang; Ying Liu; Zhenghong Li; Wenbo Xu (Archives of Virology, 2020)

SsHKT1;1 is coordinated with SsSOS1 and SsNHX1 to regulate Na+ homeostasis in Suaeda salsa under saline conditions - Wen-Ying Wang; Ya-Qi Liu; Hui-Rong Duan; Xiu-Xia Yin; Yan-Nong Cui; Wei-Wei Chai; Xin Song; Timothy J. Flowers; Suo-Min Wang (Plant and Soil, 2020)

Effects of different light conditions on the retinal microstructure and ultrastructure of Dicentrarchus labrax larvae - Hongwei Yan; Qi Liu; Xufang Shen; Wenlei Liu; Xin Cui; Pengfei Hu; Zhen Yuan; Lei Zhang; Changbin Song; Lili Liu; Ying Liu (Fish Physiology and Biochemistry, 2020)

Ceria oxide nanoparticle-based diffusive gradients in thin films for in situ measurement of dissolved reactive phosphorus in waters and sewage sludge - Feng Tan; Yi Wang; Yan Wang; Suyu Ren; Ying Cui; Dongyan Xu (Environmental Science and Pollution Research, 2020)

Amyloid precursor protein regulates 5-fluorouracil resistance in human hepatocellular carcinoma cells by inhibiting the mitochondrial apoptotic pathway - Xiao-long Wu; Ying Chen; Wen-cui Kong; Zhong-quan Zhao (Journal of Zhejiang University-SCIENCE B, 2020)

GPR based RTM imaging technology for estimating rhizome diameters and application in the western China mining area - Fan Cui; Shuai Li; Jiong-Xuan Yuan; Jie-Bin Bai; Yu-Xuan Zhao; Ying-Ging Zhou (Applied Geophysics, 2020)

Identification of a novel COL4A5 mutation in the proband initially diagnosed as IgAN from a Chinese family with X-linked Alport syndrome - Zhihui Li; Peng Zhu; Hui Huang; Ying Pan; Peng Han; Huanhuan Cui; Zhijuan Kang; Mai Xun; Yi Zhang; Saijun Liu; Jian Wang; Jing Wu (Science China Life Sciences, 2019)

Newer and select maize, wheat, and rice varieties can help mitigate N footprint while producing more grain - Hao Ying; Yulong Yin; Huifang Zheng; Yingcheng Wang; Qingsong Zhang; Yanfang Xue; Darko Stefanovski; Zhenling Cui; Zhengxia Dou (Global Change Biology, 2019)
Sustainably feeding the growing population amid a changing climate and dwindling resources is a grand challenge facing mankind. Decades‐long advancement in crop breeding has progressively elevated yield potential, markedly enhancing global food production capacity. However, relevant impact on reactive N (Nr) emissions associated with crop variety improvement has not been explicitly described. Here, we report multitiered evidence that newer and select maize, wheat, and rice varieties developed in China have the capacity to substantially lower Nr losses while producing more grain. First, we pooled studies featuring side‐by‐side comparison of different varieties, totaling 269 paired observations, to demonstrate that collectively, relatively newer varieties of maize, wheat, and rice had less Nr emissions (9.6%–23.5%) while yielding more grains (7.3%–11.2%) compared to older varieties under wide‐ranging conditions. Next, we built an extended database (142 field studies with 833 observations) and comprehensively evaluated the Nr‐loss reduction potential of newer varieties (2000 and after) versus older ones (1985–1999). We found that newer varieties had Nr emission factors (N loss as a percentage of N applied after correcting for background emissions) 18.2%–75.7% less for N 2 O, 18.3%–75.7% less for , and −8.5% to 22.8% less for NH 3 , while producing more grains (16.0%–24.4%). Individual varieties differed markedly in yield‐emission scores. A nationwide farmer survey (2.47 million responses) indicated tremendous opportunities for a new way of management intervention. Coupling variety selection with sound N and other agronomic management can help lower N footprint while producing more grain.

An integrated strategy to identify genes responsible for sesquiterpene biosynthesis in turmeric - Jingru Sun; Guanghong Cui; Xiaohui Ma; Zhilai Zhan; Ying Ma; Zhongqiu Teng; Wei Gao; Yanan Wang; Tong Chen; Changjiangsheng Lai; Yujun Zhao; Jinfu Tang; et al. (Plant Molecular Biology, 2019)

Growth and survival of Takifugu rubripes larvae cultured under different light conditions - Qi Liu; Hongwei Yan; Pengfei Hu; Wenlei Liu; Xufang Shen; Xin Cui; Yumeng Wu; Zhen Yuan; Lei Zhang; Yanxiang Zhang; Changbin Song; Ying Liu (Fish Physiology and Biochemistry, 2019)

Fipronil induces apoptosis and cell cycle arrest in porcine oocytes during in vitro maturation - Wenjun Zhou; Ying-Jie Niu; Zheng-Wen Nie; Yong-Han Kim; Kyung-Tae Shin; Jing Guo; Xiang-Shun Cui (Apoptosis, 2019)

Analysis of josamycin in three kinds of feed using ultra high performance liquid chromatography with tandem mass spectrometry - Jin Han; Weidong Jin; Zhenzhou Wu; Ying Shi; Fengyue Cui (Food Additives & Contaminants: Part A, 2019)

Potent anti-MRSA activity and synergism with aminoglycosides by flavonoid derivatives from the root barks of Morus alba, a traditional Chinese medicine - Guo-Ying Zuo; Cui-Xian Yang; Zhao-Juan Ruan; Jun Han; Gen-Chun Wang (Medicinal Chemistry Research, 2019)

iTRAQ-based analysis of 17β-estradiol induced proteome in Chinese tongue sole Cynoglossus semilaevis - Ying Zhu; Yangzhen Li; Hailong Li; Lei Wang; Ning Zhang; Yang Liu; Liang Meng; Xiwen Xu; Zhongdian Dong; Min Wei; Hua Guo; Zhongkai Cui; et al. (Journal of Oceanology and Limnology, 2019)

The orphan nuclear receptor NUR77 promotes trophoblast invasion at early pregnancy through paracrine placental growth factor - Xiao-Cui Li; Xiang-Jie Yin; Wei Hong; Jie Liu; Feng Jin; Bei-Ying Wang; Yu-Mei Wang; Fu-Ju Tian (Journal of Molecular Medicine, 2019)

Alterations in the skin microbiome are associated with disease severity and treatment in the perioral zone of the skin of infants with atopic dermatitis - Yumei Zheng; Qian Wang; Laiji Ma; Yuanyuan Chen; Ying Gao; Gaolei Zhang; Shumei Cui; Haiyun Liang; Congfen He; Liya Song (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

An assessment of the performance of two snow kernels in characterizing snow scattering properties - Anxin Ding; Ziti Jiao; Yadong Dong; Ying Qu; Xiaoning Zhang; Chuan Xiong; Dandan He; Siyang Yin; Lei Cui; Yaxuan Chang (International Journal of Remote Sensing, 2019)

MicroRNAs Involved in the Regulation of LC-PUFA Biosynthesis in Teleosts: miR-33 Enhances LC-PUFA Biosynthesis in Siganus canaliculatus by Targeting insig1 which in Turn Upregulates srebp1 - Jun Jun Sun; Li Guo Zheng; Cui Ying Chen; Jin Ying Zhang; Cui Hong You; Qing Hao Zhang; Hong Yu Ma; Óscar Monroig; Douglas R. Tocher; Shu Qi Wang; Yuan You Li (Marine Biotechnology, 2019)

Design, synthesis, bioactivity, and DFT calculation of 2-thiazolyl-hydrazone derivatives as influenza neuraminidase inhibitors - Man-Ying Cui; Jian-Xia Nie; Zhong-Zhong Yan; Meng-Wu Xiao; Ding Lin; Jiao Ye; Ai-Xi Hu (Medicinal Chemistry Research, 2019)

Down-regulation of miR-377 suppresses high glucose and hypoxia-induced angiogenesis and inflammation in human retinal endothelial cells by direct up-regulation of target gene SIRT1 - Chunmei Cui; Yuehua Li; Ying Liu (Human Cell, 2019)

Glacier extent changes and possible causes in the Hala Lake Basin of Qinghai-Tibet Plateau - Dong-Sheng Li; Bu-Li Cui; Ying Wang; Bei Xiao; Bao-Fu Jiang (Journal of Mountain Science, 2019)

Seabed deposition and erosion change and influence factors in the Yangshan Deepwater Port over the years - Shuhua Zuo; Hualiang Xie; Xiaoming Ying; Cheng Cui; Yuxin Huang; Huaiyuan Li; Mingxiao Xie (Acta Oceanologica Sinica, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Accelerated Versus Conventional Corneal Collagen Cross-Linking in the Treatment of Keratoconus: A Meta-analysis and Review of the Literature - Yang Jiang; Shan Yang; Ying Li; Ge Cui; Thomas Chengxuan Lu (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Cyclosporin A Protected Cardiomyocytes Against Oxidative Stress Injury by Inhibition of NF-κB Signaling Pathway - Meng Ma; Xiaohui Ma; Jie Cui; Yifeng Guo; Xiuqin Tang; Chuanmin Chen; Ying Zhu; Chao Cui; Gang Wang (Cardiovascular Engineering and Technology, 2019)

A novel SGNH family hydrolase Ali5 with thioesterase activity and a GNSL motif but without a classic GDSL motif from Altererythrobacter ishigakiensis - Li-Guo Hong; Shu-Ling Jian; Ying-Yi Huo; Hong Cheng; Xiao-Jian Hu; Jixi Li; Heng-Lin Cui; Xue-Wei Xu (Biotechnology Letters, 2019)

Ecological Offsetting in China’s Coastal Wetlands: Existing Challenges and Strategies for Future Improvement - Shuling Yu; Baoshan Cui; Chengjie Xie; Xu Ma; Ying Man; Zhonghua Ning (Chinese Geographical Science, 2019)

Long-term spatiotemporal variations of atmospheric sulfur, nitrogen and particle pollutants in Chongqing, southwest China: implication of industrial transfer - Ying Peng; Jian Cui; Hongyun Zhu; Youhui Cao; Ke Du; Dongrui Yao (Environmental Science and Pollution Research, 2019)

Study on nitrogen removal from rice paddy field drainage by interaction of plant species and hydraulic conditions in eco-ditches - Huanhao Han; Yuanlai Cui; Rong Gao; Ying Huang; Yufeng Luo; Shizhou Shen (Environmental Science and Pollution Research, 2019)

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Anti-Hypertensive Action of Fenofibrate via UCP2 Upregulation Mediated by PPAR Activation in Baroreflex Afferent Pathway - Jian Guan; Miao Zhao; Chao He; Xue Li; Ying Li; Jie Sun; Wei Wang; Ya-Li Cui; Qing Zhang; Bai-Yan Li; Guo-Fen Qiao (Neuroscience Bulletin, 2019)

Altered Expression of Zinc Transporter ZIP12 in Broilers of Ascites Syndrome Induced by Intravenous Cellulose Microparticle Injection - Hao Cui; Jianxin Liu; Guming Xu; Xujiao Ren; Zhenbiao Li; Ying Li; Zhangyong Ning (Biochemical Genetics, 2019)

Integrated analysis of transcription factors and targets co-expression profiles reveals reduced correlation between transcription factors and target genes in cancer - Jinsheng Liang; Ying Cui; Yuhuan Meng; Xingsong Li; Xueping Wang; Wanli Liu; Lizhen Huang; Hongli Du (Functional & Integrative Genomics, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Development of a Reverse Transcription-Recombinase Polymerase Amplification Assay for Detection of Sugarcane Yellow Leaf Virus - Xiao-Yan Feng; Lin-Bo Shen; Wen-Zhi Wang; Jun-Gang Wang; Zheng-Ying Cao; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2018)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

The complete mitochondrial genome of an endangered reef gastropods Trochus pyramis - Zhi-ying Zhao; Zhi-gang Tu; Jing Cui; Li-rong Bai (Conservation Genetics Resources, 2018)

Effects of Different Land Types on Soil Enzyme Activity in the Qinghai Lake Region - Yuguo Yang; Ying Yang; Yuqing Geng; Guilin Huang; Xueqing Cui; Meng Hou (Wetlands, 2018)

White Matter Deficits Underlying the Impaired Consciousness Level in Patients with Disorders of Consciousness - Xuehai Wu; Jiaying Zhang; Zaixu Cui; Weijun Tang; Chunhong Shao; Jin Hu; Jianhong Zhu; Yao Zhao; Lu Lu; Gang Chen; Georg Northoff; Gaolang Gong; et al. (Neuroscience Bulletin, 2018)

A case study on the occurrence, transport, and fate of mercury species in a sewage treatment plant in Jiaozuo, China - Hao Liu; Ying Cui; Hua Li; Yuxiang Mao (Environmental Science and Pollution Research, 2018)

Polybrominated diphenyl ethers in cord blood and perinatal outcomes from Laizhou Wan Birth Cohort, China - Limei Chen; Caifeng Wang; Yan Zhang; Yijun Zhou; Rong Shi; Chang Cui; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2018)

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

Ethanol extract of Rehmannia glutinosa exerts antidepressant-like effects on a rat chronic unpredictable mild stress model by involving monoamines and BDNF - Jun-Ming Wang; Li-Xin Pei; Yue-Yue Zhang; Yong-Xian Cheng; Chun-Ling Niu; Ying Cui; Wei-Sheng Feng; Gui-Fang Wang (Metabolic Brain Disease, 2018)

Proteomic analysis of human umbilical vein endothelial cells exposed to PM2.5 - Ji Zhu; Lin-wen-si Zhu; Jin-huan Yang; Ying-ling Xu; Cui Wang; Zhuo-yu Li; Wei Mao; De-zhao Lu (Journal of Zhejiang University-SCIENCE B, 2018)

Optimized staggered-grid finite-difference operators using window functions - Ying-Jun Ren; Jian-Ping Huang; Peng Yong; Meng-Li Liu; Chao Cui; Ming-Wei Yang (Applied Geophysics, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Fate of antibiotic and metal resistance genes during two-phase anaerobic digestion of residue sludge revealed by metagenomic approach - Ying Wu; Erping Cui; Yiru Zuo; Weixiao Cheng; Hong Chen (Environmental Science and Pollution Research, 2018)

Functional Investigation of a GRIN2A Variant Associated with Rolandic Epilepsy - Xing-Xing Xu; Xiao-Rong Liu; Cui-Ying Fan; Jin-Xing Lai; Yi-Wu Shi; Wei Yang; Tao Su; Jun-Yu Xu; Jian-Hong Luo; Wei-Ping Liao (Neuroscience Bulletin, 2018)

Responses of soil microbial community to nitrogen fertilizer and precipitation regimes in a semi-arid steppe - Yi-Fei Sun; Ju-Pei Shen; Cui-Jing Zhang; Li-Mei Zhang; Wen-Ming Bai; Ying Fang; Ji-Zheng He (Journal of Soils and Sediments, 2018)

Characterization of an endangered marine strombid gastropod Strombus luhuanus complete mitochondrial genome - Zhi-ying Zhao; Zhi-gang Tu; Li-rong Bai; Jing Cui (Conservation Genetics Resources, 2018)

Dysfunction of GABAergic neurons in the parafacial zone mediates sleep disturbances in a streptozotocin-induced rat model of sporadic Alzheimer’s disease - Jin-Zhi Song; Su-Ying Cui; Xiang-Yu Cui; Xiao Hu; Yu-Nu Ma; Hui Ding; Hui Ye; Yong-He Zhang (Metabolic Brain Disease, 2018)

A new isoflavone from the roots of Ficus auriculata - Cui-Cui Qi; Yan-Hui Fu; Wen-Hao Chen; Guang-Ying Chen; Chun-Yan Dai; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

The complete mitochondrial genome of goby Acentrogobius viridipunctatus - Zhi-ying Zhao; Zhi-gang Tu; Jing Cui (Conservation Genetics Resources, 2017)

Cerebral perfusion alterations in type 2 diabetes and its relation to insulin resistance and cognitive dysfunction - Ying Cui; Xia Liang; Hong Gu; Yuzheng Hu; Zhen Zhao; Xiang-Yu Yang; Cheng Qian; Yihong Yang; Gao-Jun Teng (Brain Imaging and Behavior, 2017)

The aflatoxin-detoxifizyme specific expression in the parotid gland of transgenic pigs - An-gang Lou; Jin-shun Cai; Xue-mei Zhang; Cheng-dou Cui; Ying-shu Piao; Li-zeng Guan (Transgenic Research, 2017)

Effects of feeding rates on growth, feed utilization, and body composition of juvenile Pseudobagrus ussuriensis - Xianyong Bu; Xuqiu Lian; Ying Zhang; Chenghui Yang; Cunhe Cui; Jianfang Che; Baibing Tang; Baohui Su; Qicun Zhou; Yuhong Yang (Aquaculture International, 2017)

Recent advances in decomposition of the most potent greenhouse gas SF 6 - Xiaoxing Zhang; Hanyan Xiao; Ju Tang; Zhaolun Cui; Ying Zhang (Critical Reviews in Environmental Science and Technology, 2017)

Mitochondrial genome of the sand goby Acentrogobius caninus (Acentrogobius, Gobiidae) - Zhi-gang Tu; Zhi-ying Zhao; Jing Cui; Guang-can Wu (Conservation Genetics Resources, 2017)

Arsenic sorption by red mud-modified biochar produced from rice straw - Chuan Wu; Liu Huang; Sheng-Guo Xue; Yu-Ying Huang; William Hartley; Meng-qian Cui; Ming-Hung Wong (Environmental Science and Pollution Research, 2017)

Effects of endogenous hormones on variation of shoot branching in a variety of non-heading Chinese cabbage and related gene expression - Xue-Wei Cao; Hong-Mi Cui; Yuan Yao; Ai-Sheng Xiong; Xi-Lin Hou; Ying Li (Journal of Plant Biology, 2017)

The Interaction of Mitochondrial Biogenesis and Fission/Fusion Mediated by PGC-1α Regulates Rotenone-Induced Dopaminergic Neurotoxicity - Kaige Peng; Likui Yang; Jian Wang; Feng Ye; Guorong Dan; Yuanpeng Zhao; Ying Cai; Zhihong Cui; Lin Ao; Jinyi Liu; Zhongmin Zou; Yan Sai; et al. (Molecular Neurobiology, 2017)

Impact of socioeconomic and meteorological factors on reservoirs’ air quality: a case in the Three Gorges Reservoir of Chongqing (TGRC), China over a 10-year period - Ying Peng; Fengwu Zhou; Jian Cui; Ke Du; Qiangmei Leng; Fumo Yang; Andy Chan; Hongting Zhao (Environmental Science and Pollution Research, 2017)

Detection and Monitoring of Oil Spills Using Moderate/High-Resolution Remote Sensing Images - Ying Li; Can Cui; Zexi Liu; Bingxin Liu; Jin Xu; Xueyuan Zhu; Yongchao Hou (Archives of Environmental Contamination and Toxicology, 2017)

The behavior of antibiotic resistance genes and arsenic influenced by biochar during different manure composting - Erping Cui; Ying Wu; Yanan Jiao; Yiru Zuo; Christopher Rensing; Hong Chen (Environmental Science and Pollution Research, 2017)

Polyguluronate sulfate and its oligosaccharides but not heparin promotes FGF19/FGFR1c signaling - Ying Lan; Xuan Zeng; Zhihua Guo; Pengjiao Zeng; Cui Hao; Xia Zhao; Guangli Yu; Lijuan Zhang (Journal of Ocean University of China, 2017)

Processes of coastal ecosystem carbon sequestration and approaches for increasing carbon sink - Yao Zhang; MeiXun Zhao; Qiu Cui; Wei Fan; JiaGuo Qi; Ying Chen; YongYu Zhang; KunShan Gao; JingFeng Fan; GuangYi Wang; ChongLing Yan; HaoLiang Lu; et al. (Science China Earth Sciences, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Polyguluronate sulfate, polymannuronate sulfate, and their oligosaccharides have antithrombin III- and heparin cofactor II-independent anticoagulant activity - Xuan Zeng; Ying Lan; Pengjiao Zeng; Zhihua Guo; Cui Hao; Lijuan Zhang (Journal of Ocean University of China, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Chemical constituents from the roots of Ampelopsis delavayana and their antibacterial activities - Shuang-Xi Mei; Xu-Hong Li; Li-Guo Yang; Xiao-Hui Li; Jia-Ying Xie; Qi Yao; Mei Su; Tao Cui; Jing-Kun Wang; Zhao-Yun Zhu (Natural Product Research, 2017)

The accumulation and health risk of heavy metals in vegetables around a zinc smelter in northeastern China - Bo Li; Yanhong Wang; Yong Jiang; Guochen Li; Jiehua Cui; Ying Wang; Hong Zhang; Shicheng Wang; Sheng Xu; Ruzhen Wang (Environmental Science and Pollution Research, 2016)

Application of high resolution SNP arrays in patients with congenital oral clefts in south China - TING-YING LEI; HONG-TAO WANG; FAN LI; YING-QIU CUI; FANG FU; RU LI; CAN LIAO (Journal of Genetics, 2016)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

A comparative analysis of the evolution, expression, and cis-regulatory element of polygalacturonase genes in grasses and dicots - Ying Liang; Youjian Yu; Jinlong Cui; Meiling Lyu; Liai Xu; Jiashu Cao (Functional & Integrative Genomics, 2016)

Transcriptome analysis of sika deer in China - Bo-Yin Jia; Heng-Xing Ba; Gui-Wu Wang; Ying Yang; Xue-Zhe Cui; Ying-Hua Peng; Jun-Jun Zheng; Xiu-Mei Xing; Fu-He Yang (Molecular Genetics and Genomics, 2016)

Geniposide alleviates depression-like behavior via enhancing BDNF expression in hippocampus of streptozotocin-evoked mice - Junming Wang; Peili Duan; Ying Cui; Qing Li; Yanran Shi (Metabolic Brain Disease, 2016)

Sleep and Cognitive Abnormalities in Acute Minor Thalamic Infarction - Wei Wu; Linyang Cui; Ying Fu; Qianqian Tian; Lei Liu; Xuan Zhang; Ning Du; Ying Chen; Zhijun Qiu; Yijun Song; Fu-Dong Shi; Rong Xue (Neuroscience Bulletin, 2016)

Host protein Snapin interacts with human cytomegalovirus pUL130 and affects viral DNA replication - Guili Wang; Gaowei Ren; Xin Cui; Zhitao Lu; Yanpin Ma; Ying Qi; Yujing Huang; Zhongyang Liu; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2016)

Soil microbial community composition and its driving factors in alpine grasslands along a mountain elevational gradient - Hai-jun Cui; Gen-xu Wang; Yan Yang; Yang Yang; Rui-ying Chang; Fei Ran (Journal of Mountain Science, 2016)

Seismic dynamic monitoring in CO2 flooding based on characterization of frequency-dependent velocity factor - Jun-Hua Zhang; Jun Li; Wen Xiao; Ming-You Tan; Yun-Ying Zhang; Shi-Ling Cui; Zhi-Peng Qu (Applied Geophysics, 2016)

Interleukin-12 inhibits the hepatocellular carcinoma growth by inducing macrophage polarization to the M1-like phenotype through downregulation of Stat-3 - Qin Wang; Feng Cheng; Ting-ting Ma; Hai-Yu Xiong; Zi-Wei Li; Chang-Li Xie; Cui-Ying Liu; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2016)

Follicle-stimulating hormone increases the intramuscular fat content and expression of lipid biosynthesis genes in chicken breast muscle - Xiao-yan Cui; Ying-ying Li; Ran-ran Liu; Gui-ping Zhao; Mai-qing Zheng; Qing-he Li; Jie Wen (Journal of Zhejiang University-SCIENCE B, 2016)

Knockdown of α-synuclein in cerebral cortex improves neural behavior associated with apoptotic inhibition and neurotrophin expression in spinal cord transected rats - You-Cui Wang; Guo-Ying Feng; Qing-Jie Xia; Yue Hu; Yang Xu; Liu-lin Xiong; Zhi-wei Chen; Hang-Ping Wang; Ting-Hua Wang; Xue Zhou (Apoptosis, 2016)

Active capping technology: a new environmental remediation of contaminated sediment - Chang Zhang; Meng-ying Zhu; Guang-ming Zeng; Zhi-gang Yu; Fang Cui; Zhong-zhu Yang; Liu-qing Shen (Environmental Science and Pollution Research, 2016)

A Comparison of Different-Mode Fields Generated from Grounded-Wire Source Based on the 1D Model - Nan-Nan Zhou; Guo-qiang Xue; Hai Li; M. Younis; Dong-yang Hou; Hua-sen Zhong; Wei-ying Chen; Jiang-wei Cui (Pure and Applied Geophysics, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Morphology, sex steroid level and gene expression analysis in gonadal sex reversal of triploid female (XXX) rainbow trout (Oncorhynchus mykiss) - Gefeng Xu; Tianqing Huang; Xian Jin; Cunhe Cui; Depeng Li; Cong Sun; Ying Han; Zhenbo Mu (Fish Physiology and Biochemistry, 2016)

Stormwater infiltration and surface runoff pollution reduction performance of permeable pavement layers - Zhi-Guang Niu; Zhi-Wei Lv; Ying Zhang; Zhen-Zhen Cui (Environmental Science and Pollution Research, 2016)

Chikusetsu Saponin IVa Ameliorates Cerebral Ischemia Reperfusion Injury in Diabetic Mice via Adiponectin-Mediated AMPK/GSK-3β Pathway In Vivo and In Vitro - Jialin Duan; Ying Yin; Jia Cui; Jiajia Yan; Yanrong Zhu; Yue Guan; Guo Wei; Yan Weng; Xiaoxiao Wu; Chao Guo; Yanhua Wang; Miaomiao Xi; et al. (Molecular Neurobiology, 2016)

Phylogeny and taxonomy of the genus Anomoloma (Amylocorticiales, Basidiomycota) - Jie Song; Xue-Ying Liu; Min Wang; Bao-Kai Cui (Mycological Progress, 2016)

Trends in the prevalence of heart diseases over a ten-year period from single-center observations based on a large echocardiographic database - Hao Lu; Wen-zhi Pan; Quan Wan; Lei-lei Cheng; Xian-hong Shu; Cui-zhen Pan; Ju-ying Qian; Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2016)

A novel Halomonas ventosae-specific virulent halovirus isolated from the Qiaohou salt mine in Yunnan, Southwest China - Chao-Qun Fu; Qin Zhao; Zhi-Ying Li; Yong-Xia Wang; Shi-Ying Zhang; Yong-Hong Lai; Wei Xiao; Xiao-Long Cui (Extremophiles, 2016)

Glucocorticoid Receptor β Acts as a Co-activator of T-Cell Factor 4 and Enhances Glioma Cell Proliferation - Qian Wang; Pei-Hua Lu; Zhi-Feng Shi; Yan-Juan Xu; Jie Xiang; Yan-Xia Wang; Ling-Xiao Deng; Ping Xie; Ying Yin; Bin Zhang; Hui-Jun Mu; Wei-Zhen Qiao; et al. (Molecular Neurobiology, 2015)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Detection of α S2-casein variants in Chinese yak (Bos grunniens) by PCR-SSCP - XIAOJUN QU; YANHUA CUI; TING YU; TONG HU; CHAO WANG; XIAOMENG LV; YING MA (Journal of Genetics, 2015)

Efficacy and tolerability of canagliflozin as add-on to metformin in the treatment of type 2 diabetes mellitus: a meta-analysis - Ting Yang; Min Lu; Lingyue Ma; Ying Zhou; Yimin Cui (European Journal of Clinical Pharmacology, 2015)

Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2015)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

Palynomorph assemblages and paleoclimate records from the Zhuanchengzi Bed of the Yixian Formation, western Liaoning Province, China - Ying Cui; EnPu Gong; TieHui Wang; ChangQing Guan; YongLi Zhang; JunHong Liang (Science China Earth Sciences, 2015)

Effects of MAL61 and MAL62 overexpression on maltose fermentation of baker’s yeast in lean dough - Cui-Ying Zhang; Xue Lin; Hai-Yan Song; Dong-Guang Xiao (World Journal of Microbiology and Biotechnology, 2015)

Polycyclic aromatic hydrocarbons in the largest deepwater port of East China Sea: impact of port construction and operation - Juan-Ying Li; Yu Cui; Lei Su; Yiqin Chen; Ling Jin (Environmental Science and Pollution Research, 2015)

Effects of a rhizobacterium on the growth of and chromium remediation by Lemna minor - Jie Tang; Ying Zhang; Yan Cui; Jiong Ma (Environmental Science and Pollution Research, 2015)

Exploration of copula function use in crop meteorological drought risk analysis: a case study of winter wheat in Beijing, China - Ying Li; Wei Gu; Weijia Cui; Zhiyun Chang; Yingjun Xu (Natural Hazards, 2015)

Isolation and characterization of thirty-eight microsatellite loci for the Pinus wangii, an endangered species - Zhi-Yong Zhang; Binbin Cui; Jian-Feng Mao; Xiao-Ming Pang; Ying-Yue Li (Conservation Genetics Resources, 2015)

Plastorhodobacter daqingensis gen. nov., sp. nov.: A Non-phototrophic Bacterium Isolated from Daqing Oilfield - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Arenimonas taoyuanensis sp. nov., a novel bacterium isolated from rice-field soil in China - Shi-Ying Zhang; Wei Xiao; Yun-Sheng Xia; Yong-Xia Wang; Xiao-Long Cui; Nai-Ming Zhang (Antonie van Leeuwenhoek, 2015)

Association mapping of salinity and alkalinity tolerance in improved japonica rice (Oryza sativa L. subsp. japonica Kato) germplasm - Di Cui; Chang-ying Xu; Chun-gang Yang; Qi-xing Zhang; Jun-guo Zhang; Xiao-ding Ma; Yong-li Qiao; Gui-lan Cao; San-yuan Zhang; Long-zhi Han (Genetic Resources and Crop Evolution, 2015)

AKT Pathway Affects Bone Regeneration in Nonunion Treated with Umbilical Cord-Derived Mesenchymal Stem Cells - Zhiguo Qu; Shengnan Guo; Guojun Fang; Zhenghong Cui; Ying Liu (Cell Biochemistry and Biophysics, 2015)
We have previously grafted human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) with blood plasma to treat rat tibia nonunion. To further examine the biological characteristics of this process, we applied an established hUC-MSCs-treated rat nonunion model with the addition of an inhibitor of AKT. SD rats (80) were randomly divided into four groups: a fracture group (positive control); a nonunion group (negative control); a hUC-MSCs grafting with blood plasma group; and a hUC-MSCs grafting with blood plasma & AKT blocker group. The animals were sacrificed under deep anesthesia at 4 and 8 weeks post fracture for analysis. The fracture line became less defined at 4 weeks and disappeared at 8 weeks postoperatively in both the hUC-MSCs grafting with blood plasma and grafting with blood plasma & the AKT blocker, which is similar to the fracture group. Histological immunofluorescence studies showed that the numbers of hUC-MSCs in the calluses were significantly higher in the hUC-MSCs grafting with blood plasma than those in group with the AKT blocker. More bone morphogenetic protein 2 and bone sialoprotein expression and less osteoprotegerin and bone gla protein expression were observed in the AKT blocker group compared to the hUC-MSCs grafting with blood plasma. AKT gene expression in the AKT blocker group was decreased 50 % compared to the hUC-MSCs with plasma group and decreased 70 % compared to the fracture group, while the elastic modulus was decreased. In summary, our work demonstrates that AKT may play a role in modulating osteogenesis induced by hUC-MSCs.

Endophytes in the plant Huperzia serrata: fungal diversity and discovery of a new pentapeptide - Zhi-Qiang Xiong; Ying-Ying Yang; Qiao-Xia Liu; Cui-Cui Sun; Yu Jin; Yong Wang (Archives of Microbiology, 2015)

Characteristics of porosity and permeability layer of fossil Halimeda reef mineral rock of Miocene in the Xisha Islands and its genetic model - Hong Xu; Yurui Zhu; G. P. Eberli; Wei Luo; Xinwei Zhao; Ying Cai; Xinyu Liu; Guijing Yan; Bolin Zhang; Kai Wei; Ruyong Cui (Acta Oceanologica Sinica, 2015)

Up-regulation of integrin α6β4 expression by mitogens involved in dairy cow mammary development - Feng Zhao; Chang Liu; Yu-Meng Hao; Bo Qu; Ying-Jun Cui; Na Zhang; Xue-Jun Gao; Qing-Zhang Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Novel polymorphic EST-derived microsatellite markers for the red-listed five needle pine, Pinus dabeshanensis - Zhi-Yong Zhang; Bin-Bin Cui; Jian-Feng Mao; Xiao-Ming Pang; Hui Liu; Ying-Yue Li (Conservation Genetics Resources, 2015)

Development of 36 novel polymorphic microsatellites for the critically endangered tree Pinus squamaia, by transcriptome database mining - Jian-Feng Mao; Bin-Bin Cui; Zhi-Yong Zhang; Hui Liu; Ying-Yue Li (Conservation Genetics Resources, 2015)

Three-dimensional tensor controlled-source electromagnetic modeling based on the vector finite-element method - Ying-Cai Hu; Tong-Lin Li; Cui-Song Fan; Da-Yong Wang; Jian-Ping Li (Applied Geophysics, 2015)

The role of visfatin on the regulation of inflammation and apoptosis in the spleen of LPS-treated rats - Ke Xiao; Wei-Hua Zou; Zhi Yang; Zia ur Rehman; Abdur Rahman Ansari; Huai-Rui Yuan; Ying Zhou; Lu Cui; Ke-Mei Peng; Hui Song (Cell and Tissue Research, 2015)

Halodurantibacterium flavum gen. nov., sp. nov., a Non-phototrophic Bacterium Isolated from an Oil Production Mixture - Xiang-Lin Lv; Bai-Sheng Xie; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Seohaeicola nanhaiensis sp. nov., A Moderately Halophilic Bacterium Isolated from the Benthic Sediment of South China Sea - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Yan-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2014)

Genetic variation in the β-lactoglobulin of Chinese yak (Bos grunniens) - YANHUA CUI; YU CAO; YING MA; XIAOJUN QU; AIJUN DONG (Journal of Genetics, 2014)

Upregulation of EHD2 after Intracerebral Hemorrhage in Adult Rats - Kaifu Ke; Ying Rui; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Maohong Cao (Journal of Molecular Neuroscience, 2014)

Functional analysis of FABP3 in the milk fat synthesis signaling pathway of dairy cow mammary epithelial cells - Meng-yao Liang; Xiao-ming Hou; Bo Qu; Na Zhang; Nan Li; Ying-jun Cui; Qing-zhang Li; Xue-jun Gao (In Vitro Cellular & Developmental Biology - Animal, 2014)

Expression, cloning, and IgE-binding of the full-length dust mite allergen Der f 8 - Yu-bao Cui; Ying Zhou; Nan Wang; Fei-xiang Teng; Li-li Yu; Yong-hua Bian; Jin-xia Song; Li Yang; Cheng-bo Zhang (Immunologic Research, 2014)

A homolog of glyceraldehyde-3-phosphate dehydrogenase from Riemerella anatipestifer is an extracellular protein and exhibits biological activity - Ji-ye Gao; Cui-lian Ye; Li-li Zhu; Zhi-ying Tian; Zhi-bang Yang (Journal of Zhejiang University-SCIENCE B, 2014)

Selenium Promotes the Growth and Photosynthesis of Tomato Seedlings Under Salt Stress by Enhancing Chloroplast Antioxidant Defense System - Ming Diao; Long Ma; Jianwei Wang; Jinxia Cui; Aifei Fu; Hui-ying Liu (Journal of Plant Growth Regulation, 2014)

Deep-Red Phosphorescent Iridium(III) Complexes Containing 1-(Benzo[b] Thiophen-2-yl) Isoquinoline Ligand: Synthesis, Photophysical and Electrochemical Properties and DFT Calculations - Gao-Nan Li; Ying Zou; Yi-Ding Yang; Jiao Liang; Feng Cui; Tao Zheng; Hui Xie; Zhi-Gang Niu (Journal of Fluorescence, 2014)

Estimating impacts of land use on groundwater quality using trilinear analysis - Ying Ouyang; Jia En Zhang; Lihua Cui (Environmental Monitoring and Assessment, 2014)

The checkpoint 1 kinase inhibitor LY2603618 induces cell cycle arrest, DNA damage response and autophagy in cancer cells - Feng-Ze Wang; Hong-rong Fei; Ying-Jie Cui; Ying-Kun Sun; Zhao-Mei Li; Xue-Ying Wang; Xiao-Yi Yang; Ji-Guo Zhang; Bao-Liang Sun (Apoptosis, 2014)

Platelet-derived growth factor-BB induces matrix metalloproteinase-2 expression and rat vascular smooth muscle cell migration via ROCK and ERK/p38 MAPK pathways - Ying Cui; Yin-Wei Sun; Hai-Shuang Lin; Wei-Min Su; Yan Fang; Ying Zhao; Xiao-Qing Wei; Yuan-Hua Qin; Kazuhiro Kohama; Ying Gao (Molecular and Cellular Biochemistry, 2014)

Dissipation and residue of metalaxyl and cymoxanil in pepper and soil - Xiangyun Liu; Yan Yang; Ying Cui; Huijun Zhu; Xiong Li; Zhining Li; Kankan Zhang; Deyu Hu (Environmental Monitoring and Assessment, 2014)

A novel deletion mutation of the ADAR1 gene in a Chinese patient with dyschromatosis symmetrica hereditaria - WEI-WEI LI; QIU-YUE WU; NA LI; DE-QUAN DENG; RU-SONG ZHANG; YING-XIA CUI; XIAO-JUN LI; XIN-YI XIA (Journal of Genetics, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Halomonas qiaohouensis sp. nov., isolated from salt mine soil in southwest China - Yong-Xia Wang; Wei Xiao; Ming-Hua Dong; Qin Zhao; Zhi-Ying Li; Yong-Hong Lai; Xiao-Long Cui (Antonie van Leeuwenhoek, 2014)

Characterizing the heavy metal-complexing potential of fluorescent water-extractable organic matter from composted municipal solid wastes using fluorescence excitation–emission matrix spectra coupled with parallel factor analysis - Xiao-Song He; Bei-Dou Xi; Hong-Wei Pan; Xiang Li; Dan Li; Dong-Yu Cui; Wen-Bin Tang; Ying Yuan (Environmental Science and Pollution Research, 2014)

Flavonoids from the halophyte Apocynum venetum and their antifouling activities against marine biofilm-derived bacteria - Na-Na Kong; Sheng-Tao Fang; Ying Liu; Jian-Hua Wang; Cui-Yun Yang; Chuan-Hai Xia (Natural Product Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Effect of BRAF V600E mutation on tumor response of anti-EGFR monoclonal antibodies for first-line metastatic colorectal cancer treatment: a meta-analysis of randomized studies - Dandan Cui; Dan Cao; Yu Yang; Meng Qiu; Ying Huang; Cheng Yi (Molecular Biology Reports, 2014)

Repairing cartilage defects with bone marrow mesenchymal stem cells induced by CDMP and TGF-β1 - Gang Wu; Ying Cui; Linxiang Ma; Xinyu Pan; Xuefeng Wang; Ben Zhang (Cell and Tissue Banking, 2014)

Importance of Functional Ingredients in Yak Milk-Derived Food on Health of Tibetan Nomads Living Under High-Altitude Stress: A Review - Xusheng Guo; Ruijun Long; Michael Kreuzer; Luming Ding; Zhanhuan Shang; Ying Zhang; Yang Yang; Guangxin Cui (Critical Reviews in Food Science and Nutrition, 2014)

Circulating microparticles in patients with coronary heart disease and its correlation with interleukin-6 and C-reactive protein - Ying Cui; Lihui Zheng; Ming Jiang; Ru Jia; Xiao Zhang; Qishan Quan; Guiqin Du; Dongjin Shen; Xiaodan Zhao; Wenying Sun; Hongwei Xu; Lijuan Huang (Molecular Biology Reports, 2013)

Association of Endothelin-converting Enzyme-1b C-338A Polymorphism with Increased Risk of Ischemic Stroke in Chinese Han Population - Rui Li; Min Cui; Jin Zhao; Mingming Yu; Zegang Ying; Shiming Zhou; Huadong Zhou (Journal of Molecular Neuroscience, 2013)

Up-regulation of SGTB is associated with neuronal apoptosis after neuroinflammation induced by lipopolysaccharide - Maohong Cao; Wei Xu; Jian Yu; Heyi Zheng; Xiang Tan; Lei Li; Ying Rui; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Tao Tao; et al. (Journal of Molecular Histology, 2013)

Up-regulated expression of Bnip3L after intracerebral hemorrhage in adult rats - Ying Rui; Kaifu Ke; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Guangwei Zhao; Yilu Gao; Maohong Cao (Journal of Molecular Histology, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

A chloroplast membrane protein LTO1/AtVKOR involving in redox regulation and ROS homeostasis - Ying Lu; Hua-Rong Wang; Han Li; Hao-Ran Cui; Yue-Guang Feng; Xiao-Yun Wang (Plant Cell Reports, 2013)

AP-2α suppresses invasion in BeWo cells by repression of matrix metalloproteinase-2 and -9 and up-regulation of E-cadherin - Zhan Zhang; Ling Zhang; Liting Jia; Shihong Cui; Ying Shi; Aimin Chang; Xianxu Zeng; Peng Wang (Molecular and Cellular Biochemistry, 2013)

Increased Expression of Small Heat Shock Protein αB-crystallin After Intracerebral Hemorrhage in Adult Rats - Kaifu Ke; Lei Li; Ying Rui; Heyi Zheng; Xiang Tan; Wei Xu; Jianhua Cao; Jian Xu; Gang Cui; Guangfei Xu; Maohong Cao (Journal of Molecular Neuroscience, 2013)

Cardiovascular Toxicity of Different Sizes Amorphous Silica Nanoparticles in Rats After Intratracheal Instillation - Zhongjun Du; Dali Zhao; Li Jing; Guanqun Cui; Minghua Jin; Yang Li; Xiaomei Liu; Ying Liu; Haiying Du; Caixia Guo; Xianqing Zhou; Zhiwei Sun (Cardiovascular Toxicology, 2013)

Genomic sequence analysis of a new reassortant infectious bursal disease virus from commercial broiler flocks in central China - Pei Cui; Shi-Jie Ma; Yu-Geng Zhang; Xin-Sheng Li; Xiao-Yun Gao; Bao-An Cui; Hong-Ying Chen (Archives of Virology, 2013)

Vitexin protects against cardiac hypertrophy via inhibiting calcineurin and CaMKII signaling pathways - Cui-cui Lu; Ying-qi Xu; Ji-chao Wu; Peng-zhou Hang; Yan Wang; Chen Wang; Jian-wei Wu; Jian-cui Qi; Yong Zhang; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Verapamil reverses cardiac iron overload in streptozocin-induced diabetic rats - Hong-li Shan; Yan Wang; Jian-wei Wu; Peng-zhou Hang; Xin Li; Li-hua Sun; Jian-cui Qi; Yu-ying Mao; Zhi-dan Sun; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Small interfering RNA targeting Rac1 sensitizes colon cancer to dihydroartemisinin-induced cell cycle arrest and inhibited cell migration by suppressing NFκB activity - Peng Han; Ying Luan; Yanlong Liu; Zhiwei Yu; Jingwen Li; Zicheng Sun; Gang Chen; Binbin Cui (Molecular and Cellular Biochemistry, 2013)

Effects of urbanization on arable land requirements in China, based on food consumption patterns - Guilin Li; Ying Zhao; Shenghui Cui (Food Security, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

Upregulation of CBLL1 in rat brain cortex after lipopolysaccharide treated - Maohong Cao; Heyi Zheng; Xiang Tan; Wei Xu; Ying Rui; Lei Li; Xiaofei Liu; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Kaifu Ke; et al. (Journal of Molecular Histology, 2013)

Bacterial Diversity Analysis of Zhenjiang Yao Meat During Refrigerated and Vacuum-Packed Storage by 454 Pyrosequencing - Xiang Xiao; Ying Dong; Ying Zhu; Henglin Cui (Current Microbiology, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

Two new oleanane-type saponins from the husks of Xanthoceras sorbifolia Bunge - Ying-Ying Li; Zheng Xiang; Hao Cui; Hang Xiao; Ting-Guo Kang; De-Qiang Dou; Hai-Xue Kuang (Natural Product Research, 2013)

Syntheses and antiproliferative activity of some sulfated hydroximinosterols - Yanmin Huang; Jianguo Cui; Ying Li; Lei Fan; Yanxiao Jiao; Shaoyang Su (Medicinal Chemistry Research, 2013)

Targeted blockade of interleukin-8 abrogates its promotion of cervical cancer growth and metastasis - Suhui Wu; Haixia Shang; Lihuan Cui; Zheng Zhang; Yanli Zhang; Ying Li; Jun Wu; Ren-Ke Li; Jun Xie (Molecular and Cellular Biochemistry, 2012)

AP-2α–dependent regulation of Bcl-2/Bax expression affects apoptosis in the trophoblast - Ling Zhang; Liting Jia; Shihong Cui; Ying Shi; Aimin Chang; Peng Wang; Zhan Zhang (Journal of Molecular Histology, 2012)

New sphingolipid psychotramide A–D from the stem of Psychotria sp. - Cui-Xian Zhang; Xi-Xin He; Shan-Yue Guan; Ying Zhong; Chao-Zhan Lin; Tian-Qin Xiong; Chen-Chen Zhu (Natural Product Research, 2012)

Analysis of type 2 metallothionein gene from mangrove species (Kandelia candel) - Guo-Yong Huang; You-Shao Wang; Guang-Guo Ying; Ai-Cui Dang (Trees, 2012)

Atmospheric inorganic nitrogen in wet deposition to a red soil farmland in Southeast China, 2005–2009 - Jian Cui; Jing Zhou; Ying Peng; Yuan Qiu He; Andrew Chan (Plant and Soil, 2012)

Increased Th17 cell frequency concomitant with decreased Foxp3+ Treg cell frequency in the peripheral circulation of patients with carotid artery plaques - Zhen-dong Liu; Lin Wang; Fang-hong Lu; Hui Pan; Ying-xin Zhao; Shu-jian Wang; Shang-wen Sun; Cui-ling Li; Xiao-liang Hu (Inflammation Research, 2012)

Detection of Autoantibodies and Increased Concentrations of Interleukins in Plasma from Patients with Tourette's Syndrome - Yu-hang Cheng; Yi Zheng; Fan He; Jian-hong Yang; Wen-biao Li; Min-ling Wang; De-yan Cui; Ying Chen (Journal of Molecular Neuroscience, 2012)

Signal-purity-spectrum-based colored deconvolution - Guo-Fa Li; Geng-Xin Peng; Ying Yue; Wan-Li Wang; Yong-Fu Cui (Applied Geophysics, 2012)

Overexpression of a histone H3K4 demethylase, JMJ15, accelerates flowering time in Arabidopsis - Hongchun Yang; Huixian Mo; Di Fan; Ying Cao; Sujuan Cui; Ligeng Ma (Plant Cell Reports, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Molybdenum improves antioxidant and osmotic-adjustment ability against salt stress in Chinese cabbage (Brassica campestris L. ssp. Pekinensis) - Mu Zhang; Chengxiao Hu; Xiaohu Zhao; Qiling Tan; Xuecheng Sun; Anyong Cao; Min Cui; Ying Zhang (Plant and Soil, 2012)

Biological Characteristics and Effect of Human Umbilical Cord Mesenchymal Stem Cells (hUC-MSCs) Grafting with Blood Plasma on Bone Regeneration in Rats - Zhiguo Qu; Libin Guo; Guojun Fang; Zhenghong Cui; Shengnan Guo; Ying Liu (Cell Biochemistry and Biophysics, 2012)

Molecular detection of Torque teno mini virus (TTMV) in China - Caixia Zhu; Rong A; Congli Yuan; Ying Yu; Li Cui; S. D. Tang; Zhiwei Liu; Wei Zhao; Xiuguo Hua (Virus Genes, 2012)

Classification management for grassland using MODIS data: a case study in the Gannan region, China - Xia Cui; Zheng Gang Guo; Tian Gang Liang; Yu Ying Shen; Xing Yuan Liu; Yong Liu (International Journal of Remote Sensing, 2012)

Gene cloning, expression and functional characterization of a proliferation-inducing ligand (APRIL) from hedgehog (Erinaceus europaeus) - Xian-wei Cui; Wen Xiao; Chen-bo Ji; Ai-ying Tian; Jie Zhang; Shuang-quan Zhang (Molecular Biology Reports, 2012)

Pathology of urethral fibromuscular system related to parturition-induced stress urinary incontinence and TGF-β1/Smad pathway - Guang-Yong Li; Wan-Shou Cui; Feng Zhou; Zhe-Zhu Gao; Hua Xin; Tao Liu; Wei-Ren Li; Yan-Qing Gong; Guang-Yi Bai; Ying-Lu Guo; Zhong-Cheng Xin (Molecular and Cellular Biochemistry, 2012)

Electrical Resistivity Features of Compacted Expansive Soils - Mingliang Yan; Linchang Miao; Ying Cui (Marine Georesources & Geotechnology, 2012)

A comparative study of the characteristics of two Coxsackie A virus type 16 strains (genotype B) - ErXia Yang; Heng Zhao; Ying Zhang; JianSheng Liu; Yun Liao; LiChun Wang; PingFang Cui; LiXian Yang; LongDing Liu; ChengHong Dong; ShaoZhong Dong; CongWen Shao; et al. (Science China Life Sciences, 2012)

TNF-α Increases Bone Marrow Mesenchymal Stem Cell Migration to Ischemic Tissues - Qiong Xiao; Shi-kun Wang; Hua Tian; Li Xin; Zhi-geng Zou; Yan-lai Hu; Cui-ming Chang; Xue-ying Wang; Qun-sheng Yin; Xiang-hong Zhang; Li-yan Wang (Cell Biochemistry and Biophysics, 2012)

Molecular cloning, expression, sequence analyses of dust mite allergen Der f 6 and its IgE-binding reactivity with mite allergic asthma patients in southeast China - Yubao Cui; Ying Zhou; Weihong Shi; Guifang Ma; Li Yang; Yungang Wang; Li Li (Molecular Biology Reports, 2012)

Copula-based evaluations of drought variations in Guangdong, South China - Chun-Ling Liu; Qiang Zhang; Vijay P. Singh; Ying Cui (Natural Hazards, 2011)

Evaluation of suitable reference genes for gene expression studies in Lycoris longituba - SHAO JIE CUI; QIU LING HE; YING CHEN; MIN REN HUANG (Journal of Genetics, 2011)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)

P38-Nrf-2 Signaling Pathway of Oxidative Stress in Mice Caused by Nanoparticulate TiO2 - Jue Wang; Na Li; Lei Zheng; Sisi Wang; Ying Wang; Xiaoyang Zhao; Yanmei Duan; Yaling Cui; Min Zhou; Jingwei Cai; Songjie Gong; Han Wang; et al. (Biological Trace Element Research, 2011)

Association between HLA-DRB1, HLA-DRQB1 alleles, and CD4+CD28null T cells in a Chinese population with coronary heart disease - Wenjie Sun; Ying Cui; Lihui Zhen; Lijuan Huang (Molecular Biology Reports, 2011)

Proteome changes in the plasma of Pieris rapae parasitized by the endoparasitoid wasp Pteromalus puparum - Jia-ying Zhu; Qi Fang; Gong-yin Ye; Cui Hu (Journal of Zhejiang University-SCIENCE B, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

The Wenchuan Earthquake (May 12, 2008), Sichuan Province, China, and resulting geohazards - Peng Cui; Xiao-Qing Chen; Ying-Yan Zhu; Feng-Huan Su; Fang-Qiang Wei; Yong-Shun Han; Hong-Jiang Liu; Jian-Qi Zhuang (Natural Hazards, 2011)

Use of an innovative T-tube maze assay and the proboscis extension response assay to assess sublethal effects of GM products and pesticides on learning capacity of the honey bee Apis mellifera L. - Peng Han; Chang-Ying Niu; Chao-Liang Lei; Jin-Jie Cui; Nicolas Desneux (Ecotoxicology, 2010)

Quantification of toxins in a Cry1Ac + CpTI cotton cultivar and its potential effects on the honey bee Apis mellifera L. - Peng Han; Chang-Ying Niu; Chao-Liang Lei; Jin-Jie Cui; Nicolas Desneux (Ecotoxicology, 2010)

Effects of Soil Polycyclic Musk and Cadmium on Pollutant Uptake and Biochemical Responses of Wheat (Triticum aestivum) - Cui-hong Chen; Qi-xing Zhou; Zhang Cai; Ying-ying Wang (Archives of Environmental Contamination and Toxicology, 2010)

Expression of the housefly acetylcholinesterase in a bioreactor and its potential application in the detection of pesticide residues - Guo-Jun Lang; Jin-Yan Shang; Yan-Xia Chen; Ying-Jun Cui; Qiang Wang; Zhen-Hua Tang; Chuan-Xi Zhang (World Journal of Microbiology and Biotechnology, 2010)

Estimation of water dynamics in a vertical-flow constructed wetland with a growing plant species - Ying Ouyang; Shi Ming Luo; Li Hua Cui; Ying Hu Liu; Zhong Qin (Journal of Soils and Sediments, 2010)

Molecular characterization of T-DNA integration sites in transgenic birch - Fan-Suo Zeng; Ya-Guang Zhan; Hong-Cui Zhao; Ying Xin; Feng-Hui Qi; Chuan-Ping Yang (Trees, 2010)

Probability assessment of river blocking by debris flow associated with the Wenchuan Earthquake - Jian-Qi Zhuang; Peng Cui; Yong-Gang Ge; Yi-Ping He; Ying-Hui Liu; Xiao-Jun Guo (International Journal of Remote Sensing, 2010)

Improving Cellular Properties for Genetic Manipulation by Dispersed Growing Mutagenesis in Myxococcus fulvus HW-1 - Cui-ying Zhang; Ke Cai; Zhi-hong Wu; Yue-zhong Li (Current Microbiology, 2010)

A high-resolution record from Svalbard of carbon release during the Paleocene-Eocene thermal maximum - Ying Cui; Lee R. Kump; Andy Ridgwell; Aaron Diefendorf; Chris K. Junium (Journal of Earth Science, 2010)

Regulatory effects of insulin-like growth factor-1 on the expression of sensory neuropeptide mRNAs in cultured dorsal root ganglion neurons with excitotoxicity induced by glutamate - Hui-Cui Gong; Xiang-Dong Yang; Zhen Liu; Zi-Ying Xing; Huai-Jing Wang; Zhen-Zhong Li (Neuroscience Bulletin, 2010)

Mechanism of the Formation for Thoracic Impedance Change - Ming-Xing Kuang; Qiu-Jin Xiao; Chao-Ying Cui; Nan-Zhen Kuang; Wen-Qin Hong; Ai-Rong Hu (Annals of Biomedical Engineering, 2010)

Tumor cellular proteasome inhibition and growth suppression by 8-hydroxyquinoline and clioquinol requires their capabilities to bind copper and transport copper into cells - Shumei Zhai; Lei Yang; Qiuzhi Cindy Cui; Ying Sun; Q. Ping Dou; Bing Yan (JBIC Journal of Biological Inorganic Chemistry, 2010)

Variation of airborne bacteria and fungi at Emperor Qin's Terra-Cotta Museum, Xi'an, China, during the “Oct. 1” Gold Week Period of 2006 - Yi-Ping Chen; Ying Cui; Jun-Gang Dong (Environmental Science and Pollution Research, 2010)

Proteomic analysis reveals significant elevation of heat shock protein 70 in patients with chronic heart failure due to arrhythmogenic right ventricular cardiomyopathy - Ying-Jie Wei; Yin-Xia Huang; Ya Shen; Chuan-Jue Cui; Xiao-Ling Zhang; Hao Zhang; Sheng-Shou Hu (Molecular and Cellular Biochemistry, 2009)

Enhancement of photoelectrocatalytic properties of stainless-steel/TiO2 electrode by applying mid-frequency electric field - Ying Cui; Hao Du; Lishi Wen (Environmental Chemistry Letters, 2009)

The 12 May Wenchuan earthquake-induced landslide lakes: distribution and preliminary risk evaluation - Peng Cui; Ying-yan Zhu; Yong-shun Han; Xiao-qing Chen; Jian-qi Zhuang (Landslides, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Proteome changes in the plasma of Papilio xuthus (Lepidoptera: Papilionidae): effect of parasitization by the endoparasitic wasp Pteromalus puparum (Hymenoptera: Pteromalidae) - Jia-ying Zhu; Gong-yin Ye; Qi Fang; Cui Hu (Journal of Zhejiang University-SCIENCE B, 2009)

Nitric oxide inhibits the replication cycle of porcine parvovirus in vitro - Zhan-Yong Wei; Xue-Bin Wang; Xiao-Dong Ning; Ya-Bin Wang; Hong-Ying Zhang; Dong-Fang Wang; Hong-Ying Chen; Bao-An Cui (Archives of Virology, 2009)

Protective effect of puerarin on diabetic retinopathy in rats - Yan Teng; Hao Cui; Mingming Yang; Han Song; Qingsheng Zhang; Ying Su; Jianqiu Zheng (Molecular Biology Reports, 2009)

Molecular cloning, tissue distribution and bioinformatics analyses of the rabbit BK channel β1 subunit gene - Xiao-Yong Zhang; Sha Wang; Zhen Yan; Yi Wan; Wei Wang; Guang-Bin Cui; Pang Du; Ke-Jun Ma; Wei Han; Ying-Qi Zhang; Jing-Guo Wei (Molecular Biology Reports, 2008)

Phosphorus Sorption Capacities and Physicochemical Properties of Nine Substrate Materials for Constructed Wetland - Lihua Cui; Xizhen Zhu; Mei Ma; Ying Ouyang; Mei Dong; Wenling Zhu; Shiming Luo (Archives of Environmental Contamination and Toxicology, 2008)

Plane wave shot PSDM and controlled illumination techniques - Xingfu Cui; Hongbing Li; Ying Hu; Guibao Liu; Shukai Chen (Applied Geophysics, 2007)

Wavefield continuation datuming using a near surface model - Xingfu Cui; Hongbing Li; Ying Hu; Hong Liang; Li Qi (Applied Geophysics, 2007)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)

A novel 2-aminophenol 1,6-dioxygenase involved in the degradation of p-chloronitrobenzene by Comamonas strain CNB-1: purification, properties, genetic cloning and expression in Escherichia coli - Jian-Feng Wu; Cui-Wei Sun; Cheng-Ying Jiang; Zhi-Pei Liu; Shuang-Jiang Liu (Archives of Microbiology, 2005)

Streptacidiphilus jiangxiensis sp. nov., a novel actinomycete isolated from acidic rhizosphere soil in China - Ying Huang; Quingfeng Cui; Liming Wang; Carlos Rodriguez; Erika Quintana; Michael Goodfellow; Zhiheng Liu (Antonie van Leeuwenhoek, 2004)

RecA-Mediated, Targeted Mutagenesis in Zebrafish - Zongbin Cui; Ying Yang; Christopher D. Kaufman; Dritan Agalliu; Perry B. Hackett (Marine Biotechnology, 2003)

Epoxypropane biosynthesis by Methylomonas sp. GYJ3: batch and continuous studies - Jia-Ying Xin; Jun-Ru Cui; Li-Min Zhu; Jian-Bo Chen; Chun-Gu Xia; Shu-Ben Li (World Journal of Microbiology and Biotechnology, 2002)

Agronomic and morphological characterization of Agrobacterium-transformed Bt rice plants - Qing-yao Shu; Hai-rui Cui; Gong-yin Ye; Dian-xing Wu; Ying-wu Xia; Ming-wei Gao; Illimar Altosaar (Euphytica, 2002)